Multifunctional synergistic biomass-based composites: integrated design for energy conversion, electromagnetic shielding, and microwave absorption - Yinao Jiao; Shengjie Sui; Yifei Long; Guozhi Fan; Haitao Yang; Cheng Pan (Bioresource Technology, 2027)

Regulatory mechanism of combustion and emission for ammonia direct injection engines by coupling thermal insulation coating with EGR strategy - Pengbo Dong; Yuxuan Liu; Kunlong Liu; Jiangping Tian; Wuqiang Long; Zechuan Cui; Liyun Fan; Zhenxian Zhang; Qingyang Wang (Fuel, 2026)

TFR2 p.A75V mutation aggravates liver iron overload in alcoholic liver disease via ERK pathway - Chao Xie; Yingying Liu; Xiaofan Wang; Long Huang; Xiaoming Wang; Wei Zhang; Lina Wu; Tianhui Liu; Ping Wang; Lin Liu; Xu Fan; Jidong Jia; et al. (Journal of Molecular Medicine, 2026)

ANGPTL4 in gestational diabetes: a diagnostic biomarker linked to placental senescence - Yu-Feng He; Hui Chen; Chuan-Meng Zhang; Su-Su Yang; Xiao-Long Yang; Li-Shuai Jiang; Fan Wang; Shu-Guang Zhou (Functional & Integrative Genomics, 2026)

Mechanistic and functional integration of sirtuin deacylases: from substrate specificity to biological outcomes - Jian-long Zhang; Zi-Yu Dou; Yong-yue Fan; De-guan Sun; Xiong-jie Fan; Ze Yu; Guo-Cai Yang (Glycoconjugate Journal, 2026)

Phytochemical profiling of undescribed triterpenoids from Cyclocarya paliurus leaves: structural elucidation and metabolic regulation potential - Yiwei Wu; Huizhen Yang; Wenjie Shangguan; Wenting Zhang; Long Chen; Rui Min; Xinrong Fan; Yindi Zhu; Xiaojie Zheng; Yin Xiong; Tunhai Xu (Phytochemistry, 2026)

Spatial-temporal distribution of late Cenozoic intraplate basalts in the Leiqiong area, South China: Insights into the distinct roles of mantle plume and continental lithosphere during plume head emplacement - Guo-Hong Sun; Xiao-Long Huang; Fan Yang; Yang Yu; Sheng-Zhu Zhu (Lithos, 2026)

The role of continental and oceanic subduction in generating the giant Jiaodong gold province, China: Constraints from mercury isotopes - Hong Wang; Ting-Guang Lan; Yang Xu; Hong-Rui Fan; Huan-Long Hu; Lei Shu; Lang‑Ye Zhao; Xing-Hui Li (Gondwana Research, 2026)

Microneedle patches at the bio-agricultural Interface: Toward precision, resilience, and sustainability - Fangzheng Zhou; Xiaochen Huang; Yaqi Teng; Ping Yu; Boqiang Li; Haowen Sun; Yixin Gao; Ruikun He; Wei Sun; Bei Fan; Xiaoxue Jia; Long Li; et al. (Food Research International, 2026)

Self-healing materials for food packaging: Design principles, activation mechanisms and implications for food safety - Mengzi Nie; Runkang Qiu; Huihui Yang; Xiangyu Liang; Ziqian Li; Long Li; Bei Fan; Li-Tao Tong; Peihua Ma; Fengzhong Wang (Food Research International, 2026)

Structural and electrostatic regulation of water-ion transport in double-walled carbon nanotubes for enhanced desalination performance - Long Ma; Haifeng Liang; Jing Fan; Xuanji Jia; Boyuan Zheng; Shuhui Liu; Fenhong Song (Desalination, 2026)

Self-assembled redox-responsive prodrug nanoparticles based on thioketal-geraniol conjugate for ulcerative colitis therapy - Yanyu Wang; Lei Chen; Yulian Chen; Shushu Yang; Wenjie Xi; Huixing Wu; Changrui Long; Fan Xia; Jialin Liao; Ziqiong Liao; Shijian Xiang; Yang Kang; et al. (Chemical Engineering Journal, 2026)

Ultrafast kinetics and efficient PMS activation using a 2D calcined Co-MOF nanoconfined catalytic membrane for continuous tetracycline degradation - Jinsong He; Keyu Long; Fan Ni; Yongjia Lei; Wei Qu; Wei Shi; Yifeng Zhang; Fei Shen (Water Research, 2026)

Discovery of garnet-bearing peraluminous ferroan granites in the Trans-North China Orogen: Evidence for anatexis of residual metasedimentary crust in a hot collisional orogen - Jing-Jing Fan; Caiyun Lan; Yong-Min Li; Jun Rao; Zi-Long Wang; Ze-Xian Cui; Meng-Jing Li; Xiaoping Long (Precambrian Research, 2026)

2(3→20)-abeo-taxoids with adipogenesis inhibitory activity from the leaves and twigs of Taxus chinensis var. mairei - Li-Ping Long; Xin-Yu Fan; Yuan-Hui Yu; Yuan-Liang Xu; Lin-Xi Mao; Xue Tang; Kai Guo; Yan Liu; Sheng-Hong Li (Phytochemistry, 2026)

Heteroatom-enriched hypercrosslinked polymer adsorbent with amidoxime groups for high-performance uranium removal - Shuhui Fan; Ke Wang; Jinjiu Zhu; Aoxin Ouyang; Chenglin Xiong; Meifang Ye; Zi Long; Jianwen Tian; Xiaoyong Zhang; Yen Wei (Journal of Water Process Engineering, 2026)

Preparation of Ag/CuV2O6 nanowires and investigation of the delayed antibacterial effect of fluorescent materials on photocatalysts - Xu Li; Yifang Zhang; Qiao Xia; Jiye Fan; Huaxiang Lin; Rusheng Yuan; Jinlin Long (Journal of Environmental Chemical Engineering, 2026)

Mechanistic insights into improved foaming and microbial safety of liquid egg white: The role of microwave, ultrasound, and pectin during cold storage - Sadaqat Ali; Haobo Jin; Yi Sun; Yuanyuan Zhang; Xiang Fan; Haotian Xu; Waqar Nisar; Guofeng Jin; Long Sheng (Food Research International, 2026)

Smartphone-assisted fluorescence sensor based on iron-doped carbon dots for rapid detection of tert-butyl hydroquinone in edible oils - Huihui Yang; Qinghua Liu; Yuanyuan Liu; Qian Su; Yiwei Dong; Minmin Li; Bei Fan; Fengzhong Wang; Long Li (Food Chemistry, 2026)

A pH-responsive bilayer film based on PHBV/ZnO and polyvinyl alcohol/carboxymethyl konjac glucomannan/alizarin was developed for monitoring and maintaining pork freshness - Qiu-Yu Peng; Meng Wang; Song Chen; Long-Hua Zou; Yun-Cheng Li; Fan-Bing Meng (Food Chemistry, 2026)

Flow velocity and turbulent kinetic energy effects on Crassostrea ariakensis larval settlement: Lab and CFD insights - Nan-nan Li; Rui-liang Fan; Long-ling Ouyang; Yuan-ge Chen; Jia-feng Fang; Wei Jiang; Nian Wei; Wei-min Quan (Estuarine, Coastal and Shelf Science, 2026)

Molecular engineering of a D-A-D-type fluorescent probe for detecting viscosity in environmental and living systems - Jing Shu; Hao-Long Sun; Xu-Bo Fan; Si-Hong Zhou; Gui-Chuan Huang; Ming-Qi Wang (Analytica Chimica Acta, 2026)

Aquaculture-relevant florfenicol exposure causes hepatopancreatic bioaccumulation and metabolic-immune toxicity in the mud crab Scylla paramamosain - Min-Ze Liao; Chang-Hong Cheng; Hong-Ling Ma; Guang-Xin Liu; Si-Gang Fan; Yi-Qin Deng; Juan Feng; Sheng-Kang Li; Zhi-Long Chen; Xin-Jian Liu; Zhi-Xun Guo (Environmental Pollution, 2026)

Construction of a porous-ionic-polymer encapsulated Rh-TPPTS catalyst for regioselective hydroformylation - Sen Feng; Cunyao Li; Guifa Long; Guangjun Ji; Xiaofeng Ma; Benhan Fan; Hong Wei; Xinyuan Liu; Yang Zhao; Miao Jiang; Li Yan; Yunjie Ding (Chemical Engineering Journal, 2026)

Chlorination-based resource utilization of chromium-bearing metallurgical solid wastes: Ferrochrome-slag evidence, mechanistic analogues, product recovery, and residue safety - Ren-yun Zhang; Sheng-Zhe Jia; Yan Liu; Zhi-yu Fan; Xiao-Qi Liu; Bo Wang; Long Wang; Kun Wang; Ting-an Zhang (Process Safety and Environmental Protection, 2026)

Sodium alginate–eggshell powder synergy for stabilizing egg white foams in sugar-free chiffon cakes: Interfacial rheology, multiscale structure, and performance - Yi Sun; Haobo Jin; Xiang Fan; Yuanyuan Zhang; Runyue Wang; Guofeng Jin; Long Sheng (Food Hydrocolloids, 2026)

Effect of arsenic-contaminated irrigation water exposeure combined with conventional and biodegradable microplastics on arsenic fractionation in the paddy soil - Haotian Yu; Fan Wu; Feng Peng; Keyu Long; Yihui Wei; Teng Ma (Environmental Pollution, 2026)

Adaptable cooling coil performance under broad load diversity: enabling low-lift chiller operation and resilient performance under climate and pandemic stresses - Shirun Ding; Toby Cheung; Kwan On Tai; Fan Yang; Yizhuo Zhang; Long Zheng; Xiaosong Su; Prashant Anand; Vincent Low; Praveen Hassan Chandrashekar; David Kok Wai Cheong; Chandra Sekhar; et al. (Energy and Buildings, 2026)

Dopamine-induced interlayer bridging for enhanced through-plane thermal conductive performance of expanded graphite-based thermal interface materials - Yuyuan Fan; Long Gao; Jinxing Liu; Yajuan Zhong; Sufang Yang; Xueyao Feng; Hongtao Yu; Junfen Li; Xiaodong Tian; Lei Zheng; Xing Guo; Xi Yan; et al. (Chemical Engineering Journal, 2026)

Titanium isotope fractionation in hydrous and oxidized large igneous provinces - Sheng-Zhu Zhu; Xiao-Long Huang; Peng-Li He; Fan Yang; Jin-Long Ma; Yang Yu; Xin-Yue He; Le Zhang; Gang-Jian Wei (Chemical Geology, 2026)

Full solid waste phosphogypsum-based lightweight aggregate via cold-bonded technology: from granulation kinetics to chemical consolidation - Xiaodong Wang; Guangcheng Long; Yutong Zhang; Junfeng Wen; Fan Wang (Sustainable Chemistry and Pharmacy, 2026)

Green and efficient maize varieties synergize global yield and nitrogen sustainability - Xun Wei; Yulong Yin; Xueqin Zhu; Ziwen Li; Zhenying Dong; Yan Long; Yanbo Wang; Jiuran Zhao; Changling Huang; Xingming Fan; Huabang Chen; Pervez H. Zaidi; et al. (Science Bulletin, 2026)

Maternal PAN2 selectively maintains mRNA Poly(A) tail homeostasis to regulate RNA degradation during oocyte-to-early embryo transition in mice - Xuan Wu; Hua Zhang; Yu-Ke Wu; Zhuo-Yue Niu; Jing-Wen Liu; Lu Chen; Jia-Jia Cao; Yu-Lin Chen; Shu-Yan Ji; Fa-Long Lu; Heng-Yu Fan (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Green synthesis of a histidine-copper biomimetic enzyme for sustainable degradation of sulfamethoxazole in aquaculture wastewater - Yini Zhao; Long Cheng; Tao Yu; Long Gu; Xiangyi Zhang; Hangfei Gao; Zhicen Liu; Ze Fan; Ting Yan; Dongli Qin; Xinyue Zhao; Haijiao Xie; et al. (Journal of Environmental Chemical Engineering, 2026)

Nano-assembly of dioscin via zein–Angelica sinensis polysaccharide composite nanocarriers: structure, stability, bioaccessibility and bioactivity - Tian-Le Mao; Yue Wu; Zhi-Xin Xu; Fan Yang; Jing Li; Xin Guo; Qian-Lan Wu; Ya-Fang Shang; Kiran Thakur; Yi-Long Ma; Zhao-Jun Wei (Food Chemistry, 2026)

A multi-level GNN-XGBoost fusion model for full-range impact response prediction of flexure-critical RC members - Lei Long; Wei Fan; Shilong Yang; Zhengwu Zhong; Ziming Zhou (Engineering Structures, 2026)

Climatic-hydrological-geothermal coupled mechanism drives lake evolution and Li-B enrichment from mega-lakes to salt lakes on the Tibetan Plateau - Jilei Yang; Qishun Fan; Qingkuan Li; Chuanyong Ye; Hao Long; Tianyuan Chen (Earth-Science Reviews, 2026)

Gallium Enrichment in Skarn Iron Deposits, Eastern China: Insights from the Hydrothermal Magnetite - Xian Liang; Fangyue Wang; Long Zhang; Taofa Zhou; Yu Fan; Juquan Zhang; Junwu Zhang (Journal of Earth Science, 2026)

A genetic clash of sister groups: first-ever intergeneric and interspecific mitogenome comparisons between two close gall midge genera (Cecidomyiidae: Cecidomyiinae: Cecidomyiini): the floral and veggie-versatile Contarinia and the mango-mad Procontarinia, with phylogenetic applications - Xiu-Fang Dong; Yi-Fan Zhang; Xu-Yuan Gao; Ning-Bo Ma; Yu Ji; Yan-Fei Li; Yi-Ran Mu; Zheng-Hao Yue; De-Wei Wei; Yong-Hao Yu; Hai-Li Qiao; Wen-Jun Bu; et al. (Arthropod-Plant Interactions, 2026)

Effects of Dietary Macleaya cordata Extract on Growth Performance, Antioxidant Capacity, Immunity, and Stress Resistance in Juvenile Red Claw Crayfish (Cherax quadricarinatus) - Fan-Le Jia; Yao-Peng Lu; Ze-Long Zhang; Xiu-Xia Zhang; Pei-Hua Zheng; Jun-Tao Li; Ying-Hui Liang; Dan Mu; Jian-An Xian (Fishes, 2026)
High-density, intensive aquaculture has led to the deterioration of the aquatic environment, which compromises the survival, immune function and disease resistance of aquatic animals. This study investigated the effects of dietary supplementation with different levels of Macleaya cordata extract (MCE) on growth performance, muscle composition, antioxidant capacity, immune function, and stress resistance in red claw crayfish (Cherax quadricarinatus). Juvenile crayfish with an initial body weight of 0.22 ± 0.02 g were fed diets supplemented with 0 (Diet 1, Control), 0.01 (Diet 2), 0.02 (Diet 3), 0.04 (Diet 4), 0.08 (Diet 5), and 0.15 (Diet 6) g/kg MCE for eight weeks. Results showed that dietary MCE supplementation had no significant effect on the growth performance or muscle composition of crayfish. Conversely, supplementation with 0.02–0.04 g/kg MCE significantly increased the activities of superoxide dismutase (SOD), glutathione peroxidase (GPx), phenoloxidase (PO), and the total antioxidant capacity (T-AOC) in the hepatopancreas and plasma, while significantly reducing malondialdehyde (MDA) levels. Specifically, supplementation with 0.04 g/kg MCE significantly upregulated the hepatopancreatic mRNA expression levels of SOD, hemocyanin, GPx, and selenium-dependent glutathione peroxidase (Se-GPx). Furthermore, the challenge test demonstrated that supplementation with 0.04 g/kg MCE significantly improved crayfish survival under microcystin-LR (MC-LR) stress. Overall, supplementation with 0.04 g/kg MCE significantly improved the antioxidant capacity, immunity, and stress resistance of crayfish, suggesting its potential as an environmentally friendly immunostimulatory feed additive to protect against MC-LR stress in crayfish.

The Effect of Humic Acid From Different Raw Materials on Soil Physical and Chemical Properties and Tomato Seedling Growth - Lanjing Long; Liqin Zhao; Xiangjun Chen; Zhicheng Liu; Xue Chen; Bowen Fan; Fengjun Yang (Journal of Soil Science and Plant Nutrition, 2026)

Compatibility of three adjuvants with Cordyceps fumosorosea and their synergistic effects on controlling the diamondback moth, Plutella xylostella - Mei-Qiong Xie; Long-Jiang Wang; Yong-Qiang Han; Jin-Cui Chen; Li-Ying Cao; Shi-Chuan Luo; Fan-Fan Jiao; Shu-Jun Wei (Crop Protection, 2026)

The microRNA-transcription factor-mRNA regulatory pathways involved in protein homeostasis and amino acid and lipid metabolism in the pearl gentian grouper under acute high-temperature stress - Qiu-Ting Yang; Ren-Xie Wu; Yan-Shan Liang; Ben-Ben Miao; Su-Fang Niu; Feng-Ling Lei; Fan-Li Long; Zhen-Bang Liang (Aquaculture, 2026)

Climate warming and sulfide exposure jointly disrupt intestinal microbiota and barrier homeostasis in the freshwater crab Eriocheir sinensis - Yi-fu Xing; Jian Tian; Xuan-yi Zhu; Yi-fan Feng; Qi-bin Zhu; Long-long Fu; Jia-xin Yang (Aquaculture, 2026)

Experimental and numerical simulation study on failure mode transformation in deep high sidewall cavern - Fan Li; Qiangyong Zhang; Kang Duan; Gongfeng Xin; Guanxu Long (Tunnelling and Underground Space Technology, 2026)

Molecular mechanisms underlying the maintenance of protein homeostasis in pearl gentian grouper under acute high-temperature stress - Qiu-Ting Yang; Ren-Xie Wu; Yan-Shan Liang; Ben-Ben Miao; Su-Fang Niu; Feng-Ling Lei; Fan-Li Long; Zhen-Bang Liang; Yu-Xin Shen; Yu Fu (Journal of Thermal Biology, 2026)

Tuning the thermal reactivity of low-rank coal: The structural role of phenolic hydroxyl groups from molecular aggregation to pore collapse - Hao Xu; Jin-Xi Wu; Yu-Hong Kang; Xing Fan; Ya-Ya Ma; Guang-Hui Liu; Ran-Ran Hou; Zhong-Qiu Liu; Wen-Long Mo; Yao Lu (Fuel, 2026)

Composition characteristics of the distillation waste residue from coal gasification crude phenol and pyrolysis product distribution of the corresponding residue - Jing Zhou; Bao-Kun Shi; Qing-He Ma; Ya-Ya Ma; Jie Yuan; Wen-Long Mo; Feng-Jun Ding; Bing Hu; Xing Fan; Xian-Yong Wei; Hai-Bao Huang (Fuel, 2026)

HBr modified activated carbon enhance NO removal from flue gas by Co(Ⅱ)DETA absorption–regeneration - Peiyun Chen; Xiangli Long; Tingyu Fan (Fuel, 2026)

Migration and transformation pathways of Alkali/Alkaline earth metals and chlorine during co-gasification of biochar and Coal: An experimental and thermodynamic analysis - Qianqian Guo; Hongtao Liu; Yanjun Hu; Lu Ding; Long Jiao; Shuai Liu; Xu Wang; Lingqin Zhao; Fan Yu (Fuel, 2026)

Structural analysis of protein and identification of key protein during the evolution of whole egg liquid foam - Yuanyuan Zhang; Xiang Fan; Haobo Jin; Yi Sun; Yanli Wang; Erjiao Li; Sadaqat Ali; Yanbin Song; Yunxin Sun; Long Sheng (Food Hydrocolloids, 2026)

Trace iron-induced electron delocalization metallization on the BN surface for hyper integrated C-band wideband absorber - Hui Gao; Chunyan Ding; Junyu Shen; Guohao Wu; Mingyang Fan; Zhuoyang Li; Long Xia; Guangwu Wen; Feng Xu; Xiaoxiao Huang (Chemical Engineering Journal, 2026)

Directional molecular design of quaternary ammonium deep eutectic solvents: Enabling low-temperature regeneration for CO2 capture - Chao Liu; Boyi Zhang; Shuning Li; Qinghai Long; Xuanang Fu; Huajie Qiu; Huaqiang Fan; Zuoming Zhou; Bihong Lv; Guohua Jing (Chemical Engineering Journal, 2026)

Phytic acid–engineered TiO2/cellulose composite hydrogels featuring multidentate phosphate sites for efficient Cu(II)/La(III) adsorption - Shiqi Han; Yan Long; Xiangbo Fan; Fanfan Zhang; Daoguang Teng; Guixia Fan (Carbohydrate Polymers, 2026)

Flexible photovoltaic arrays alter surface microclimate and soil environment in a karst rocky desertification region, Southwest China - Zhen Han; Nuoran Long; Xinling Fan; Bin Zhang; Peng Ran; Ruibo Zeng; Lang Peng; Ruyi Zi; Tianxu Mao; Dongdong Zhang; Longshan Zhao (Agricultural and Forest Meteorology, 2026)

Microbe–Metabolite Interactions in Cave Soils Synergistically Regulate the Environmental Persistence of Pseudogymnoascus destructans - Denghui Wang; Fan Wang; Shaopeng Sun; Long Huang; Keping Sun; Zhongle Li; Jiang Feng (Environmental Microbiology, 2026)
Pseudogymnoascus destructans (Pd), the causative agent of bat white‐nose syndrome, persists in cave soils and acts as a chronic source of infection, yet the environmental processes governing this reservoir remain unclear. We performed seasonal sampling of bat cave soils in Northeast China and combined metagenomic, untargeted metabolomic and physicochemical analyses to identify drivers of Pd loads. Pd abundance tracked strong seasonal gradients in temperature, soil water content, electrical conductivity and nitrogen availability. The microbial community structure exhibited pronounced seasonal variation, primarily associated with pH, and was governed predominantly by stochastic ecological processes. Nitrogen‐cycling genes showed a switch from nitrogen fixation and nitrification in summer to denitrification and nitrate reduction in winter. Antibiotic resistance genes and mobile genetic elements covaried with core bacterial taxa, while antifungal metabolites such as tetracycline, glycitin and chrysin were positively associated with putatively antagonistic genera (e.g., Rhodanobacter , Pseudomonas , Streptomyces , and Bacillus ), indicating a microbe–metabolite defence network. Structural equation modelling revealed a temperature‐driven cascade linking nutrient cycling, microbial communities, metabolite profiles and Pd loads. Our results show that seasonal dynamics of Pd in cave soils emerge from interactions between climate‐regulated soil processes and microbe–metabolite feedbacks, with implications for environmental control of pathogenic fungi.

Isolation, identification, and disease-protective potential of Pseudomonas monsensis DBFF02 against Saprolegnia infection in grass carp - Guofan Zhang; Kunyan Li; Yuyuan Peng; Simei He; Chen Li; Rong Fan; Jiajie Xie; Linger Qian; Xinran Long; Jiayi Wang; Jiatao Yang; Yanmin He; et al. (Aquaculture, 2026)

Pore engineering and charge attenuation for covalent organic framework membranes: A new approach to high-performance molecular–ion separation - Qiao Liu; Nong Xu; Kaiming Li; Qing Wang; Long Fan; Yinhua Wan; Xiang Hu; Zhifeng Huang (Water Research, 2026)

Antifungal activity and action mechanisms of 2, 4-Di-tert-butylphenol from Bacillus amyloliquefaciens Z-7 volatile organic compounds against Verticillium dahliae - Hong Tan; Jie Zeng; Jinyi Wu; Chunsheng Wang; Lihua Zhang; Anlong Hu; Zhibo Zhao; Youhua Long; Rong Fan; Xiaoping Hu; Rongyu Li (Pesticide Biochemistry and Physiology, 2026)

Construction of SnO2/g‑C3N4/TiO2 ternary Type-II heterojunctions for boosted photocatalytic hydrogen evolution - Fenhong Song; Ruibo Zhang; Qi Qi; Long Ma; Gang Wang; Wenguang Wang; Jing Fan (Journal of Environmental Chemical Engineering, 2026)

Chloride-enhanced degradation of diethyl phthalate in nano- and micro-scale zero valent iron-activated peroxydisulfate system: transformation and regulation of Fe(IV) and free radicals - Senlin Chen; Jie Ji; Fan Zhang; Bo Wang; Long Liu; Jiaolong Qin; Xiaojun Hu (Journal of Environmental Chemical Engineering, 2026)

Sustainable treatment and valorization of MSWIFA for construction materials: Technologies, mechanisms, and challenges - Zhiyuan Han; Guangcheng Long; Fan Wang; Kunlin Ma; Zhuo Tang; Youjun Xie; Ming Chen; Ding Jiang; Wenxiang Xie; Yan Liu (Journal of Environmental Chemical Engineering, 2026)

Nanotube-oxygen vacancy synergy for electron-rich Ru nanoparticles towards efficient H2 evolution - Xingyu Wan; Song Wu; Shaoxian Song; Guangyin Fan; Yan Long (Fuel, 2026)

Melatonin safeguards embryo and blastoid development against oxybenzone toxicity via a mitochondrial-linked NAD+ and glucose metabolic axis - Yuying Xiong; Haiying Zhu; Han Xie; Yunqi Wu; Ruojin Shi; Xueling Zhang; Lin Zhu; Yiwen Wang; Ke Zhong; Lei Li; Yaming Meng; Minyu Xie; et al. (Environmental Pollution, 2026)

Mechanistic insight into the “intermediate effect”: Competitive adsorption and surface coverage model in controlling hydrate formation in a closed-cell foam–SDS system - Yi-Feng Wang; Zhen-Guo Qi; Zhen Pan; Li-Yan Shang; Zhi-Ming Liu; Jie Liu; Zhuo-Fan Ma; Long-Qi Meng (Chemical Engineering Journal, 2026)

A ultralong-life and high-capacity Mg/Na hybrid-ion battery using four-leaf clover-shaped CuSe2/(Cu, Co)Se2 cathode pairing with triglyme electrolyte - Ting Zhou; Tianli Han; Fengming Ma; Cheng Wang; Yunmiao Fan; Xuehui Wang; Haojun Xu; Jiawei Long; Jinjin Li; Huigang Zhang; Jinyun Liu (Chemical Engineering Journal, 2026)

Deformation characteristics and mechanism of reactivation for stepwise-deepening landslides: a case study of the Hongzhai Landslide in Guizhou Province, China - Jie Dang; Lanxin Dai; Long Yan; Jincheng Guo; Di Wu; Xuanmei Fan (Landslides, 2026)

A Double-Thiadiazole-Derived Fluorescent Probe for the Cyclooxygenase-2 Detection in Colorectal Tumor-Inflammation Interaction - Long Qin; Xionggao Han; Qingqing Fan; Liuyang Jin; Weichun Huang; YiLi Jin; Chaoyue Wang (Journal of Fluorescence, 2026)

Sequence Stratigraphy, Sedimentary Evolution and Controlling Factors of the Shan-1 Member in Permian Shanxi Formation, Qingyang Gas Field, Ordos Basin, Central China - Qian-qian Fan; Shi-qiang Xia; Hui Xia; Wei Wang; Long Wang; Yan Wang; Shi-cheng Wang; Shuai-shuai Feng; Wei Zhang; Ya Li; Ping Liu; Qian-yun Dong (Applied Geophysics, 2026)

The formation mechanism and regulation of the unique flavor in fried dough products - Fangshu Fan; Guifang Huang; David Julian McClements; Huichang Zhong; Liyi Chen; Qing Hong; Zhenmin Liu; Zhengyu Jin; Long Chen (Critical Reviews in Food Science and Nutrition, 2026)

The estimation of tree-level key structural parameters based on ULS and BLS point clouds by evaluating prediction accuracy from tree stem analysis - Yu Tao; Xin Shen; Fujin Fan; Daiquan Ye; Long Zhang; Lin Cao (Computers and Electronics in Agriculture, 2026)

DICP1-A precisely degrades STING-A but not STING-B to suppress IFN expression through the autophagic pathway in gibel carp - Yue Wu; Shun Li; Fan-Xiang Gao; Zhi Li; Rui-Hai Gan; Can Zhang; Xiao-Li Yang; Zhuo-Cong Li; Chu-Jing Zhou; Yang-Yang Wang; Na Xu; Xue-Bing Wang; et al. (Aquaculture, 2026)

ZmSWEET6A/6B are required for maize male fertility via balancing sugar and lipid metabolism during pollen and anther development - Shuangshuang Liu; Yilin Jiang; Canfang Niu; Fan Zhang; Lina Zhao; Quancan Hou; Ziwen Li; Yingwei Qu; Bin Ma; Qingping Jiang; Yan Long; Xueli An; et al. (Science Bulletin, 2026)

Characterization and stochastic reconstruction of time-varying corrosion morphology of steel in marine atmospheric environments - Tiancheng Chen; Shenggang Fan; Tiangui Xu; Houmin Long; Yang Yan (Ocean Engineering, 2026)

Hydrothermal Nb mineralization during fenitization in the carbonatite system: Evidence from the Bayan Obo REE-Nb deposit, China - Qi Li; Jian Zhao; Xiaochun Li; Long Huang; Hongrui Fan; Yonggang Zhao; Xianhua Li; Mingguo Zhai (Journal of Asian Earth Sciences, 2026)

Structural contributors to digestibility: How N-glycosylation modulates the proteolytic fate of human and bovine milk lactoferrin during in-vitro infant digestion - Yu Dong; Lina Zhang; Youpeng Fan; Mengfei Long; Kasper Hettinga; Peng Zhou (Food Bioscience, 2026)

Oral delivery of colon targeted zein-xanthan gum nanoparticles loaded with giant salamander Maillard hydrolyzed peptide: improving ulcerative colitis by regulating the production of antioxidant peptides in digestive products - Jing-Jing Fu; Fan-Yu He; Yong-Jie Long; Wen-Qiang Cai; Jun-Xin Wu; Yue-Wen Chen (Food Bioscience, 2026)

Preparation and application of ergothioneine liposomes and their inhibitory effect on polyphenol oxidase from Lanzhou lily - Wenguang Fan; Shuyuan He; Haiwei Ren; Lichao Pan; Long Liu; Yaqin Tian (Food Bioscience, 2026)

The introduction of impurity energy level into electrode materials to improve the performance of photo-sensitive supercapacitors - Haifeng Tan; Wanjiang Long; Weilong Li; Sushuang Feng; Chenrui Fan; Yijie Gao; Xue Yang; Zhaoyu Ren (Chemical Engineering Journal, 2026)

Ionic microenvironment engineering integrated pH-buffering toward durable and dendrite-free metallic Zn anodes - Yuhan CHEN; Qianqian WANG; Fucong LYU; Y.U. Hanyang; Yunchen LONG; Jianan YIN; L.I. Gan; Bin QIN; Xiaoqiang CAI; Hui LIU; Jun FAN; Jian Lu (Chemical Engineering Journal, 2026)

Propyl propionate enabling stable operation of 4.55 V LiCoO2/graphite pouch cells at various temperatures via solvation and interface modulation - Shiran Li; Yu Zhang; Xiao-Zhong Fan; Xiaomeng Wang; Gupei Ding; Weiguo Li; Xu-Feng Zang; Miaomiao Han; Long Kong (Chemical Engineering Journal, 2026)

Manipulating non-radical pathway preference in PMS-mediated phenolic degradation: Substituent-dependent catalyst-pollutant interfacial interaction over single-atom Fe-N-C - Fan Huang; Xianhu Long; Ting Li; Xuexia Guo; Lingling Hu; Huinan Zhao; Shuanghong Tian; Minhua Su; Chun He (Chemical Engineering Journal, 2026)

Downregulation of UQCRC1 Expression Leads to Cognitive Decline by Disrupting the Cilia in the Dentate Gyrus - Jing Zhang; Tianyao Liu; Zonghong Long; Zuoxi Wu; Jing Luo; Fuhai Bai; Lianyu Zhou; Hong Gong; Meifeng Gong; Hong Li; Xiaotang Fan (Neuroscience Bulletin, 2026)

Observation of Concurrent Latitudinal and Longitudinal Fractionations of α- and β-HCH in Chinese Rural Surface Soil: Implications for Global Lifecycle - Shuai Hao; Yi-Fan Li; Wan-Li Ma; Li-Yan Liu; Zi-Feng Zhang; Wen-Long Li; Ning-Zheng Zhu; Pu-Fei Yang; Hong-Liang Jia; Min-Gang Cai; Roland Kallenborn; Derek CG Muir (Archives of Environmental Contamination and Toxicology, 2026)

Revisiting the Peripheral Nerve Injury and Regeneration - Zhen-Gang Liu; Yun-Long Zou; Min-Xin Zhang; Fan Yang; Peng-Fu Li; Bo-Yin Zhang (NeuroMolecular Medicine, 2026)

Contract coordination of coal supply chain considering reciprocity altruism under water cap-and-trading regulations - Peiyao Wang; Pu Dong; Long Zhang; Yan Li; Peishan Fan; Xiaofan Li; Chaowei Wang (Environment, Development and Sustainability, 2026)

Four new flavonoids from Sophora flavescens and their antibacterial activities - Yun Gao; Xin-Min Li; Fan-Fan Cao; Guo-Qing Long; Jing-Ming Jia; An-Hua Wang (Natural Product Research, 2026)

Effects of suspended sediment on the survival and settlement of Crassostrea ariakensis and Crassostrea sikamea larvae: Results from lab experiments - Nan-nan Li; Yu Han; Yuan-ge Chen; Wei-liang Dong; Long-ling Ouyang; Rui-liang Fan; Wei Jiang; Jia-feng Fang; Nian Wei; Jin-ming Wang; Wei-min Quan; Jian Zeng (Regional Studies in Marine Science, 2026)

Deposition characterization and predictive modeling of phosphorus and heavy metals during sewage sludge incineration - Qianqian Guo; Taojie Duan; Yanjun Hu; Long Jiao; Lingqin Zhao; Fan Yu; Xu Wang; Lei Che; Frederik Ronsse (Journal of Environmental Management, 2026)

Robust multifunctional rGO/ZIF-8@PPS fibrous membrane for effective oil-water separation in harsh environments - Yang Liu; Tingting Fan; Changhao Liu; Yun-Ze Long (Journal of Environmental Chemical Engineering, 2026)

Endogenous copper-based biochar boosted peroxymonosulfate activation for highly efficient inactivation of Pepper mild mottle virus in water - Long Wang; Yujie Wang; Jun Ma; Yuhan Fan; Ming Chen (Journal of Environmental Sciences, 2026)

Thallium isotope insights into Mn Oxides as precursor to Ediacaran Mn Carbonate Ore - Xuwen Luo; Haifeng Fan; Jean Clemente; Chao Li; Hongjie Zhang; Long Chen; Yaowen Wu; Shaohong Fu; Jianfeng Gao; Hanjie Wen; Sune G. Nielsen (Geochimica et Cosmochimica Acta, 2026)

Sea buckthorn for future foods: bioactive mechanisms, synthetic biology, and precision delivery systems - Nan Li; Peidong Fan; Lulu Wang; Luole Feng; Hui Long; Wenjuan Yang; Jing Wang; Yanni Zhao; Huan Liu; Yuxi Guo; Pin Gong (Food Research International, 2026)

Effects of mechanized harvesting on sesame seed storage: Quality, volatile compounds, and metabolites - Yun-Long Chang; Yu-Long Niu; Jia-Rui Li; Zi-Fan Zhang; Hua-Min Liu; Xue-De Wang; Xin-Yu Wen; Hong-Yu Zhang; Hong-Wei Liu; Shao-Ze Zhang (Food Chemistry, 2026)

Regulation mechanism of fatty acid chain length and saturation on lipid adsorption behavior and protein conformation during whole egg liquid foam evolution - Yuanyuan Zhang; Yanli Wang; Haobo Jin; Yi Sun; Sadaqat Ali; Erjiao Li; Xiang Fan; Yanbin Song; Yunxin Sun; Guofeng Jin; Long Sheng (Food Hydrocolloids, 2026)

Synergistic regulation of pore structure and surface charge in COF-based membranes for monovalent ion sieving - Long Li; Qian Cao; Renzhong Wang; Ying Li; Yang Zhao; Yiqun Fan; Zhaohua Li; Feng Shao (Desalination, 2026)

Horizontal evolution characteristics of near-inertial sea surface currents induced by the tropical cyclones in the Guangdong-Hong Kong-Macao Greater Bay area - Lei Ren; Hexu Wang; Beinuo Zhou; Xiaofan Lou; Zhenglin Li; Long Bai; Fan Yang; Zhenchang Zhu; Fearghal O'Donncha; Jun Wei; Michael Hartnet (Deep Sea Research Part I: Oceanographic Research Papers, 2026)

Host size and parasite density impact on the efficacy and reproductive output of Pyemotes zhonghuajia, a biological control agent of potato tuber moth - Chenming Xiao; Xiong Zhao He; Xuelin Li; Di Fan; Long Zhang; Chengxu Wu; Maofa Yang; Jifeng Hu; Guy Smagghe; Jianfeng Liu; Fangling Xu (Experimental and Applied Acarology, 2026)

Description and Comparative Genomic Analysis of Salipiger Bruguierae sp. nov., a Novel Member of the Family Roseobacteraceae Isolated from Mangrove Sediments - Qiangcai He; Shaoshuai Tang; Zhen Gan; Dakun Chen; Huimin Fan; Yishan Lu; Meng Long (Current Microbiology, 2026)

The climate threshold for locally absent rings in Siberian larch exhibits significant variation with altitude - Xiao-xia Gou; Tong-wen Zhang; Hua-ming Shang; Shu-long Yu; Dong Guo; Rui-bo Zhang; Li Qin; Sheng-xia Jiang; Yu-ting Fan; Ke-xiang Liu; He-li Zhang; Kai-long Guo; et al. (Agricultural and Forest Meteorology, 2026)

A yaw angle attitude model method for HY2C and HY2D satellites based on spaceborne GNSS and DORIS data - Chongchong Zhou; Zhao Guo; Fengcheng Guo; Lelin Xing; Long Wang; Junao Wang; Fan Gao (Advances in Space Research, 2026)

Dissecting the aberrant vasculature of glioblastoma: mechanisms and therapeutic targets - Yinan Li; Yinfei Du; Fan Guan; Xuetong Li; Shu Cui; Wei Gao; Xinmiao Long; Minghua Wu (Cancer and Metastasis Reviews, 2026)

Mechanism of Cu migration and transformation during pyrolysis of Copper-Bearing sludge regulated by Cellulose/Kaolinite - Yanjun Hu; Xuan Yu; Lingqin Zhao; Qianqian Guo; Long Jiao; Fan Yu; Aijia Zhang (Waste Management, 2026)

Macro-micro changes of clayey loess subjected to wetting-drying cycles and the effect on mechanical behavior deterioration - Ya-ni Wei; Wen Fan; Hanghang Chen; Bo Yu; Long-sheng Deng; Jia-yu Liang (Soil and Tillage Research, 2026)

Maternal mRNA clearance is associated with the prevention of precocious transcription and genome instability in mouse early embryos - Qian-Qian Sha; Yun-Wen Wu; Meng-Yan Jia; Yu Jiang; Xing-Xing Dai; Long-Wen Zhao; Heng-Yu Fan (Science Bulletin, 2026)

Synergistic defense in cotton: Lignin-mediated barriers and JA/ET signaling pathways against Verticillium wilt - Zhixin Liu; Yinpeng Zhang; Yaping Zhou; Baozhen Wang; Jiani Long; Mengyu Liao; Xiaoli Fan; Wenxuan Kang; Beibei Liu; Xuwu Sun (Plant Science, 2026)

Burkholderia seminalis suppresses Fusarium wilt infection in banana by modulating cell wall integrity - Shazma Gulzar; Yaxin Xu; Fan Fiona Fei; Zan Yi; Chunxia Huang; Rahat Sharif; Zhihui Long; Yisha Lu; Huiling Zhan; Chunxiang Xu (Pesticide Biochemistry and Physiology, 2026)

Mechanistic insights into magnetite-enhanced Indoleacetic acid production by a mixed culture - Yun-Xin Ge; Wei Gao; Zi-Han Fan; Yun Niu; Long-Tao Fang; Xi-Zhen Zou; Wei Zhang (Journal of Water Process Engineering, 2026)

Integrated machine learning and density functional theory to design C₃N₅ piezo-catalysts toward precise control of selective reactive oxygen species and efficient water purification - Ting Li; Xianhu Long; Wei Liu; Fan Huang; Huinan Zhao; Tao Zhong; Jingyun Fang; Chun He (Journal of Hazardous Materials, 2026)

Effective separation of organic species from a shale oil sludge - He-Qi Liu; Xian-Yong Wei; Zhi-Hao Ma; Jing Chen; Xiao-Yan He; Zhi-Min Zong; Xing Fan; Yu-Hong Kang; Fang-Jing Liu; Hai-Xu Zou; Guang-Hui Liu; Yierxiati Dilixiati; et al. (Journal of Environmental Management, 2026)

Wolframite and cassiterite geochemistry deciphers W–Sn ore formation: A case study from the Zuoba quartz-vein tungsten deposit, South China - Kai-Han Zhang; Jun-Yi Pan; Pei Ni; Gen-Wen He; Lin-Lin Peng; Ming-Sen Fan; Yuan-Long Zhang; Wen-Sheng Li (Journal of Asian Earth Sciences, 2026)

WHU-STree: A multi-modal benchmark dataset for street tree inventory - Ruifei Ding; Zhe Chen; Wen Fan; Chen Long; Huijuan Xiao; Yelu Zeng; Zhen Dong; Bisheng Yang (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Ba isotope unmasks recycling processes of fluid mobile elements in subduction zones - Yang Yu; Xiao-Long Huang; Betchaida D. Payot; Hai-Quan Liu; Ying-De Jiang; Yu Wang; Carla B. Dimalanta; Xin-Feng Ou; Gabriel Theophilus V. Valera; Fan Yang; Graciano P. Yumul; Yi-Gang Xu; et al. (Geochimica et Cosmochimica Acta, 2026)

Engineering core–shell nanocatalysts for boosting electrocatalytic water electrolysis - Kun Wang; Wei-Long Xu; Yuebin Lian; Yan Chen; Huike Fan; Hui Xu (Fuel, 2026)

Study on structure regulation of porous carbon prepared from phenol/ammonium components of semi-coking wastewater - Xianjie Wang; Long Yan; Yufei Wang; Shuaige Shi; Jian Li; Xiaoyong Fan (Fuel, 2026)

Selective hydrogenation of nitriles to primary and secondary amines via Ni0/Ni2+ dual sites - Tongtong Fan; Jiaheng Qin; He Wen; Siyu Li; Hong Zhao; Tong Li; Xiao Zhang; Jiantai Ma; Yu Long (Fuel, 2026)

Interfacial reorganization of egg yolk granules by ultrasound-assisted pH-shifting: concentration-dependent lecithin functionality from emulsion stabilizer to competitive displacer - Shuangshuang Li; Yaqin Yang; Yi Sun; Yuanyuan Zhang; Xiang Fan; Mohamed Salama; Guofeng Jin; Long Sheng (Food Chemistry, 2026)

Multispectral characterization, molecular docking, and dynamics simulation of trans-cinnamaldehyde–ovalbumin interactions: implications for gel texture, water retention, and microstructural properties - Yi Sun; Bao Chen; Haobo Jin; Sadaqat Ali; Yuanyuan Zhang; Xiaohui Lv; Xiang Fan; Guofeng Jin; Long Sheng (Food Chemistry, 2026)

Nematode predation mitigates microbial competition to sustain the plant growth-promoting effect of Streptomyces - Ke-Fan Huo; Jing-Nan Zhang; Elly Morriën; Ping Liu; Neil B. McLaughlin; Kai-Hong Bai; Zhen-Long Wang; Shi-Xiu Zhang; Lu-Jun Li (European Journal of Soil Biology, 2026)

Overcoming acidic constraints: A bio-inspired cu-bilirubin nanozyme with superior neutral-pH peroxidase and laccase-like activities for selective sensing and removal of formaldehyde and pyrogallic acid - Ruochen Duan; Xiaohui Hao; Ao Shen; Panqing Zhang; Zeyu Zhang; Xuebing Wang; Long Chen; Qingyang Fan; Jiahao Wang; Yunxu Yang (Chemical Engineering Journal, 2026)

A co-delivery nanoplatform for coordinated STING activation and dual PI3K/COX-2 blockade potentiates Cancer immunotherapy - Zhe Zhang; Ruibai Chang; Jindian Fan; Bingjing Liang; Long Zheng; Rui Fan; Xin Huang; Yitong Wang; Jingyi Lv; Xiaoting Yang; Belal Abdellah; Khaled A.M. Abouzid; et al. (Chemical Engineering Journal, 2026)

Direct seawater electrolysis for Mg(OH)2 extraction over an anti-scaling cathode with NiFeCo hierarchical microstructure arrays - Wei Long Wang; Wei Hao Zhong; Fan Xia; Wen Da Kang; Yu Wei Gu; Yu Chen Zhao; Hong Yi Sheng; Hong Tao Yu (Chemical Engineering Journal, 2026)

Interface passivation with 1,3-propyldiammonium diiodide enables production-line compatible perovskite/silicon tandem solar cells - Dongyong Fan; Longhao Jisi; Wenfeng Zhang; Xin Hu; Fang Wen; Wei Long; Yuchao Hu; Yifeng Zhang; Guoqiang Xing; Liping Su; Haijin Li; Wenhua Zhang; et al. (Chemical Engineering Journal, 2026)

Tailoring metal-support interaction boosted thermal catalytic heterolytic hydrogenation for biomass upgrading - Dongying Yan; Long Cui; Weifeng Fan; Ruihui Gan; Chenxi Bai (Chemical Engineering Journal, 2026)

Deciphering the regulatory role of the pfs gene on biofilm formation in Lactobacillus plantarum R: Insights from transcriptome and metabolome - Xin Fan; Bo Li; Xinao Xu; Binbin Long; Zhiwen Jia; Ran Wang; Junjun Gao; Yang Chen; Mingye Peng; Mengzhou Zhou (Bioresource Technology, 2026)

Semi-rational engineering of a β-farnesene synthase hybrid for enhanced production in Serratia marcescens - Wenqi Zhao; Linbo Gou; Di Liu; Shengfang Wu; Xiuwen Zhou; Tai-Ping Fan; Long Wang; Yujie Cai (Systems Microbiology and Biomanufacturing, 2026)

Establishment of an embryonic cell line of Grapholita molesta (Lepidoptera: Tortricidae) and in vitro replication of Cydia pomonella granulovirus in it - Gui-Ling Zheng; Yu-Fan Yao; Xiao-Yu Zhang; Qian-Long Yu; Jie Li; Yi-Ping Li; Dong Chu; Chang-You Li (In Vitro Cellular & Developmental Biology - Animal, 2026)

Corrigendum to “Mantle evolution of the nascent oceanic basin subsequent to continental breakup constrained by Mo–Sr–Nd–Hf isotopes in MORBs from the northern margin of the South China Sea” [Lithos 512–513(2025) 108151] - Yu-Xin Cai; Xiao-Long Huang; Fan Yang; Yang Yu; Jie Li; Zhen-Min Ge (Lithos, 2026)

Recovering residual carbon from coal gasification slag via flotation for wastewater treatment - Haiyu Wang; Jufen Zhu; Qi Yan; Jiale Wen; Junfei Shang; Xiaoyong Fan; Baoning Li; Fanhui Guo; Qingbo Wei; Lingxing Zan; Yuxuan Liu; Jian Li; et al. (Journal of Water Process Engineering, 2026)

Enhancing norfloxacin adsorption via NF dual-site non-metal functionalized biochar: Performance and mechanism - Fan Yin; Zihui Lin; Hailong Lu; Chunmin Xu; Hui Chen; Long Cheng (Journal of Water Process Engineering, 2026)

Unlocking a new application of coal and biomass co-ethanolysis: high-performance supercapacitor based on N/O self-doped hierarchical porous carbons - Li Li; Yu-Fan Ren; Chang-Wang Shao; Long-Yu Zhang; Guo-Rong Qi; Xing-Shun Cong; Xian-Yong Wei; Zi-Chun Fan; Xiao-Yu Zhang (Fuel, 2026)

Research on the pore structure of bituminous coal on the basis of different degassing temperature and particle size - Lingling Qi; Jiahui Liu; Long Fan; Xiangjun Chen; Zhaofeng Wang; Jun Liu; Xiaoqing Zhou (Fuel, 2026)

Magnetic iron oxide-loaded coal-based activated carbon for Enhanced copper (II) removal: Batch and fluidized bed studies - Wen Fan; Bo Lv; Long Li; Yutong Jiao; Man Wang; Baolin Xing (Fuel, 2026)

Effects of metals on thermal oxidation of jet fuel and mitigation strategies - Bowang Lu; Xiaoyong Fan; Dong Li; Jun Yang; Long Yan; Bo Yang; Guanghui Pang; Jian Li; Bi Chen (Fuel, 2026)

Experimental study on seismic performance of low-yield-point steel tubular links - Jun-Yu Wu; Liang-Dong Zhuang; Ji-Zhi Zhao; Li-Long Fan; Xiao Feizhi (Engineering Structures, 2026)

Tailored plasmonic interfaces on LAS glass-ceramic gratings for high-efficiency electromagnetic wave absorption - Chunyan Ding; Shanshan Fan; Zhengliang Qiu; Zhuoyang Li; Yiteng Zhang; Songsong Wu; Liping Tong; Bo Zhong; Long Xia; Guangwu Wen; Xiaoxiao Huang (Chemical Engineering Journal, 2026)

Metabolic flux balancing and enhanced expression of engineered Paeonia lactiflora pinene synthase for high-yield α-pinene production in Serratia marcescens HBQA7 - Ping Zhang; Linbo Gou; Di Liu; Shengfang Wu; Xiuwen Zhou; Tai-Ping Fan; Long Wang; Yujie Cai (Bioresource Technology, 2026)

FGF2 Enhances MSCs Secretome Therapy for Skin Photoaging by Delaying Senescence via iNAMPT/AMPK Signaling and Facilitating eNAMPT-Mediated Regenerative Crosstalk - Yixin Zhang; Manping Lu; Jieqing Ouyang; Lin Liang; Fan Li; Zhihan Pei; Lihao Chen; Miaoman Ye; Jiajie Tan; Liwei Xiang; Lijing Kong; Long Huang; et al. (Stem Cell Reviews and Reports, 2026)

Precise point positioning with an adaptive geometry-free cycle slip detection threshold under complex ionospheric conditions - Long Tang; Luheng Zhou; Fan Xu; Jiahuan Hu; Xiaohong Zhang (GPS Solutions, 2026)
Global navigation satellite system (GNSS) precise point positioning (PPP) performance experiences significant degradation under complex ionospheric conditions, particularly during geomagnetic storm events. To address this challenge, this study develops an adaptive geometry-free (GF) cycle slip detection threshold model, leveraging GNSS Doppler measurements to reduce the incorrect cycle slip detection, thereby enhancing the accuracy and reliability of GNSS PPP. The proposed threshold model is fitted using Doppler index data extracted from 110 International GNSS Service (IGS) stations on the 11th May 2024 when an extreme geomagnetic storm occurred. 72 IGS stations which are not used in modeling on the same day are employed to validate its performance. The results show that PPP with adaptive GF cycle slip detection threshold can achieve positioning accuracy improvements by 42.4% and 37.2% in horizontal and vertical directions, respectively, compared with traditional strategy. Furthermore, positioning accuracy improvements of 63.1% and 50.1% in horizontal and vertical are obtained with data from another geomagnetic storm event on the 11th October 2024, which further demonstrates the efficiency and uniformity of proposed model. Comparison of positioning accuracy with tight and loose thresholds during the ionospheric quiescence periods also verifies the adaptability of the built model.

Mud crab reovirus infection disrupts the intestinal microbiota and intestinal physiological homeostasis in mud crabs (Scylla paramamosain) - Min-Ze Liao; Chang-Hong Cheng; Hong-Ling Ma; Guang-Xin Liu; Si-Gang Fan; Yi-Qin Deng; Juan Feng; Sheng-Kang Li; Xin-Jian Liu; Zhi-Long Chen; Zhi-Xun Guo (Aquaculture, 2026)

Evaluation method for seismic resilience of underground structures and its verification - Yang Fan; Zhuang Haiyang; Yun Long; Wang Dianpeng; Xu Zigang (Soil Dynamics and Earthquake Engineering, 2026)

Monthly monitoring of urban development and renewal at the block-level in China using Sentinel-2 time series - Haixu He; Jining Yan; Lirong Liu; Xu Long; Runyu Fan; Zhongchang Sun (Remote Sensing of Environment, 2026)

Preharvest melatonin application enhances soft rot resistance in kiwifruit through the jasmonic acid signaling pathway - Junsen Peng; Shufeng Du; Rong Fan; Youhua Long; Guofang Xie; Xiaochun Ding; Xiaoqing Dong (Postharvest Biology and Technology, 2026)

The candidate effector Bd_A04480 contributes to Botryosphaeria dothidea-induced postharvest soft rot in kiwifruit by increasing virulence and suppressing plant immunity - Hong Tan; Jinhuang Song; Juanrong Qin; Shufeng Du; Rui Yang; Xiaoqing Dong; Zhibo Zhao; Youhua Long; Rong Fan (Postharvest Biology and Technology, 2026)

Typhoon-induced cascade effects on hydrological and biogeochemical dynamics in estuary-coast continuum: Insights from multidisciplinary observations and model forecasting in Zhanjiang Bay, China - Huizi Long; Peng Zhang; Jibiao Zhang; Menghan Gao; Binbin Fan; Zhangxi Hu; Zhihao Li; Rong Chen (Journal of Hydrology, 2026)

Curcumin-mediated photodynamic action disturbs TOM70-depedent MIC60 import to damage mitonchondria against breast cancer - Xiang-Yi Zhao; Min Yan; Liang Zheng; Chang-Long Gou; Qi Huang; Liu-Gen Li; Xin-Ran Yu; Jing-Yu Lu; Cui Hu; Si-Han Zhang; Cunqing Kong; Fan Leng; et al. (Journal of Photochemistry and Photobiology B: Biology, 2026)

Enhanced electrokinetic removal of NH4+-N and Mn2+ from electrolytic manganese residue by different organic acid - Weilong He; Na Liang; Dinghao Yang; Maokui Wang; Long Fan; Yong Yang; Facheng Qiu; Changyuan Tao; Renlong Liu; Jiancheng Shu (Journal of Hazardous Materials, 2026)

Evaluation of deconvolution methods and loading parameters in nanoindentation characterization of sodium aluminosilicate hydrate gel in fly ash based geopolymers - Wenrui Xu; Youjun Xie; Fan Wang; Zhiyu Luo; Gang Ma; Yiran Li; Yingjie Li; Guangcheng Long; Zhuo Tang (Journal of Cleaner Production, 2026)

Simultaneous dual-mode detection and removal of acrolein in food samples via a fluorescent PAA-CDs/Sulfhydryl cotton/SA hydrogel composite - Panqing Zhang; Ruochen Duan; Zeyu Zhang; Lingwei Xue; Xuebing Wang; Long Chen; Qingyang Fan; Jiahao Wang; Yunxu Yang (Food Chemistry, 2026)

Perillaldehyde controls citrus green mold by inhibiting the ribosome biogenesis of Penicillium digitatum and improving citrus disease resistance - Shuqi Liu; Yuxin Jiang; Jiancheng Sun; Fan Yang; Yuqing Wang; Yongqing Lu; Weiqiang Lai; Chao-an Long (Food Control, 2026)

Selective control in the oxygen activation involved ROS generation over carbon nitride for long-term aerosol disinfection: Carbonyl location matters - Hanyu Zhang; Long Tan; Guochun Lv; Yaofang Fan; Munir Ahmad; Xiaojing Wang; Kai Wei; Hong Xiao; Hong Peng; Xiaohui Lu; Shihuai Deng; Fei Shen; et al. (Chemical Engineering Journal, 2026)

Electrically insulating BNNS/PVDF@AlN/PVP composites with simultaneously enhanced in-plane and through-plane thermal conductivities - Wei-Hua Han; Yaping Fan; Yu Long; Bin Sun; Yun-Ze Long; Chun-Cheng Hao (Chemical Engineering Journal, 2026)

TFEB-driven autophagy enhancement via a ROS-triggered NIR-II nanoplatform for targeted non-alcoholic fatty liver disease therapy - Fan Wu; Xin Kuang; Jian Xiong; Chaoqiang Li; Jinkang Zheng; Bibo Zhao; Sanlin Deng; Gui-long Wu; Qinglai Yang; Guodong Chen (Chemical Engineering Journal, 2026)

224Ra labeled nanohydroxyapatite for targeted alpha therapy of metastatic lung cancer - Jie Lyu; Long Qiu; Fuyuan Tan; Yuying Yu; Xisheng Fan; Tianzhen Ye; Shuran Lei; Jiali Liao; Yuanyou Yang; Ning Liu; Feize Li (Chemical Engineering Journal, 2026)

Late Pliocene-Quaternary climate-environment evolution on the southeastern Tibetan Plateau and links to hominin dynamics - Yidan Long; Wenxia Han; Boyan Sun; Yifei Fan; Xue Xiao; Tianli Wang; David B. Kemp; Chenyu Shang; Yunping Chi; Xiaomin Fang (CATENA, 2026)

Real-time Monitoring Unveils Three Distinct Neuronal Response Patterns to SAW Ultrasound via L-type Calcium Channels - Yiming Chen; Wenxu Tang; Yifan Wang; Ya Gao; Jiaqi Hu; Yixuan Lu; Long Meng; Hairong Zheng; Yi Feng; Liming Cheng; Wenyong Fan; Qian Cheng; et al. (Neuroscience Bulletin, 2026)

Endothelial Glycocalyx Degradation as a Mediator of Neuroinflammation and Cognitive Impairment in Aged Rats: Protective Role of SS-31 - Min-Hui Kan; Yang Liu; Fan-Qi Meng; Long Fan; Yan Wu; Tian-Long Wang (Molecular Neurobiology, 2026)

QTL analysis of single-segment substitution lines dissected from a rice CSSL-Z668 and fine-mapping of qGL3.4 for grain length - Si-Qian Xiang; Yu-Zhu Tao; Zhao-Peng Yu; Zhuo-Wen Zhao; Han Zhang; Qiao-Long Li; Lu Li; Ao-Ni Xiang; Jing-Hong Xu; Fan Zhang; Xu Yan; Zheng-Lin Yang; et al. (Euphytica, 2026)

Geophysical Characteristics and Prospecting Significance of the Halong’erma Polymetallic Deposit in the East Kunlun Metallogenic Belt - You Zhou; Zhi-Qiang Zhang; Ji-En Dong; Hai-Yue Fu; Fa-Long Qi; Wen-ke Fan; Hao Ren; Xue-lin Huang (Applied Geophysics, 2025)

Optimizing fucoxanthin production in the diatom Phaeodactylum tricornutum using ARTP-evolved mutant consortia and a multifaceted approach in LED-driven photobioreactors - Wen Liu; Jing Liu; Song Zou; Jijian Long; Qin Zhang; Yue He; Hong Chen; Yan Liu; Yawen Fan; Qiang Hu (Algae, 2025)
The diatom Phaeodactylum tricornutum is known for its rapid growth and high fucoxanthin content (1–3% of dry weight), a photosynthetic pigment with considerable pharmaceutical and nutraceutical potential. Despite these advantages, the commercial biotechnological applications of this organism have not yet been realized, primarily due to challenges in scaling up photobioreactor (PBR) systems, as well as issues with the organism’s robustness and production processes. In this study, we present a multifaceted approach to enhance fucoxanthin productivity by combining innovations in PBR design, strain improvement, and LED light recipes. Systematic evaluation of P. tricornutum in 700 mL column PBRs identified optimal light conditions (e.g., 660 nm red light at 50 μmol photons m–2 s−1 with optimized light regimes), which were subsequently scaled up to novel 200 L and 10,000 L PBRs. Meanwhile, atmospheric and room temperature plasma mutagenesis, coupled with an adaptive evolution screening technique, generated superior mutant consortia exhibiting enhanced phenotypic characteristics, including higher fucoxanthin yield and long-term stability of cultivation. Comparative cultivation experiments in the 10,000 L PBR demonstrated the superiority of the mutant consortia, yielding 0.59 g L–1 biomass (an 18% increase) and 7.29 mg L–1 fucoxanthin (a 32.79% increase) compared to the wild type strain. Productivity was significantly improved, with biomass and fucoxanthin production rates reaching 0.12 g L–1 d–1 (a 33.33% increase) and 1.47 mg L–1 d–1 (a 54.74% increase) in the 10,000 L PBR, respectively. This work provides an optimized light recipe, superior mutant consortia, and scalable PBR design, effectively bridging laboratory-scale research with industrial application potential.

An interpretable nondestructive detection model for maize seed viability: Based on grouped hyperspectral image fusion and key biochemical indicators - Yaoyao Fan; Ting An; Xueying Yao; Yuan Long; Qingyan Wang; Zheli Wang; Xi Tian; Liping Chen; Wenqian Huang (Computers and Electronics in Agriculture, 2025)

Research on the potential of reconstructing spectral indices and dividing crop growth stages based on satellite remote sensing for monitoring soil moisture in farmland - Tianjin Dai; Junying Chen; Hao Liu; Lu Liu; Shuailong Fan; Xuqian Bai; Long Qian; Hao Liu; Yalan Ba; Qiongda (Computers and Electronics in Agriculture, 2025)

Combining dual-wavelength laser-induced fluorescence hyperspectral imaging with mutual information decomposition and redundancy elimination method to detect Aflatoxin B1 of individual maize kernels - Yaoyao Fan; Xueying Yao; Zheli Wang; Yuan Long; Jian Kang; Liping Chen; Wenqian Huang; Xi Tian (Computers and Electronics in Agriculture, 2025)

Residential preferences and purpose-specific walking behaviors: Mediation effects of built environments - Yuanyuan Shi; Chun Yin; Yingying Long; Jing Wen; Lingyun Fan (Transportation Research Part D: Transport and Environment, 2025)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Unveiling the functional contribution of Malpighian tubule specific glucose transporters to xenobiotics tolerance in Spodoptera litura - Long Jin; Zixin Zhang; Haoran Kong; Chengcheng Fan; Furong Mao; Yiou Pan; Qingli Shang (Pesticide Biochemistry and Physiology, 2025)

Fat body specific ABCG3 accounts for xenobiotic tolerance and is regulated by the homeobox transcription factor Bcd in Spodoptera litura - Lin Liang; Long Jin; Furong Mao; Chengcheng Fan; Haoran Kong; Zixin Zhang; Yiou Pan; Qingli Shang (Pesticide Biochemistry and Physiology, 2025)

Recycled oceanic crust restricting trace element enrichment in mid-ocean ridge basalts - Fan Yang; Xiao-Long Huang; Yi-Gang Xu; Yang Yu; Peng-Li He; Le Zhang; Ze-Xian Cui (Lithos, 2025)

Efficient removal of microplastics through a combined treatment process: Pre-filtration and adsorption - Bo Lv; Wen Fan; Long Li; Yutong Jiao; Man Wang; Baolin Xing (Journal of Environmental Management, 2025)

Ag2O-decorated poly(lanthanide–β-cyclodextrin) based on a silica microsphere with reversible photo-regeneration: Highly sensitive and broad-spectrum fluorescent sensing of tetracycline antibiotics - Junlong Li; Zerong Long; Jianling Wang; Tianli Fan; Laifang Qi (Journal of Environmental Chemical Engineering, 2025)

Precision prediction of trihalomethanes in drinking water and three-stage regulation mechanism: A study based on XGBoost-SHAP framework - Yang Tao; Gongduan Fan; Feinan Liu; Jing Luo; Ruseng Zou; Yuzhou Huang; Yuhuan Cao; Jiayu Long; Kai-Qin Xu (Journal of Environmental Chemical Engineering, 2025)

Recent advances in the applications of Bacillus subtilis in the fermentation of food: Improving product quality and enhancing biological activity - Xin Gao; Ruifeng Fan; Long Tan; Jiaqi Fu (Food Research International, 2025)

Wheat germ peptides enhance hypoxia tolerance by modulating gut microbiota and reprogramming brain energy metabolism in mice - Jing-yang Cai; Ying-Ying Liu; Meng-Cheng Li; Xin-Xin Guo; Ai-Mei Liao; Yin-Chen Hou; Quan-Ping Liu; Yong-Chao Fan; Long Pan; Ji-Hong Huang (Food Bioscience, 2025)

Boosting (E)-nerolidol yield in Serratia marcescens via nerolidol synthase engineering and competitive pathway knockout - Na Chen; Linbo Gou; Di Liu; Shengfang Wu; Xiuwen Zhou; Tai-Ping Fan; Long Wang; Yujie Cai (Food Bioscience, 2025)

LPS disrupts erythroid-myeloid balance in zebrafish via Jak2/Stat3-Hif1a signaling - Hai-Chuan Yu; Meng-Yao Chen; Shuang-Ling Zhang; Fang-Chao Tong; Fan-Ping Wang; Lin Wang; Jia-Long Zhang; Jiao-Jie Guo; Bing-Yang Zhang; Jia-Qi Tian; Jiao Wu (Fish & Shellfish Immunology, 2025)

Real-time food freshness monitoring with AI assisted colorimetric and fluorescent dual-mode paper-based sensors: Harnessing size-dependent effects of mesoporous Cu2O - Zixin Jin; Zhiwei Liu; Ziwuzhen Wang; Yuqing Yang; Hongyu Shi; Caixu Fan; Yamin Liu; Qiuyue Ji; Wei Sheng; Long Ma; Shuo Wang (Chemical Engineering Journal, 2025)

Effects of gum incorporation on the properties of sodium alginate-based composite hydrogel beads for encapsulating lactic acid bacteria - Ying-Ying Jing; Yun-Cheng Li; Yong-Qi Luo; Long-Hua Zou; Yuan-Mou Tang; Yu-Xi Lin; Fan-Bing Meng (Carbohydrate Polymers, 2025)

Genome-wide survey and expression analysis of JAZ genes in watermelon (Citrullus lanatus) - Yan-Ge Li; Jing Zhang; Xiu-Xiu Cai; Le-Ping Fan; Zhong-Hou Zhu; Xue-Jie Zhu; Da-Long Guo (Molecular Biology Reports, 2025)

PACS2/PKCα/NOX4 pathway damaged the renal vascular endothelial barrier by promoting ROS production in diabetic nephropathy mice - Xinru Zheng; Qianjun Zhu; Jie Ouyang; Jing Zhang; Quanjun Liu; Jianing Fan; Peng Gao; Haijiao Long; Hong Xiang; Hongwei Lu (Molecular and Cellular Biochemistry, 2025)

USP18-mediated protein stabilization of NOTCH1 is associated with altered Th17/Treg cell ratios and B cell-mediated autoantibody secretion in Sjögren syndrome - Xiaorong Jin; Yunjing Bai; Xiaohua Xu; Fan Wu; Xiaoyu Long; Yajuan Yao (Immunologic Research, 2025)

Critical processes controlling the formation of visible gold in the giant Jiaodong gold province: Constraints from microtextural and geochemical analyses by SEM, TOF–SIMS, and LA-(MC)-ICP-MS - Hong Wang; Ting-Guang Lan; Lang-Ye Zhao; Hong-Rui Fan; Zhan-Ping Li; Huan-Long Hu; Zi-Qi Xu; Hong-Wei Peng; Lei Shu (Acta Geochimica, 2025)

Stock Assessment Using Three Bayesian Models for Chinese Icefish in Taihu Lake, a Major Freshwater Fishery in the Yangtze River Basin, China - Zhipeng Li; Long Ren; Yingchun Fan; Dongpo Xu (Fisheries Management and Ecology, 2025)
Inland fisheries play a crucial role in global food security, particularly in low‐income regions, yet their management has often been overshadowed by a focus on marine fisheries. We investigated the resource utilization and management status of Chinese icefish ( Neosalanx tangkahkeii ) in Taihu Lake, the largest freshwater lake in East China with significant fishery resources, over 35 years prior to the implementation of a decade‐long fishing ban in 2020. Using three surplus production models (SPMs)—ASPIC, SPiCT, and JABBA—we evaluated historical biomass and fishing pressure dynamics of the Chinese icefish population. Persistent overfishing that reduced annual biomass consistently below MSY for over two decades confirmed unsustainable fishing mortality. The SPiCT model was the best fitting, but all models were reliable, with

Functional insights into avrPto5 from Pseudomonas syringae pv. actinidiae and its interaction with zinc finger proteins regulating plant defenses - Muhammad Asif; Ting Xie; Rong Fan; Youhua Long; Zhibo Zhao (Physiological and Molecular Plant Pathology, 2025)

Fe-Cu separation in skarn deposits: Insights from magmatic and hydrothermal titanite - Fang-Yue Wang; Xian Liang; Long Zhang; Tao-Fa Zhou; Yu Fan; Xian-Zheng Guo; Yong-Hong Guo; Jun-Wu Zhang (Lithos, 2025)

Mg-Fe isotopic constraint on the role of the lithosphere mantle in arc magmatism - Yang Yu; Xiao-Long Huang; Fan Yang; Yu Wang; Yi-Gang Xu; Iwan Setiawan; Sun-Lin Chung; Le Zhang; Guan-Hong Zhu (Lithos, 2025)

Mantle evolution of the nascent oceanic basin subsequent to continental breakup constrained by Mo–Sr–Nd–Hf isotopes in MORBs from the northern margin of the South China Sea - Yu-Xin Cai; Xiao-Long Huang; Fan Yang; Yang Yu; Jie Li; Zhen-Min Ge (Lithos, 2025)

NCOA4-dependent ferritinophagy drives perfluorooctanoic acid-triggered renal ferroptosis in chicken embryos - Jie Yang; Xue Wen; Yi-Tong Fu; Chao Li; Hai-Long Chang; Yao-Yao Lu; Xue-Ru Li; Rui-Feng Fan (Journal of Hazardous Materials, 2025)

Quantifying threshold water tables for the stability of the oasis-desert ecotone in arid areas - Yong Wang; Xing Li; Yong Zhao; Long Yan; Fan He; Jiaqi Zhai; Yajie Hu; Yuan Liu; Wei Deng; Zhu Wang; Qingming Wang; Minjian Chen (Journal of Environmental Management, 2025)

Investigation of rare earth element extraction from coal byproducts using supercritical CO2 - Uthej Veerla; Long Fan (Hydrometallurgy, 2025)

Electroencephalography (EEG) design for flavor perception of Baijiu: An investigation into the influence of full-bodied mouthfeel on brain rhythms - Panpan Chen; Yubo Yang; Jinyuan Sun; Shui Jiang; Imre Blank; Bohan Zhang; Chao Chen; Tianjun Long; Liangyan Chen; Hongyan Tang; Fan Yang; Yuan Liu (Food Chemistry, 2025)

Deterioration mechanism for the solubility of skimmed egg yolk powder: powder characteristics, rehydration capability and protein structure - Xiang Fan; Yuanyuan Zhang; Yi Sun; Yanbin Song; Yunxin Sun; Sadaqat Ali; Haobo Jin; Long Sheng (Food Chemistry, 2025)

China’s food security and food system governance: recent developments and global implications - Wenjin Long; Ting Meng; Xu Tian; Shenggen Fan (Food Policy, 2025)

Exposure to heavy metals from Chaohu Lake impairs motor ability and reproductive fitness in Drosophila - Huan Zhou; Jin Zhang; Long-Long Fan; Zhi Yuan; Qi Lu; Gang Liu; Yu-Hong Nie; Yi-Fan Hu; Shen-Dong Xu; Xu-Dong Zhang; Ye-Xin Luo; Hua-Long Zhu; et al. (Environmental Research, 2025)

Long-range nighttime dynamic monitoring of long-span cable-stayed bridge with the enhanced bokeh tracking method using closing operation and Long Short-term Memory networks - Jingxi Qin; Jiale Long; Mingjin Zhang; Renan Yuan; Fan Jiang; Wenhui Duan (Engineering Structures, 2025)

Engineering a robust and versatile terpenoid production platform in Serratia marcescens HBQA7 - Long Wang; Linbo Gou; Di Liu; Shengfang Wu; Xiuwen Zhou; Tian Yang; Tai-Ping Fan; Yujie Cai (Chemical Engineering Journal, 2025)

Spin orbit charge transfer enhances intermolecular hydrogen atom transfer catalyzed polymerization for conductive elastomers syntheses - Qingze Pan; Saran Long; Jianwei Li; Pengzhong Chen; Junhui Wang; Kaifeng Wu; Jiangli Fan; Xiaojun Peng (Chemical Engineering Journal, 2025)

Susceptibility of mud crabs (Scylla paramamosain) to the infection with decapod iridescent virus 1 - Min-Ze Liao; Hong-Ling Ma; Chang-Hong Cheng; Guang-Xin Liu; Si-Gang Fan; Yi-Qin Deng; Juan Feng; Xin-Jian Liu; Zhi-Long Chen; Zhi-Xun Guo (Aquaculture, 2025)

Application of supercritical carbon dioxide in textile material manufacturing: A theoretical investigation of hybrid fluid field and flowing in a universal vessel by numerical simulation models - Fan Wang; Lan Xu; Jia-Jie Long (Process Safety and Environmental Protection, 2025)

Research and application mechanism of chlorination roasting for polymetallic minerals and waste - Zhi-yu Fan; Long Wang; Ren-yun Zhang; Yi-yong Wang; Ting-an Zhang; Xing-jian Wang; Ji-dong Li; Xin-xin Zhao; Wei-juan Li (Minerals Engineering, 2025)

Metal bioaccumulation and lipid response in aquatic ecosystem: Evidence of machine learning from Chaohu Lake, China - Qi Lu; Zhi Yuan; Wei Chang; Shen-dong Xu; Lan-lan Wu; Gang Liu; Li-yan Yang; Si-ting Liu; Meng-xue Gao; Yi-fan Hu; Xu-dong Zhang; Huan Zhou; et al. (Journal of Hazardous Materials, 2025)

Current status and influencing factors of blue carbon in seagrass beds: An extensive survey and comprehensive analysis in the Yellow and Bohai Seas, China - Xiang Zhao; Jie Sun; Fan Li; Shao-Wen Li; Hai-Xia Su; Xiu-Fen Ma; Lei Yang; Gui-Xiang Zheng; Wan-Long Sun; Pei-Dong Zhang (Journal of Environmental Management, 2025)

Electrochemical separation technology utilizing MXene composites for environmental pollutant removal: A comprehensive review - Zi Long; Shuhui Fan; Min Wang; Guiqing Gao; Shaorong Huang; Xiaoyong Zhang; Yen Wei (Journal of Environmental Chemical Engineering, 2025)

Cobalt boride derived from metal-organic framework as highly efficient catalyst for tetracycline degradation with peroxymonosulfate activation - Huali Wang; Jiaying Zang; Yaoyao Zhang; Jie Zhang; Yan Pu; Yan Long; Pengyao You; Guangyin Fan; Yi Wang (Journal of Environmental Chemical Engineering, 2025)

Effect of H2O physicochemical properties on NO formation mechanism in NH3 oxy-steam combustion under MILD mode - Xiaojian Zha; Zewu Zhang; Zhenghong Zhao; Long Yang; Wenchao Mao; Fan Wu; Xiaoshan Li; Cong Luo; Liqi Zhang (Fuel, 2025)

Multi-scale analysis of the influence of red-bed lithological interface on tunnel deformation and instability - Jing-Kai Qu; Yi-Guo Xue; Fan-Meng Kong; Cui-Ying Zhou; Zhen Liu; Zuo-Peng Wang; Jin-Rui Duan; Yan Ai; Zi-Ming Qu; Jian-Ning Wang; Bo Wang; Chao Lu; et al. (Engineering Geology, 2025)

Microbially induced phosphate precipitation disentangles sludge retention time trade-off enabling efficient phosphorus removal with minimal sludge discharge in aerobic granular sludge - Peng Bi; Xiaohui Yan; Yueying Song; Hebin Miao; Hui Sun; Ying Han; Long Chen; Kangxin Yan; Mingyang Li; Fan Xiong; Jingwei Ma; Qiulai He (Chemical Engineering Journal, 2025)

Highly stable and active cerium single-atom immobilized Ti3C2TX MXene for high-stability lithium‑sulfur batteries - Shengdong Jing; Shilan Li; Xiaoli Peng; Long Yuan; Shengjun Lu; Yufei Zhang; Haosen Fan (Chemical Engineering Journal, 2025)

Polysaccharide nano‑selenium in the regulation of neuroinflammation: A review of mechanisms, functional potential, and activity evaluation - Xinyue Liu; Simal-Gandara Jesus; Zhiqiang Kong; Ningning Fan; Yunchong Mi; Qiong Wang; Yatao Huang; Long Li; Jia Lu; Bei Fan; Minmin Li (Carbohydrate Polymers, 2025)

PM2.5 and PM10 vertical distribution retrieval methods based on coherent Doppler lidar via machine learning: for haze and dust in Qingdao - Rongzhong Li; Kangwen Sun; Xitao Wang; Guangyao Dai; Mengqi Fan; Li Ma; Xiaowei Zheng; Wenrui Long; Fanqian Meng; Qichao Wang; Songhua Wu (Atmospheric Environment, 2025)

Bone marrow mesenchymal stem cells promote the recovery of stroke in rats with type 2 diabetes mellitus by inhibiting the activation of TLR4/NF-κB signaling pathway - Fan Peng; Yanping Long; Taolin Zheng; Minghui Leng; Hui Deng (Molecular and Cellular Biochemistry, 2025)

Comparative evaluation of selected adjuvants for possible application of Aeromonas caviae inactivated vaccine in crucian carp (Carassius auratus) - Han Lu; Tao-luo Tao; Yu-Long Liu; Fan Jia; Yi-feng Cui; Xiao-feng Shan (Aquaculture International, 2025)

Egg powder: Constraints, methods of enhancing functional properties and innovative applications - Xiang Fan; Mohamed Salama; Yuanyuan Zhang; Sadaqat Ali; Yi Sun; Yanbin Song; Yunxin Sun; Yumeng Shan; Haobo Jin; Long Sheng (Trends in Food Science & Technology, 2025)

Spatiotemporal analysis of CO₂ emissions from heavy-duty trucks in belt and road port transportation using GPS trajectory data - Jingwei Guo; Haofei Guo; Zhen-Song Chen; Zhitao Fan; Wen-Long Shang (Resources, Conservation and Recycling, 2025)

Changes in cell wall characteristics and expression of MiERF12, MiERF109-like, and MiERF113 during mango softening - Yuhan Long; Lihong Xie; Ping Yi; Fang Huang; Min Huang; Ting Gan; Jian Sun; Li Li; Hao Dong; Qi Wei; Zhenmei Fan; Qiuyu Cheng (Postharvest Biology and Technology, 2025)

Ras-associated protein PdRSR1 is essential for sterol synthesis and stress tolerance to response to prochloraz in Penicillium digitatum - Fan Yang; Sirong Ji; Lanping Bai; Yan Ke; Weiqiang Lai; Chao-An Long (Pesticide Biochemistry and Physiology, 2025)

OsATG1 and OsATG8 exhibit autophagy-independent functions to oppositely regulate ROP GTPase-mediated plant immunity in rice - Feng He; Hui Tao; Ruyi Wang; Jinling Liu; Zeyun Hao; Debao Wang; Xuetao Shi; Fan Zhang; Jiawei Long; Hao Zhang; Xiao Yang; Mengchao Qin; et al. (Molecular Plant, 2025)

Comparative analysis of phytoplankton community structure and stability in the Arabian Sea and Bay of Bengal using eDNA metabarcoding - Changwen Li; Ge Xiao; Han Long; Tongxi Ai; Fenghua Tang; Jianfeng Ju; Shenglong Yang; Yan Pi; Lei Gao; Lingbo Ma; Wei Fan; Ming Zhao; et al. (Marine Environmental Research, 2025)

Green spaces and preventable disease and economic burdens in China from 2000 to 2020: A health impact assessment study - Hui-Ling Qiu; Hui-Yun Chen; Yu-Ting Xie; Gang-Long Zhou; Kai-Ze Yang; Hai-Juan Huang; Jian-Cheng Jiang; Xiao-Qi Zhu; Lu Wang; Kexin Yan; Guang-Hui Dong; Shujun Fan; et al. (Landscape and Urban Planning, 2025)

Specific catalytic hydrogenation of 2-butyne-1,4-diol to butane-1,4-diol - Li Li; Xian-Yong Wei; Shun-Hong Lv; Xiang Bai; Yierxiati Dilixiati; Jun-Long Wang; Xiao-Yan He; Zhi-Min Zong; Xing Fan (Fuel, 2025)

Optimizing removal and control of inclusions/impurities and recovery of valuable elements in metallurgical melts via electric field: toward circular economy and resource efficiency - Wen-zhi Xia; Hai-chuan Wang; Ruipeng Pang; Yun Zhou; Zhi-you Liao; Ting Wu; Baowen He; Guang-da Bao; Zhen Hou; Shao-long Chu; Ping-fan Ren (Chemical Engineering Journal, 2025)

Scalable and interpretable automated machine learning framework for biogas prediction, optimization, and stability monitoring in industrial-scale dry anaerobic digestion - Long Chen; Pinjing He; Jinlin Zou; Hua Zhang; Wei Peng; Fan Lü (Chemical Engineering Journal, 2025)

Glucose membrane-assist pyrolysis engineered ultrafine FeP/CoP3-doped hollow carbon nanospheres: Enhanced bifunctional oxygen catalysts for rechargeable zinc-air batteries - Fan Li; Jilan Long; Li Kang; Fei Zhao; Simeng Ding (Chemical Engineering Journal, 2025)

Klotho mediates the association between serum testosterone and severe abdominal aortic calcification: a cross-sectional study from the NHANES database - Shengwei Lai; Handai Qin; Xinhao Wang; Guanchao Sun; Long Cao; Zheqi Fan; Hongpeng Zhang; Wei Guo (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Investigation of Near-Surface S-Wave Velocity Structure beneath the Epicenter and adjacent Area of the Jishishan Earthquake by using the Receiver Function - Fan-chang Meng; Ruo-ge Xu; Hui Sun; Bo Li; Yun Long (Applied Geophysics, 2025)

Depletion of Albendazole and Its Metabolites and Their Impact on the Gut Microbial Community Following Multiple Oral Dosing in Yellow River Carp (Cyprinus carpio haematopterus) - Yue Liu; Yan Dai; Yan-Ni Zhang; Wen-Rui Wang; Yu-Xin Chen; Yang-Guang Jin; Long-Ji Sun; Shi-Hao Li; Fang Yang; Xing-Ping Li; Fan Yang (Fishes, 2025)
Healthy Yellow River carp (Cyprinus carpio haematopterus) reared at a water temperature of 23 ± 0.6 °C were orally administered albendazole (ABZ) at a dose of 12 mg/kg body weight (BW) once daily for seven consecutive days. At predetermined time points after the final administration, five fish were randomly selected for sampling. Plasma, skin-on-muscle, liver, and kidney tissues were collected, and the concentrations of ABZ and its three metabolites—albendazole sulfoxide (ABZSO), albendazole sulfone (ABZSO2), and albendazole-2-aminosulfone (ABZ-2-NH2−SO2)—were determined using high-performance liquid chromatography (HPLC). The results indicated that ABZ and ABZSO were widely distributed across tissues, while ABZSO2 and ABZ-2-NH2-SO2 were only present at trace levels. Pharmacokinetic analysis of ABZ and ABZSO in plasma and tissues was performed using noncompartmental analysis (NCA). ABZ peaked in plasma at 0.73 μg/mL at 24 h after the last administration, with an elimination half-life (t1/2λZ) of 38.56 h. ABZSO reached a peak plasma concentration of 1.54 μg/mL at 24 h, with a t1/2λZ of 53.73 h. According to China’s national standard, where ABZ-2-NH2−SO2 is the marker residue with a maximum residue limit (MRL) of 100 μg/kg in fish skin-on muscle, no withdrawal period was necessary. However, based on the European Union standard—which uses the sum of ABZ and its three metabolites as the marker residue and an MRL of 100 μg/kg in ruminants—a withdrawal period of 16 days (or 351 °C-days) was required. Additionally, the study assessed changes in the intestinal microbiota following multiple oral doses of ABZ. The results indicated that ABZ administration significantly altered microbial diversity and composition in a dose- and time-dependent manner. After drug withdrawal, the intestinal microbiota gradually returned to baseline levels, similar to the untreated control group.

A constrained multi-objective evolutionary algorithm based on online problem identification and separate handling - Xinyu Zhou; Long Fan; Kunjie Yu; Kangjia Qiao (Swarm and Evolutionary Computation, 2025)

Implementation and topological characterization of Weyl exceptional rings in quantum-mechanical systems - Hao-Long Zhang; Pei-Rong Han; Xue-Jia Yu; Shou-Bang Yang; Jia-Hao Lü; Wen Ning; Fan Wu; Qi-Ping Su; Chui-Ping Yang; Zhen-Biao Yang; Shi-Biao Zheng (Science Bulletin, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Optimizing lithium recovery from artificial β-spodumene slags: A breakthrough in pyrometallurgical processing of spent lithium-ion batteries - Shiliang Chen; Xin Wang; Hu Li; Guan Xiutao; Youqi Fan; Yuchi Yan; Zhipeng Guo; Hanbing He; Hongming Long (Journal of Environmental Chemical Engineering, 2025)

Selective sulfite activation based on a non-radical reaction pathway with dominant 1O2 generation triggered by oxygen vacancies-enriched CuCo2O4 for efficient degradation of ciprofloxacin - Jinyuan Zhang; Long Cao; Jianxin Liu; Yawen Wang; Rui Li; Xiaochao Zhang; Yunfang Wang; Caimei Fan (Journal of Environmental Chemical Engineering, 2025)

Primary greisen-type tin mineralization: Insights from unidirectional solidification texture in oxidized, fluorine-rich ores from the Paleocene Kalonta Sn-W deposit, southern Myanmar - Jin-Xiang Li; Wei-Ming Fan; Rui Yuan; Lamu Ciren; Li-Yun Zhang; Fu-Long Cai; Ya-Hui Yue; Jing Xie; Lin Ding (Journal of Asian Earth Sciences, 2025)

High-sensitivity detection of hydrogen sulfide and water content using a Triphenylamine-based fluorescent probe: Applications in food safety monitoring - Yanqing Xu; Zhaojiang Yin; Qian Long; Haotian Xie; Xinying Yan; Fusheng Liao; Hanfeng Cui; Hao Fan (Food Chemistry, 2025)

Improved Biome-BGC model for simulating spatiotemporal dynamics of gross primary productivity in evergreen broadleaf forests of the karst region - Hengyuan Liu; Qian Ding; Yuechen Li; Lei Fan; Long Zhao; Mingguo Ma (Environmental Modelling & Software, 2025)

NPK-N application limits grain cadmium concentration of wheat via promoting Cd export during grain filling - Yiran Cheng; Yuanjiang He; Jia Chen; Weiping Li; Wenhui Xiang; Xing Chen; Dan Long; Jian Zeng; Yang Liu; Dongwei Wang; Dandan Wu; Lina Sha; et al. (Plant and Soil, 2025)

Xuebijing inhibits alveolar macrophage M1 polarization by regulating ROS-mediated NLRP3 inflammasome signaling - Xuelian Chen; Fan Zhang; Zhiguo Zhou; Dixuan Jiang; Long Wen (In Vitro Cellular & Developmental Biology - Animal, 2025)

Antibacterial Activity of Essential Oils from Clove and Elsholtzia Plants Against Common Pathogens of Bovine Mastitis, Antioxidant Activity, and Toxicity to Bovine Mammary Epithelial Cells - Xu-Dong Wang; Jia-Li Bai; Zhen-Jia Ma; Jie Fan; Wei-Bao Kong; Jun-Long Wang; Ji Zhang; Jun-Yu Liang (Current Microbiology, 2025)

Intercropping enhances stable soil organic carbon pool through macroaggregate protection and biochemical recalcitrance interactions - Ding Wang; Wenchun Yu; Chunyan Ming; Linkang Chen; Ping Zhao; Xiaojun Shi; Zhengxiong Zhao; Maopan Fan; Guangqiang Long (Agriculture, Ecosystems & Environment, 2025)

Research on Operational Risk for Northwest Passage Cruise Ships Using POLARIS - Long Ma; Jiemin Fan; Xiaoguang Mou; Sihan Qian; Jin Xu; Liang Cao; Bo Xu; Boxi Yao; Xiaowen Li; Yabin Li (Journal of Marine Science and Engineering, 2025)
In the context of global warming, polar tourism is developing rapidly, and the demand for polar cruise travel in the Northwest Passage continues to increase, while sea ice has long been a key factor limiting the development of polar cruise tourism. This study focuses on the operational risk of sea ice on cruise ships in the Northwest Passage (NWP), aiming to provide a scientific basis for ensuring the safety of cruise ship navigation and promoting the sustainable development of polar tourism. Based on ice data from 2015 to 2024, this study used the Polar Operational Limit Assessment Risk Indexing System (POLARIS) methodology recommended by the International Maritime Organization (IMO) to establish three scenarios for the route of ice class IC cruise ships: light ice, normal ice, and heavy ice. The navigable windows were systematically analyzed and critical waters along the route were identified. The results indicate that the navigable windows for IC ice-class cruise ships under light ice conditions are from mid-July to early December, while the navigable period under normal ice conditions is only from mid- to late September, and navigation is not possible under heavy ice conditions. The study identified Larsen Sound, Barrow Strait, Bellot Strait and Eastern Beaufort Sea as critical waters on the NWP cruise route. Among them, Larsen Sound and Eastern Beaufort Sea have a more prominent impact on voyage scheduling because their navigation weeks overlap less with other waters. This study provides a new idea for the risk assessment of polar cruise ships in ice regions. The research results can provide an important reference for the safe operation of polar cruise ships in the NWP and the decision-making of relevant parties.

Synergistic recovery for Al and Ga within high-alumina fly ash by carbochlorination using the response surface method - Wang Long; Zhao Xin-xin; Zhang Zi-mu; Zhang Ting-An; Lv Guo-Zhi; Dou Zhi-He; Liu Yan; Fan zhi-yu (Waste Management, 2025)

A strategy to improve the detection accuracy and universality of highland barley muti-quality attributes based on near infrared spectroscopy combined with model transfer method - Linglei Li; Long Li; Jingfeng Li; Jingjing Yang; Lang Jia; Bei Fan; Litao Tong; Liya Liu; Yatao Huang; Xiaolong Yang; Fengzhong Wang; Lili Wang (Food Chemistry, 2025)

Gut microbiota mediated immunoregulatory effects of Dendrobium officinale polysaccharides-selenium nanoparticles complexes - Yan Long; Jiajing Yang; Hongfei Ji; Yuting Fan; Keyao Dai; Wenjie Ding; Haiyu Ji; Juan Yu (Food Bioscience, 2025)

Corrigendum to “Porous liquids based on ZIF-67@ZIF-8 through the strategy of interface layer reconstruction for CO2 selective sorption” [Chem. Eng. J. 500 (2024) 156655] - Jiadi Li; Yangyang Xin; Zheng Dong; Baolu Cui; Zhiye Du; Jingwen Wang; Libing Qian; Shuangshuang Long; Zicheng Wei; Wendi Fan; Jinwen Fan; Yunpan Ying; et al. (Chemical Engineering Journal, 2025)

A flexible intelligent sensor for patients with amyotrophic lateral sclerosis - Lei Duan; Zhi Li; Fan Jiang; Zong-Ju Chen; Wei-Song Zhang; Pei-Chen Zhao; Li-Chun Wang; Yan-Long Luo; Che Zhao; Cheng-Hui Li (Chemical Engineering Journal, 2025)

Double-punch strategy: Macrophage membrane-enveloped imipramine and aCD47 reprograms tumor microenvironment to enhance glioblastoma immunotherapy - Long Zhang; Yining Zhang; Ji Qi; Jiahao Yu; Haojie Hu; Xiangrong Lu; Jiangpeng Fan; Guimei Cui; Rutong Yu; Xiuping Zhou (Chemical Engineering Journal, 2025)

Engineering of farnesyl pyrophosphate hydrolase for farnesol production in Serratia marcescens - Xia Chen; Di Liu; Long Wang; Yao Lu; Yongai Ma; Tai-Ping Fan; Yujie Cai (Systems Microbiology and Biomanufacturing, 2025)

Comparative Research on Vessel Navigability on the Northern Sea Route Based on the NSR Admission Criteria and POLARIS Methodology - Long Ma; Sihan Qian; Xiaoguang Mou; Jiemin Fan; Jin Xu; Liang Cao; Bo Xu; Boxi Yao; Xiaowen Li; Yabin Li (Journal of Marine Science and Engineering, 2025)
At present, sea ice remains a critical factor affecting the safety of vessel operations along the Northern Sea Route (NSR). However, inconsistencies between the navigability outcomes derived from the criteria for the admission of ships in the area of the Northern Sea Route (NSR criteria) and the polar operational limit assessment risk indexing system (POLARIS) methodology present challenges for navigational decision-making. This study aims to conduct a systematic comparison of the POLARIS methodology and the NSR criteria in evaluating the navigability of independently operating vessels classified as Arc4 to Arc9. Through comparative calculations of navigability and the navigability rates for six ice-class vessels across 27 districts using the two methods, this study reveals the consistencies and discrepancies in their navigability outcomes. Firstly, using the POLARIS methodology, the risk index outcome (RIO) is calculated for six ice-class vessels across 27 districts. For these districts, the navigability threshold is defined when 95% or more of the area exhibits an RIO greater than or equal to zero. Secondly, using the NSR criteria, navigability ratios for six ice-class vessels under varying ice conditions are evaluated. A navigability threshold is defined when 95% or more of the ice conditions in a district are classified as navigable. Finally, a quantitative comparison of the weekly navigability ratios obtained by the two methods is conducted to reveal the consistencies and discrepancies in the navigability outcomes of each ice-class vessel across different NSR districts. The results indicate that the consistency between the navigability outcomes of the two methods decreases with lower vessel ice classes, particularly in September and March. In general, the consistency of performance between the two methods in terms of navigability outcomes deteriorates as the vessel ice class decreases and ice conditions become more complex. This study provides a scientific foundation and data-based support for route planning and real-time decision-making in polar waters.

Cleaner purification of contaminants on cotton substrate interfaced with supercritical carbon capsules for sustainable development in cleaning industries - Meng-Yue Li; Fan Wang; An-Tong Liu; Qing-Cheng Tang; Xue Dong; Jia-Jie Long (Process Safety and Environmental Protection, 2025)

Analysis of driving factors and suitability assessment for raft aquaculture in the Northern China seas using remote sensing data - Long Gao; Xiao He; Junmin Zhang; Bo Wang; Sijia Tian; Kunfu Wang; Mengnan Chen; Wenzhuo Lin; Xian Wu; Mingrui Fan (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

A systematic review on mechanism and regulation strategy of marine hydrodynamic noise: Advances, challenges, and perspectives - Xin Jin; Hua-long Huang; Yuan Tao; Fu-gui Zhang; Min Luo; Chang-yuan Fan; Tao Tang (Ocean Engineering, 2025)

Microbial mechanism of naturally formed stable partial nitrification in sequencing batch biofilm reactors - Xiao-Yan Fan; Yue Niu; Xing Li; Shen-Bin Cao; Meng-Yuan Zheng; Shi-Long Zhou (Journal of Environmental Chemical Engineering, 2025)

Mechanisms of chemical corrosion in alumina-chromite refractories during e-waste recovery via pyrometallurgy - Shiliang Chen; Jian Wu; Xin Wang; Youqi Fan; Yuntao Yan; Xiutao Guan; Zhipeng Guo; Sen Zhao; Wenlong Tan; Chao Ding; Hongming Long (Journal of Environmental Chemical Engineering, 2025)

Effect of alternating current electric fields on the preservation of fresh-cut Chinese cabbage and spinach - Wenjing Xiong; Jia Meng; Yuxin Zhang; Guozhi Fan; Cheng Pan; Canduo Shen; Yifei Long (Innovative Food Science & Emerging Technologies, 2025)

Revealing the potassium poisoning mechanism of V2O5-MoO3/TiO2 catalyst for chlorobenzene catalytic oxidation - Jiaying Xing; Jisheng Long; Li Bai; Guimin Wang; Yufei Fan; Haiyan Liu; Jianjun Chen; Junhua Li (Fuel, 2025)

A 7-year feed study on the long-term effects of genetically modified maize containing cry1Ab/cry2Aj and EPSPS genes on gut microbiota and metabolite profiles across two generations of cynomolgus macaques - Chenyun Wang; Shengtao Fan; Minghao Li; Yousong Ye; Zheli Li; Weihu Long; Yongjie Li; Zhangqiong Huang; Qinfang Jiang; Wanjing Yang; Rujia Yang; Donghong Tang (Food and Chemical Toxicology, 2025)

Overcrowded steric engineering of through-space interactions for anti-quenching multi-resonance TADF materials - Ru-Jia Wang; Fan Zheng; Jie Hu; Yu-Lan Wu; Xiao-Long Liu; Jia-Xiong Chen; Longjiang Xing; Qiao-Er Wu; Yanping Huo; Wen-Cheng Chen (Chemical Engineering Journal, 2025)

Effective collective value-added recycling of nitrate and sulfion in wastewater via synergistic electrocatalysis of dual-active sites on copper-cobalt oxides - Donglin Zhao; Song Wu; Yihan Zhang; Dongxu Cao; Ruizhi Li; Yan Long; Guangyin Fan (Chemical Engineering Journal, 2025)

ARHGAP17 Inhibits Hepatocellular Carcinoma Progression by Inactivation of Wnt/β-Catenin Signaling Pathway - Sirui Fan; Hongqing Zhao; Cheng Li; Xing Chen; Mingjie Sun; Fengyang Chen; Chao Long; Yinghui Zhou; Boyuan Nan; Hao Zhao; Wei Zhang (Biochemical Genetics, 2025)

COP1 Overexpression Attenuates Nociceptive Behaviors and Neuroinflammation in Cancer-Induced Bone Pain by Suppressing c/EBPβ - Dan-Yang Li; Lin Liu; Shao-Jie Gao; Dai-Qiang Liu; Long-Qing Zhang; Jia-Yi Wu; Fan-He Song; Xin-Yi Dai; Ya-Qun Zhou; Wei Mei (Journal of Neuroimmune Pharmacology, 2025)

Overview of monitoring methods and environmental distribution: Microplastics in the Indian Ocean - Long Zhou; Jingxi Li; Chang Zhao; Jiaxuan Yin; Jinfeng Ding; Wei Cao; Wei Fan (Marine Pollution Bulletin, 2025)

Accurate identification and formation mechanism unraveling of radicals in UV-induced peracetic acid activation system using in-situ electron paramagnetic resonance - Long Chen; Ruohan Zhang; Zhaoli Liu; Fan Li; Boyu Huang; Wen Liu (Science Bulletin, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Sustainable water desalination with anti-wetting Janus membranes under simulated industrial low-grade fluctuated heat conditions in DCMD - Muhammad Mujahid; Muhammad Ali Hasnain; Ghafoor Ahmad; Chao Wang; Fan Xiao; Zhe Wu; Long-Fei Ren; Jiahui Shao (Process Safety and Environmental Protection, 2025)

Effects of microtopographic modification on soil labile organic carbon fractions and enzyme activities in urban restored wetlands - Kangting OUYANG; Zhongyu SUN; Long YANG; Guangqing HUANG; Cunxiang FAN; Zhibin LIN (Pedosphere, 2025)

Effective degradation of ammonia nitrogen wastewater by novel three-dimensional residual charcoal particle electrode - Jiale Wen; Jian Li; Jufen Zhu; Haiyu Wang; Qi Yan; Luyuan Chen; Jialu Qiao; Xiaoyong Fan; Long Yan (Journal of Water Process Engineering, 2025)

Quantifying and modeling of coal permeability spatiotemporal response: Implications for gas recovery and CO2 sequestration - Jinming Zhang; Xiaowei Hou; Shimin Liu; Yanming Zhu; Ang Liu; Long Fan; Yingjin Wang; Han Zhang (Fuel, 2025)

Ruthenium-doped molybdenum boride for electrocatalytic hydrogen evolution - Xiang Wang; Panfeng Fan; Yu Xie; Long Zhang; Jiawei Jiang; Ping Huang; Muhammad Ahmad; Yaru Cheng; Jie Zhao (Fuel, 2025)

Acid etching V2O5 nanowires cathode for high-performance zinc-ion full batteries - Huan-zhang Wen; Aiqun Kong; Yun-fei Shen; Yun-qi Fan; Jian-jie Liu; Long Chen (Chemical Engineering Journal, 2025)

Anti-detachment interface enabled ultra-flexible quinone-rich polydopamine/carbonized silk textile for reversible sodium storage - Zhiwen Long; Chonghui Fan; Zhilong Yan; Ruizhe Zhang; Hui Qiao; Keliang Wang; Ke Liu (Chemical Engineering Journal, 2025)

Stratified distribution of recycled components in the mantle of the South China Sea unveiled through magnesium isotopes - Zhen-Min Ge; Xiao-Long Huang; Fan Yang; Yang Yu; Guan-Hong Zhu; Le Zhang; Yu-Xin Cai; Guo-Hong Sun (Chemical Geology, 2025)

Mo isotope evidence for the significance of subducted continental crust in formation of post-collisional porphyry Cu deposits - Jing Jing Fan; Qiang Wang; Xiao Ping Long; Derek A. Wyman; Andrew C. Kerr; Jie Li; Zi Long Wang; Lin Gong; Dong Jing Xu; Qi Ji Yang; Le Zhang; Ze-Xian Cui (Chemical Geology, 2025)

Diaporthe hispaniae causes leaf black spot disease of kiwi crop in Guizhou Province, China - Hong Tan; Zhibo Zhao; Youhua Long; Rong Fan (Crop Protection, 2025)

Middle Paleoproterozoic tectonic evolution of the North China Craton: Constraints from the A-type granites in the Wutai area - Jingyu Wang; Yujing Wang; Wei Hong; Caiyun Lan; Jingjing Fan; Xiaoping Long (Precambrian Research, 2025)

Pepper feeding derivative Brucella sp. in the gut of Spodoptera litura (Lepidoptera: Noctuidae) affect the growth and development of host larvae - Yu Wang; Zhou Yu; Bei-Long Chen; Shao-Shao He; Zi-Yao Liu; Zheng Zhai; Lin Chen; Jiang-Bin Fan; Huan Yu; Zhi-Ping Zuo; Yong-Sheng Zhang (Pesticide Biochemistry and Physiology, 2025)

Field test of geosynthetic-reinforced floating pile-supported embankments on soft soil - Rui Rui; Shi-kai He; Long-fan Peng; S.J.M. Van Eekelen; Liang-hao Li; Yu-qiu Ye (Geotextiles and Geomembranes, 2025)

Data-driven pipeline modeling for predicting unknown protein adulteration in dairy products - Huihui Yang; Yutang Wang; Jinyong Zhao; Ping Li; Zhixiang Li; Long Li; Bei Fan; Fengzhong Wang (Food Chemistry, 2025)

Simultaneous determination of vegetable oil frying frequency and peroxide value based on the three-dimensional fluorescence spectroscopy and machine learning - Huihui Yang; Yutang Wang; Bei Fan; Qing Chen; Meifeng Wu; Fengzhong Wang; Long Li (Food Chemistry, 2025)

Identification and spatial distribution of organophosphorus flame retardants in surface soils from typical petrochemical industry and flame retardant production parks in China - Zhiyong Fan; Chaoyang Long; Xiang Ge; Zhaofa Huang; Helong Ren; Yingxin Yu; Taicheng An (Environmental Pollution, 2025)

Production of geraniol by a solvent-tolerant Serratia marcescens without the formation of geraniol derivatives - Yongai Ma; Di Liu; Long Wang; Yao Lu; Taiping Fan; Huaxiang Deng; Yujie Cai (Biocatalysis and Agricultural Biotechnology, 2025)

Equatorial plasma bubble detection based on GNSS Doppler index using support vector machine algorithm - Fenkai Zhang; Wu Chen; Fan Xu; Fang Zou; Yuanfan Deng; Long Tang (GPS Solutions, 2025)

Nitrogenous chemical constituents and their antitumor activities evaluation in vitro from the aerial parts of Corydalis impatiens (pall.) Fisch - Ze-dong Nan; Yi-dong Zhu; Chao-fan Deng; Guo-dong Jiang; Zhen-zhen Wang; Chong-long Li; Xiao-li Ma; Zhi-Bo Jiang (Natural Product Research, 2025)

Parameter optimization of vibration and crushing combination digging device based on soil-tuber breakage model - Sifang Long; Shuo Kang; Shaomin Xu; Yueguang Liu; Jiali Fan; Jun Wang (Computers and Electronics in Agriculture, 2025)

Mixed exposure to PFOA and PFOS induces oocyte apoptosis and subfertility in mice by activating the Hippo signaling pathway - Xiang-Zhu Yan; Jia Peng; Yu-Qing Liu; Ruo-Nan Fan; Xin-Yi Ni; Ling Gong; Dan-Ni Zhang; Xin Huang; Shu-Hua Tan; Hai-Long Wang (Reproductive Toxicology, 2025)

The Arabidopsis heterotrimeric G protein α subunit binds to and inhibits the inward rectifying potassium channel KAT1 - Jiang-Fan Guo; Hui Zhou; Zhuo-Ran Hu; Ya-Lan Yang; Wen-Bin Wang; Yan-Ru Zhang; Xue Li; Nuerkaimaier Mulati; Ying-Xin Li; Lu Wu; Yu Long; Jun-Min He (Plant Science, 2025)

Exploring trench of clay with submerged moving circular vertical jet: Numerical analysis - Zeren Fan; Long Yu; Yunrui Han; Qing Yang (Ocean Engineering, 2025)

Effects on extracellular and intracellular antibiotic resistance genes and their potential hosts in activated sludge under stress of high concentrations of antibiotics - Xiao-Yan Fan; Meng-Yuan Zheng; Xing Li; Shen-Bin Cao; Yue Niu; Shi-Long Zhou (Journal of Water Process Engineering, 2025)

Mechanistic insights into phenol-ammonia synergy for optimizing phenolic porous carbon synthesis and pore formation - Xianjie Wang; Long Yan; Yufei Wang; Shuaige Shi; Jian Li; Xiaoyong Fan (Fuel, 2025)

Preparation of waste toner-derived magnetic adsorbent for analysis of lead in aqueous and oil-based foods - Long Qin; Yue Wang; Tingjiang Wan; Weian Fan; Han Jiang; Bin Zhang; Yiwei Wu; Xiaoxiao Yu; Chuan Wang (Food Chemistry, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Mantle wedge serpentinites as a potential nitrogen reservoir regulating subduction-zone nitrogen recycling and mantle heterogeneity - Kan Li; Kai Wu; Amber Jie Yu; Yi-Fan Du; Weidong Sun; Long Li (Earth and Planetary Science Letters, 2025)

Synergistic toxicity of cadmium and triadimefon on the microbiota and health of Rana dybowskii tadpoles - Xiao-yun Han; Peng Guo; Qiu-ru Fan; Qing-bo Zhou; Ming-da Xu; Xin-zhou Long; Li-yong Cui; Qing Tong (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Electrocatalytic reduction of nitrate to ammonia on CoMoO4 microspheres: A comparative study with Co3O4 - Yibo Xu; Long Cao; Hele Hua; Rui Li; Yunfang Wang; Jianxin Liu; Yawen Wang; Caimei Fan (Chemical Engineering Journal, 2025)

Heterogenic membrane-coated nanoparticles for targeted immunotherapy against osteosarcoma via p53-mediated ferroptosis and mTOR inhibition - Ting Lei; Zichao Jiang; Jiangyu Nan; Han Fan; Junxiao Yang; Yiyi Wang; Long Hua; Hu Qian; Yihe Hu (Chemical Engineering Journal, 2025)

Salt-template induced multistage porous graphite foam incorporating low melting point alloy for thermal management of high-power devices - Xing Guo; Jinxing Liu; Long Gao; Yajuan Zhong; Sufang Yang; Yaxiong Liu; Yuyuan Fan; Xiaodong Tian; Zechao Tao; Xiaoyue Guo; Xiaoqing Gao; Xiaohui Guo; et al. (Chemical Engineering Journal, 2025)

Discovery, optimization and biological evaluation of chromone derivatives as novel BRD4 inhibitors - Zhao-Tong Jia; You Li; Wei Shi; Jian-Qiang Qian; Ya-Yu Xu; Hai-Ran Fan; Xiao-Long Hu; Hao Wang (Medicinal Chemistry Research, 2025)

The protective effect of wearing hearing protection devices in noise-induced hearing loss and its potential influencing factors in the Chinese adult population - Linyan Shu; Zhixing Fan; Jia Tang; Guoyong Xu; Jianyu Guo; Taihua Long; Junle Wu; Minghui Xiao; Shijie Hu; Bin Xiao (Science of The Total Environment, 2025)

How to restore ecology and reduce carbon emissions in abandoned mines in a safe and environmentally friendly way？ - Wei Zhao; Jingwei Huang; Kai Wang; Peifeng Hu; Yue Huang; Chengxin Li; Yuxuan Zhu; Long Fan; Lijun Zhao (Process Safety and Environmental Protection, 2025)

Calcium and iron isotope fractionation during felsic magma differentiation - Qiu-Yun Guan; Jin-Xiang Li; Ya-Li Sun; Shi-Lei Tang; Noreen J. Evans; Zhao-Feng Zhang; Li-Yun Zhang; Fu-Long Cai; Wei-Ming Fan; Lin Ding (Lithos, 2025)

U-Pb ages of apatite, sulfur isotopes of sulfides and possible origin of the Dashui hematite-rich, sulfide-deficient gold deposit in the West Qinling orogen, Central China - Liang Fan; Jia Chang; Jian-Wei Li; Ji-Xiang Sui; Shi-Guang Du; Long-Hui Huang (Journal of Asian Earth Sciences, 2025)

Toward economy hydrogenation: Highly efficient hydrodeoxygenation of guaiacol to cyclohexanol over a CoNi-NC catalyst - Jing Chen; Zongyan Ma; Jiaheng Qin; Ming Chen; Linkun Dong; Weiwen Mao; Tongtong Fan; Yu Long; Jiantai Ma (Fuel, 2025)

Relationship between the molecular structure of soluble organic matter in a subbituminous coal and the electrochemical properties of prepared supercapacitor - Hao Xu; Yu-Qian Zhang; Xue-Liang Yao; Chen Wang; Qi Zhang; Bo Long; Chen-Chen Guo; Xing Fan (Fuel, 2025)

Microwaving plus enzymatic pretreatment of safflower seeds increases the phenolic content and oxidative stability of extracted oil - Zhi Qin; Yun-Long Chang; Zi-Cheng Yang; Wei Fan; Zi-Meng Chen; Ling-Biao Gu; Zhao Qin; Hua-Min Liu; Xin-Liang Zhu; Yu-Xiang Ma (Food Chemistry, 2025)

Triptolide exposure triggers ovarian inflammation by activating cGAS-STING pathway and decrease oocyte quality in mouse - Si-Yao Cheng; Yi-Fan Yang; Ya-Long Wang; Zhao-Ping Yue; Yan-Zhu Chen; Wen-Ke Wang; Zhi-Ran Xu; Lin-Feng Li; Hao Shen; Zhi-Min Qi; Chang-Long Xu; Yu Liu (Food and Chemical Toxicology, 2025)

Impact of carbon/nitrogen ratio on sequencing batch biofilm reactors initiated with different seed sludges for treating actual mariculture effluents - Xiao-Yan Fan; Shi-Long Zhou; Yanling Yang; Shen-Bin Cao; Yue Niu; Meng-Yuan Zheng; Jun-Ru Zhao (Bioresource Technology, 2025)

Enhanced visual detection of litchi fruit in complex natural environments based on unmanned aerial vehicle (UAV) remote sensing - Changjiang Liang; Juntao Liang; Weiguang Yang; Weiyi Ge; Jing Zhao; Zhaorong Li; Shudai Bai; Jiawen Fan; Yubin Lan; Yongbing Long (Precision Agriculture, 2025)

An analysis about the linkage between precipitation and atmosphere stratification at climate scale - Jiawei Hao; Dian Yuan; Xuehan Zhao; Hao Long; Qidong Ling; Er Lu; Juqing Tu; Chenchen Fan (Climate Dynamics, 2025)

Molecular characteristics of three complete genome sequences of apple rubbery wood virus 1 isolates from apple trees in China - Cheng-long Liu; Zun-Ping Zhang; Xu-Dong Fan; Fang Ren; Guo-Jun Hu; Ya-Feng Dong (Journal of Plant Pathology, 2025)

The independent and combined associations of nocturnal sleep duration, sleep midpoint, and sleep onset latency with global cognitive function in older Chinese adults - Xueyao Wu; Jiaqiang Liao; Xin Chen; Jinyu Xiao; Xinyang Dui; Tianpei Ma; Lin Hu; Xunying Zhao; Qian Bu; Mengyu Fan; Tao Zhang; Lu Long; et al. (GeroScience, 2025)

Comparative analysis of carotenoids, fatty acids, minerals, tastes, and odor in the skin of wild versus farmed large yellow croaker: Superior nutritional benefits with elevated heavy metal risks - Jia-Lang Zheng; Tao Zhu; Wang-Yang Jin; Qing-Hao Zhan; Fa-Guo Wan; Yong-Long Chen; Tian-Hong Chen; Shun Chen; Qing-Ling Zhu; Shuang Chen; Wei-Ye Li; Yi-Fan Liu; et al. (Aquaculture, 2025)

The miR172a–SNB module orchestrates both induced and adult-plant resistance to multiple diseases via MYB30-mediated lignin accumulation in rice - He Wang; Zhe-Xu Wang; Hong-Yuan Tian; Yu-Long Zeng; Hao Xue; Wan-Ting Mao; Lu-Yue Zhang; Jun-Ni Chen; Xiang Lu; Yong Zhu; Guo-Bang Li; Zhi-Xue Zhao; et al. (Molecular Plant, 2025)

Parametric study on the methanol/diesel JCCI mode with dual-direct injection system in a light-duty engine - Bo Li; Wei Tan; Yunpeng Wei; Liyun Fan; Yang Wang; Xianyin Leng; Ge Xiao; Wuqiang Long (Fuel, 2025)

Influence of synergistic/competitive interactions of nonionic emulsifiers and proteins on the foam stability of whole egg liquids: Based on air-water and oil-water dual interface perspectives - Yuanyuan Zhang; Haobo Jin; Yanli Wang; Erjiao Li; Sadaqat Ali; Xiang Fan; Yanbin Song; Yunxin Sun; Long Sheng (Food Hydrocolloids, 2025)

Ingenious microfluidic-microwave integrated biosensor for cell sorting and concentration detection of mixed white blood cells and yeasts solution - Yuan-Bo Li; Yan-Xiong Wang; Sen Yang; Qian-Long Chen; Zhong-Hao Li; Jun-Ge Liang; Qi-Gao Fan; Yan-Feng Jiang; Xiaoman Zhou; Tian Qiang (Chemical Engineering Journal, 2025)

High-Performance wave loss capability by Constructing Well-Defined hierarchical aerogel framework with strongly coupled Carbon/CeO2 interface - Yun-Xia Bai; Da-Peng Liu; Lu Zhou; Bo Cai; Pei-Yan Zhao; Hua-Long Peng; Yu Zhang; Qi-Fan Xuan; Wen-Hao Liang; Zhi-Ling Hou; Guang-Sheng Wang (Chemical Engineering Journal, 2025)

Design, integration, and field evaluation of a selective harvesting robot for broccoli - Shuo Kang; Sifang Long; Dongfang Li; Jiali Fan; Dongdong Du; Jun Wang (Computers and Electronics in Agriculture, 2024)

Assessing and improving the high uncertainty of global gross primary productivity products based on deep learning under extreme climatic conditions - Long Qian; Xingjiao Yu; Zhitao Zhang; Lifeng Wu; Junliang Fan; Youzhen Xiang; Junying Chen; Xiaogang Liu (Science of The Total Environment, 2024)

QSAR models for predicting key hormesis parameters of quinolone antibiotic mixtures on Vibrio qinghaiensis sp.-Q67 - Ling-Yun Mo; Si-Tong Long; Xia-Chang-Li Xu; Li-Tang Qin; Fan Jiang (Science of The Total Environment, 2024)

Enhanced rare earth alkali cake washing and alkaline wastewater disposal via mineral phase transformation and ultrasound - Jianfei Li; Zhenhui Long; Yanglei Geng; Ruifeng Ma; Xiaowei Zhang; Yanhong Hu; Jinxiu Wu; Feng Guo; Wenbin Xin; Xiaoyan Hao; Zhicheng Dong; Fan Xiufeng (Minerals Engineering, 2024)

Free-radical triggered formation of dioxins from 2-chlorophenol pyrolysis investigated by synchrotron radiation photoionization mass spectrometry - Ming-Gao Xu; Chen Huang; Yi-Fan Zhang; Jia-Bin Huang; Long Zhao; Wenchao Lu; Yang Pan; Jiu-Zhong Yang; Feng Zhang; Zhan-Jun Cheng (Journal of Hazardous Materials, 2024)

Machine learning-assisted optimization of 5-hydroxymethylfurfural yield from straw by microwave hydrothermal conversion - Lvhan Zhu; Lijiao Fan; Yanhong Wang; Liqun Xiao; Dongsheng Shen; Yuyang Long (Journal of Cleaner Production, 2024)

Machine learning for enhancing prediction of biogas production and building a VFA/ALK soft sensor in full-scale dry anaerobic digestion of kitchen food waste - Jinlin Zou; Fan Lü; Long Chen; Hua Zhang; Pinjing He (Journal of Environmental Management, 2024)

Comparative study of pre- and post-Cu modified calcium-based desulfurizers: Experimental and theoretical insights into adsorption vs. catalysis - Xiaodong Liao; Yulu Liu; Zongshe Liu; Qisong Liu; Wanglai Cen; Rui Fan; Long Li; Jing Shao; Yuxiao Shi (Journal of Environmental Chemical Engineering, 2024)

An experimental study on monitoring and early warning of spontaneous coal combustion fires using CPM - Liyang Gao; Bo Tan; Long Fan; David Cliff; Jiliang Huang; Haiyan Wang; Biao Kong (Journal of Environmental Chemical Engineering, 2024)

Geochemical behavior of riverine magnesium isotopes in the Yarlung Tsangpo River Basin, southern Tibetan Plateau - Ya-Ni Yan; Jun-Wen Zhang; Jie Wu; Bai-Ling Fan; Dong Zhang; Long-Fei Gou; Qing-You Liu; Zhi-Qi Zhao (Global and Planetary Change, 2024)

Development of multifunctional fruit packaging by incorporating starch aldehyde-quercetin conjugate into chitosan coating films - Yufeng Sun; Yang Ju; Lili Wang; Ran Tao; Long Li; Bei Fan; Fengzhong Wang (Food Hydrocolloids, 2024)

Association of PM2.5 exposure in early pregnancy and maternal liver function: A retrospective cohort study in Shenzhen, China - Zhijian Chen; Minting Zhu; Weigui Ni; Bo Wu; Tao Liu; Bingyi Lin; Lijuan Lai; Yi Jing; Long Jiang; Zhongai Ouyang; Jianxiong Hu; Haoqu Zheng; et al. (Environmental Research, 2024)

Per- and polyfluoroalkyl substances (PFAS) at low concentration improve coagulation efficiency but induce higher membrane fouling in drinking water treatment - Qianyi Chen; Junling Wang; Zhaoyang Su; Long Tian; Fan Huang; Ting Liu; Nigel Graham; Guibai Li; Wenzheng Yu (Environmental Pollution, 2024)

Exposure to greenspaces sourced soils improves mice gut microbiota - Gang-Long Zhou; Yan Xie; Yi-Dan Zhang; Lu Wang; Yu-Ting Xie; Hui-Ling Qiu; Xiao-Qi Zhu; Jian-Cheng Jiang; Yan Yang; Mingdeng Xiang; Guang-Hui Dong; Yuanzhong Zhou; et al. (Environmental Pollution, 2024)

Machine-learning downscaling of GPM satellite precipitation products in mountainous regions: A case study in Chongqing - Yushi Gan; Yuechen Li; Lihong Wang; Long Zhao; Lei Fan; Haichao Xu; Zhe Yin (Atmospheric Research, 2024)

The Effect of Platelet Fibrin Plasma (PFP) on Postoperative Refractory Wounds: Physiologically Concentrated Platelet Plasma in Wound Repair - Lu Fan; Ying Zhang; Xiankun Yin; Silu Chen; Pin Wu; Tianru Huyan; Ziyang Wang; Qun Ma; Hua Zhang; Wenhui Wang; Chunyan Gu; Lu Tie; et al. (Tissue Engineering and Regenerative Medicine, 2024)

Pancreatitis affects gut microbiota via metabolites and inflammatory cytokines: an exploratory two-step Mendelian randomisation study - Yi-Fan Qiu; Jun Ye; Jin-Jin Xie; Xiao-Tong Mao; Yi-Long Liu; Qian Fang; Yang-Yang Qian; Wen-Bin Zou; Yu Cao; Zhuan Liao (Molecular Genetics and Genomics, 2024)
Previous studies have observed relationships between pancreatitis and gut microbiota; however, specific changes in gut microbiota abundance and underlying mechanisms in pancreatitis remain unknown. Metabolites are important for gut microbiota to fulfil their biological functions, and changes in the metabolic and immune environments are closely linked to changes in microbiota abundance. We aimed to clarify the mechanisms of gut–pancreas interactions and explore the possible role of metabolites and the immune system. To this end, we conducted two-sample Mendelian randomisation (MR) analysis to evaluate the casual links between four different types of pancreatitis and gut microbiota, metabolites, and inflammatory cytokines. A two-step MR analysis was conducted to further evaluate the probable mediating pathways involving metabolites and inflammatory cytokines in the causal relationship between pancreatitis and gut microbiota. In total, six potential mediators were identified in the causal relationship between pancreatitis and gut microbiota. Nineteen species of gut microbiota and seven inflammatory cytokines were genetically associated with the four types of pancreatitis. Metabolites involved in glucose and amino acid metabolisms were genetically associated with chronic pancreatitis, and those involved in lipid metabolism were genetically associated with acute pancreatitis. Our study identified alterations in the gut microbiota, metabolites, and inflammatory cytokines in pancreatitis at the genetic level and found six potential mediators of the pancreas–gut axis, which may provide insights into the precise diagnosis of pancreatitis and treatment interventions for gut microbiota to prevent the exacerbation of pancreatitis. Future studies could elucidate the mechanism underlying the association between pancreatitis and the gut microbiota.

MEIKIN expression and its C-terminal phosphorylation by PLK1 is closely related the metaphase–anaphase transition by affecting cyclin B1 and Securin stabilization in meiotic oocyte - Li-Hua Fan; Shu-Tao Qi; Zhen-Bo Wang; Ying-Chun Ouyang; Wen-Long Lei; Yue Wang; Ang Li; Feng Wang; Jian Li; Li Li; Yuan-Yuan Li; Yi Hou; et al. (Histochemistry and Cell Biology, 2024)

Symbiotrophs dominate rhizosphere soil fungal community stability of the Cathaya argyrophylla - Zhibo Zhou; Peng Xie; Kerui Huang; Ping Mo; Aihua Deng; Shaogang Fan; Binbin Long; Yun Wang (Applied Soil Ecology, 2024)

The determining regions, specific genes and markers of sex in Pyropia haitanensis (Bangiales, Rhodophyta) - Long-chen Tang; Hong-chang Ding; Ye-fan Qiu; Xing-hong Yan (Algal Research, 2024)

Description of Nesterenkonia aerolata sp. nov., an actinobacterium isolated from air of manufacturing shop in a pharmaceutical factory - Ming-Hui Song; Wen-Long Ma; Ning Zhang; Wei He; Hong-Chuan Wang; Shuang Wang; Yi-Ling Fan; Dao-Feng Zhang (Antonie van Leeuwenhoek, 2024)

Navigability of Liquefied Natural Gas Carriers Along the Northern Sea Route - Long Ma; Sihan Qian; Haihui Dong; Jiemin Fan; Jin Xu; Liang Cao; Shuai Xu; Xiaowen Li; Chengcheng Cai; Yuanyuan Huang; Min Cheng (Journal of Marine Science and Engineering, 2024)
As Arctic sea ice continues to melt and global demand for clean energy rises, Russia’s Liquefied Natural Gas (LNG) exports via the Northern Sea Route (NSR) are rapidly increasing. To ensure the operational safety of LNG carriers and safeguard the economic interests of stakeholders, including shipowners, a thorough assessment of the navigability of various ice-class LNG carriers along this route is essential. This study collected Arctic ice condition data from 2014 to 2023 and applied the Polar Operational Limit Assessment Risk Indexing System (POLARIS) methodology to calculate the Risk Index Outcome (RIO) for LNG carriers with No Ice Class, Arc4, and Arc7 ice classifications in Arctic waters. A navigability threshold of 95% RIO ≥ 0 was established to define navigable windows, and critical waters were identified where sections of the route remain in hazardous or risky conditions year-round. The results indicate that for No Ice Class vessels, Arc4 vessels, and Arc7 vessels, the navigable windows for westbound Route 1 and Route 2 under light, normal, and heavy ice conditions range from 70 to 133 days, 70 to 365 days, and 70 to 365 days, respectively, while for eastbound Route 3, the navigable windows range from 0 to 84 days, 0 to 238 days, and 7 to 365 days, respectively. The critical waters affecting the navigability of No Ice Class vessels, Arc4 vessels, and Arc7 vessels are primarily located in the Kara Sea, Laptev Sea and East Siberian Sea. This study, using the POLARIS methodology, provides valuable insights into the navigability of LNG carriers with different ice classes along the NSR, supporting the development and utilization of Arctic energy and shipping routes while offering decision-making support for stakeholders involved in Arctic maritime operations.

Preparation of hydrophilic PVDF membranes through in situ assembly of phytate-polyethyleneimine-Fe3+ for efficient separation of herbal volatile oil from oily water - Wenling Fan; Jiali Wu; Long Sun; Meiqi Gao; Xiaotong Zhang (Environmental Science and Pollution Research, 2024)

An efficient Meta-VSW method for ship behaviors recognition and application - Zhiyuan Cai; Qidong Fan; Lecheng Li; Long Yu; Congbo Li (Ocean Engineering, 2024)

Enhanced hydrogen generation from ammonia borane hydrolysis over nitrogen-modified urchin-like TiO2-anchored Rh nanoparticles: Active site and water dissociation regulating - Shaoxian Song; Meng Yuan; Guangyin Fan; Yan Long (Fuel, 2024)

Accumulated inflammation and fibrosis participate in atrazine induced ovary toxicity in mice - Yi-Fan Yang; Si-Yao Cheng; Ya-Long Wang; Zhao-Ping Yue; Yu-Xi Yu; Yan-Zhu Chen; Wen-Ke Wang; Zhi-Ran Xu; Zhong-Quan Qi; Yu Liu (Environmental Pollution, 2024)

Introducing electron-rich thiophene bridges in hot exciton emitter for efficient non-doped near-infrared OLEDs with low turn-on voltages - Ruming Jiang; Zhangshan Liu; Yuanyuan Han; Jiawei Long; Ting Guo; Xia Lan; Mingguang Yu; Ting Fan; Haijun Ma; Yen Wei; Ben Zhong Tang; Zujin Zhao (Chemical Engineering Journal, 2024)

Porous liquids based on ZIF-67@ZIF-8 through the strategy of interface layer reconstruction for CO2 selective sorption - Jiadi Li; Yangyang Xin; Zheng Dong; Baolu Cui; Zhiye Du; Jingwen Wang; Libing Qian; Shuangshuang Long; Zicheng Wei; Wendi Fan; Jinwen Fan; Yunpan Ying; et al. (Chemical Engineering Journal, 2024)

Recent research progress on recycling metallurgical waste slag and strengthening directional recovery of impurity elements by applied electric field - Wen-zhi Xia; Yun Zhou; Guang-da Bao; Zhen Hou; Shao-long Chu; Ping-fan Ren; Zhi-you Liao; Hai-chuan Wang (Chemical Engineering Journal, 2024)

Icariin-loaded selenium-gold multi-shell nanocomposites with NIR-II response release to relieve post-damaged bone microenvironment for osteoporosis synergy therapy - Yuqing Li; Xiaotong Feng; Yuwei Li; Qile Song; Naling Long; Xiaoting Fu; Yifan Wang; Yingjiao He; Huiying Yan; Cong Li; Lina Feng; Cundong Fan; et al. (Chemical Engineering Journal, 2024)

Nanofiber aerogel with layered array with structure coupled photothermal/magnetothermal effect for continuous seawater desalination - Zichen Yu; Tingting Fan; Yang Liu; Bowen Yang; Luyao Wang; Fang Yin; Yuan Gao; Yun-Ze Long (Chemical Engineering Journal, 2024)

Microtopography and hydrological regulation alter CO2 and CH4 fluxes in urban wetlands: Evidence from the Pearl River Delta, China - Kangting Ouyang; Zhihui Wang; Zhongyu Sun; Guangqing Huang; Long Yang; Meijie Liu; Cunxiang Fan; Zhibin Lin (CATENA, 2024)

Numerical analysis of turbulent mixed convection heat transfer of molten salt in an inclined cooling tube - Wangsheng Tian; Tianji Peng; Yanze Tang; Xukai Fan; Yifeng Wang; Haiyan Meng; Deliang Fan; Xudong Liu; Long Gu (Annals of Nuclear Energy, 2024)

Effect of CO2 Thickeners on CH4-CO2 Replacement in Hydrate-Bearing Sediment - Xuebing Zhou; Jiahong Zhou; Zhen Long; Huiyun Wen; Shuanshi Fan; Deqing Liang (Journal of Marine Science and Engineering, 2024)
CO2 fracturing is known as the best solution to improve the efficiency of the CO2 replacement of natural gas hydrates, but the effect of CO2 thickeners on CH4-CO2 replacement are barely noticed. In this work, the effect of four kinds of CO2 thickener—including DL-Lactic acid, polyvinyl acetate, ethyl trifluoroacetate and octamethyl trisiloxane—on the CH4-CO2 replacement in quartz sand was measured thermodynamically and kinetically. The results show that the majority of the CO2 thickeners had no effect on the equilibria of the CH4 and CO2 hydrates, except for DL-Lactic acid, where the temperature depression caused by the addition of 5.5 wt% DL-Lactic acid was about 0.52 and 0.48 K for the CH4 and CO2 hydrates, respectively. In the kinetic measurements, the CH4-CO2 replacement was promoted via the addition of the CO2 thickeners, except DL-Lactic acid. The CO2 thickeners were suggested to strengthen the CH4-CO2 replacement by enhancing the gas exchange in the pore space. Octamethyl trisiloxane, which could promote CH4 recovery and CO2 capture at a low concentration, was suggested to be an ideal CO2 thickener for CH4-CO2 replacement.

Comparative study on the quality of wild and ecologically farmed large yellow croaker through on-site synchronous sampling from the Nanji Archipelago in the East China Sea - Jia-Lang Zheng; Yong-Long Chen; Fa-Guo Wan; Qing-Hao Zhan; Tian-Hong Chen; Shun Chen; Qing-Ling Zhu; Li-Hua Jiang; Wei-Ye Li; Wen-Tao Ye; Yi-Fan Liu; Wei-Hua Song; et al. (Aquaculture, 2024)

Reconstructing high-resolution gridded precipitation data in the southwest China highland canyon area using an improved (MGWR) downscaling method - Lihong Wang; Yuechen Li; Yushi Gan; Long Zhao; Lei Fan; Wei Qin; Lin Ding (Science of The Total Environment, 2024)

Will greenhouse gas emissions increase with mining depth in coal mines? An analysis of gas occurrence under varying in-situ stress conditions - Wei Zhao; Dan Zhao; Kai Wang; Long Fan; Zhihu Zhao; Huzi Dong; Longyong Shu (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

New data on Silurian (Llandovery) sinacanthids from Wuhan, South China and their biostratigraphic and paleobiogeographic implications - Yi-Long Liu; Jia-Yi Yin; Ruo-Ying Fan; Rui-Wen Zong; Yi-Ming Gong (Palaeoworld, 2024)

Fraction-dependent variations in cooling efficiency of urban trees across global cities - Wenfeng Zhan; Chunli Wang; Shasha Wang; Long Li; Yingying Ji; Huilin Du; Fan Huang; Sida Jiang; Zihan Liu; Huyan Fu (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

A novel preparation strategy for an oil-soluble catalyst in slurry phase hydrocracking: Synergistic effect and electronic regulation of Fe on MoS2 - Wenkai Wei; Huandi Hou; Yi Zhao; Xi Fan; Lei Shi; Yuxin Yan; Ting Wang; Jun Long (Fuel, 2024)

Exploration of hydrogen-rich gas evolution mechanism during vitrinite pyrolysis: A combined TG-MS and ReaxFF study - Yuan-Yuan Jiang; Jie-Ping Wang; Jin-Xiao Dou; Rui Guo; Li-Hua Fan; Guang-Yue Li; Ying-Hua Liang; Jiang-Long Yu (Fuel, 2024)

Suppressed testicular macrophage M1 polarization by HDAC5 enforces insensitivity to LPS-elicited blood-testis barrier damage - Hao Li; Yi-Fan Hu; Xin-Run Wang; Kong-Wen Ouyang; Hua Wang; Kai-Wen Wang; Wei Chang; Jin Zhang; Zhi Yuan; Yong-Wei Xiong; Hua-Long Zhu; Lan Yang; et al. (Food and Chemical Toxicology, 2024)

DPA-Zn enables targeting and bypassing endosomal trapping delivery of a genome-editing system into cancer cells via phosphatidylserine-mediated endocytic pathway - Qi Shao; Cai-Liang Shen; Wei You; Xuan Nie; Wei-Qiang Huang; Fan Gao; Xiao-Hong Zhou; Hai-Li Wang; Long-Hai Wang; Guang Chen; Chang-Hui Wang; Chun-Yan Hong; et al. (Chemical Engineering Journal, 2024)

The positive contributions of steel slag in reducing carbon dioxide emissions in the steel industry: Waste heat recovery, carbon sequestration, and resource utilization - Chunlong Fan; Rufei Wei; Tong Cheng; Rong Sun; Hao Zhang; Hongming Long (Chemical Engineering Journal, 2024)

Deep oxidation of CH2Cl2 over Mo-doped CoAl2O4 spinel oxides: Unravelling the promoting roles of Brønsted acidity and H2O - Yu-Kun Ma; Long-Ren Ouyang; Yi-Fan Yao; Zhi-Feng Dai; Yu Wang; Ji-Qing Lu (Chemical Engineering Journal, 2024)

Magnetic conjugated microporous polymer for rapid extraction and sensitive analysis of environmental endocrine disruptors in environmental waters and dairy products - Hai-Long Jiang; Fu-Shuai Kang; Ye-Fei Fan; Xia Wang; Yun-Liang Lin; Lu Liu; Wei Liu; Yan-Fang Zhao; Ru-Song Zhao (Analytica Chimica Acta, 2024)

Experimental and model investigation on hydro-mechanical behaviour of sandy mudstone - Yanjie Zhang; Mingtao Hu; Weiya Xu; Huanling Wang; Lulu Fan; Rubin Wang; Long Yan; Wei Huang; Tao Zhang (European Journal of Environmental and Civil Engineering, 2024)

Comparative study on the morphological characteristics, nutritional quality, and tastes of large yellow croaker from five cage culture areas: Relay farming improved fish quality - Jia-Lang Zheng; Fa-Guo Wan; Yong-Long Chen; Li-Hua Jiang; Qing-Hao Zhan; Tian-Hong Chen; Shun Chen; Qing-Lin Zhu; Wei-Ye Li; Yi-Fan Liu; Wei-Hua Song; Xiao-Jun Yan (Aquaculture, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Numerical investigation on the vertical jet fire impinging on the horizontal cylindrical obstacle in a ship engine room: Characteristics and new prediction models of flame length - Shaogang Zhang; Yongqiang Fan; Long Shi; Jiahao Liu; Jianghong Liu; Jinhui Wang; Beihua Cong (Ocean Engineering, 2024)

A gap filling method for daily evapotranspiration of global flux data sets based on deep learning - Long Qian; Lifeng Wu; Zhitao Zhang; Junliang Fan; Xingjiao Yu; Xiaogang Liu; Qiliang Yang; Yaokui Cui (Journal of Hydrology, 2024)

Improving high uncertainty of evapotranspiration products under extreme climatic conditions based on deep learning and ERA5 reanalysis data - Long Qian; Xingjiao Yu; Lifeng Wu; Zhitao Zhang; Shuailong Fan; Ruiqi Du; Xiaogang Liu; Qiliang Yang; Rangjian Qiu; Yaokui Cui; Guomin Huang; Yicheng Wang (Journal of Hydrology, 2024)

Enrichment of cobalt at Baijian skarn Fe-Co deposit in the Handan-Xingtai region, North China Craton: Insights from mineral trace elements and pyrite sulfur isotopes - Xian Liang; Fang-Yue Wang; Ju-Quan Zhang; Long Zhang; Tao-Fa Zhou; Yu Fan; Chao Qin; Jun-Wu Zhang (Journal of Asian Earth Sciences, 2024)

Application of opposing coils transient electromagnetic method in urban area with metal interference - Juan Fan; Enke Hou; Dewu Jin; Zhenzhu Xi; Xia Long; Sheng Zhou; Shenghui Nan; Yingfeng Liu; Kang Guo; Dianyan Ning (Journal of Applied Geophysics, 2024)

Archean atmospheric sulfur stocked in the Cretaceous gold deposits - Yong-Wen Zhang; Hong-Rui Fan; Long Li; Qiu-Li Li; Hong-Wei Peng; Ya-Chun Cai; Peng Jiang; Kai Feng (Geochemistry, 2024)

Enhanced anti-biochemical fouling properties of the polyacrylonitrile membranes assisted by the d-amino acid surface-modified halloysite nanotubes - Qiao Liu; Nong Xu; Kaiming Li; Qing Wang; Long Fan; Peng Zang; Yinhua Wan (Chemical Engineering Journal, 2024)

Rational design of robust Cu@Ag core-shell nanowires for wearable electronics applications - Yu-Chieh Kuo; Jiajun Fan; Lingqing Zong; Fandi Chen; Ziheng Feng; Chao Liu; Tao Wan; Zi Gu; Long Hu; Peiyuan Guan; Chun-Ho Lin; Mengyao Li; et al. (Chemical Engineering Journal, 2024)

Magnesium isotope fractionation during magmatic differentiation in the lower continental crust - Ying Wei; Xiao-Long Huang; Qiang Ma; Fan Yang; Peng-Li He (Chemical Geology, 2024)

Autonomous Underwater Vehicle Path Planning Based on Improved Salp Swarm Algorithm - Xuan Guo; Dongming Zhao; Tingting Fan; Fei Long; Caihua Fang; Yang Long (Journal of Marine Science and Engineering, 2024)
Aiming at the problem of path planning for autonomous underwater vehicle (AUV) to cope with the influence of obstacles and eddies in complex marine environments, a path planning method based on an improved salp swarm algorithm (ISSA) is proposed. Firstly, the motion model of the AUV and eddy current model are constructed, including the relationship between position, velocity, attitude, and control inputs. Secondly, the improved SSA is proposed, which introduces the Levy flight strategy to enhance the algorithm’s optimization seeking ability and adds a nonlinear convergence factor to enhance the convergence ability of the algorithm. The stability and robustness of the improved algorithm are verified by test functions. Finally, the ISSA is applied to AUV path planning, which optimizes the AUV travel distance, improves the search efficiency and accuracy, and avoids the local optimum of the algorithm. The ISSA enhances the adaptive ability and robustness of the algorithm by introducing a dynamic adjustment strategy and feedback mechanism. Experimental verification is carried out using a simulated marine environment. The results show that the ISSA is better than the traditional algorithm in terms of path length as well as algorithm stability, and can effectively improve the navigation performance of AUV.

Effects of three different protein levels on the growth, gonad development, and physiological biochemistry of female Pengze crucian carp (Carassius auratus var. Pengze) broodstock - Jun Xiao; Fan Long; Liyun Ding; Yuan Yao; Weihua Wu; Yilong Fu; Wenjing Chen (Frontiers in Marine Science, 2024)
A 56-days feeding experiment was conducted to evaluate the effect of dietary protein levels on fish growth, gonad development, and physiological biochemistry of female Pengze crucian carp ( Carassius auratus var. Pengze) broodstock. Three isoenergetic diets were formulated, and the crude protein levels were 26.85%, 35.73% and 44.38%, the lipid levels were 7.39%, 7.92% and 7.91%, respectively. The results showed that the weight gain rate (WGR), the specific growth rate (SGR) and the protein efficiency ratio (PER) of the female Pengze crucian carp broodstock increased significantly and the feed conversion ratio (FCR) decreased significantly when the dietary protein level was 35.73% ( P < 0.05). The WGR, the SGR and the PER were significantly higher in the 35.73% and 44.38% protein groups than in the 26.85% protein group ( P <0.05). Increasing dietary protein levels led to a significant increase in the gonad index and the egg menstrual length of the female Pengze crucian carp broodstock ( P <0.05). The higher protein levels resulted in a significant increase in total amino acids, total essential amino acids, and total nonessential amino acids ( P <0.05). The varying ovaries of each group of total saturated fatty acids, total highly unsaturated fatty acids, and total polyunsaturated fatty acids all increased significantly with increasing protein levels ( P <0.05). Furthermore, the aspartate transaminase (AST), low-density lipoprotein cholesterol (LDLC), and malondialdehyde (MDA) contents in plasma were significantly lower in the 35.73% and 44.38% groups than in the 26.85% group ( P < 0.05). The 35.73% group exhibited the highest plasma superoxide dismutase (SOD) activity,. The plasma vitellogenin (VTG), estradiol 2 (E2), and progesterone (PROG) in plasma of female Pengze crucian carp broodstock were significantly higher in the 35.73% and 44.38% protein groups than in the 26.85% protein group ( P <0.05). The results showed that the addition of an appropriate amount of protein to the feed can significantly improve the growth, gonadal development, and health of female Pengze crucian carp. In this study, the effect of 35.73% protein concentration was better than in the other two groups.

Experimental investigation on the high-temperature corrosion of 12Cr1MoVG boiler steel in waste-to-energy plants: Effects of superheater operating temperature and moisture - Hao Guo; Weidong Fan; Yacheng Liu; Jisheng Long (Process Safety and Environmental Protection, 2024)

Sedimentology, depositional processes, and sequence stratigraphy of deep lacustrine fine-grained sedimentary rocks in the lower Oligocene Xiaganchaigou Formation, Qaidam Basin, Northwestern China - Mingqiu Hou; Zhi Yang; Youliang Feng; Xiaoni Wang; Guohui Long; Kunyu Wu; Hong Zhang; Yuchen Fan; Wenqi Jiang; Qizhao Wei (Marine and Petroleum Geology, 2024)

Response of microbial communities in aquifers with multiple organic solvent contamination: Implications for MNA remedy - Lu Yang; Qiang Chen; Jing Wei; Tingting Fan; Lingya Kong; Tao Long; Shengtian Zhang; Shaopo Deng (Journal of Hazardous Materials, 2024)

Removal of Sb(V) from complex wastewater of Sb(V) and aniline aerofloat using Fe3O4–CeO2 absorbent enhanced by H2O2: Efficiency and mechanism - Xiaohui Wang; Renjian Deng; Chuang Wang; Pei Long; Baolin Hou; Weimin Chen; Fan Chen; Bozhi Ren; Andrew Hursthouse (Journal of Environmental Management, 2024)

Glutamicibacter nicotianae AT6: A new strain for the efficient biodegradation of tilmicosin - Huijuan Li; Hao Zhou; Liling Fan; Long Meng; Yanyun Zhao; Lanmei Zhao; Bo Wang (Journal of Environmental Sciences, 2024)

Tectonic influence on the evolutionary dynamics of deep-water channel systems along the active accretionary prism margin in the Rakhine Basin, Myanmar: A high-resolution 3d seismic analysis - Haozhe Ma; Xiwu Luan; Thanuja D. Raveendrasinghe; Xinyuan Wei; Huarui He; Jianghao Qiao; Long Jin; Guozhang Fan; Yintao Lu (Geomorphology, 2024)

Self-floating and long-term stable Ti3C2TX/polyurethane composite membranes with highly efficient photothermal conversion performances for multiple applications - Ya'nan Zhao; Zongxing Liu; Long Yu; Jiarong Zhang; Fan Wu; Tiantian Lv; Chang Zhao; Guangjian Xing (Desalination, 2024)

Cross-linked g-C3N4 nanofibers enable thermal stable composite membranes for high-performance loose nanofiltration - Wan-Ting Lin; Ping Fu; Wan-Long Li; Yuan-Hui Yu; Zi-Lu Zhang; Hong-Yu Fan; Xiao-Jun Huang; Zhi-Kang Xu; Ling-Shu Wan (Chemical Engineering Journal, 2024)

Total Flavonoids of Aurantii Fructus Immaturus Regulate miR-5100 to Improve Constipation by Targeting Fzd2 to Alleviate Calcium Balance and Autophagy in Interstitial Cells of Cajal - Yong Wen; Yu Zhan; Taiyu Chen; Jun Li; Qing Long; Fan Zheng; Shiyu Tang; Xuegui Tang (Molecular Neurobiology, 2024)

Identification of candidate genes associated with blade length in Pyropia haitanensis based on BSA-seq and RNA-seq analysis - He-Ye Liu; Hong-Chang Ding; Long-Chen Tang; Ye-Fan Qiu; Xing-Hong Yan (Journal of Applied Phycology, 2024)

Macaque Brainnetome Atlas: A multifaceted brain map with parcellation, connection, and histology - Yuheng Lu; Yue Cui; Long Cao; Zhenwei Dong; Luqi Cheng; Wen Wu; Changshuo Wang; Xinyi Liu; Youtong Liu; Baogui Zhang; Deying Li; Bokai Zhao; et al. (Science Bulletin, 2024)

Totaling river discharge of the third pole from satellite imagery - Jie Xu; Lei Wang; Tandong Yao; Deliang Chen; Gang Wang; Zhaowei Jing; Fan Zhang; Yuyang Wang; Xiuping Li; Yinsheng Zhang; Yuanwei Wang; Tian Zeng; et al. (Remote Sensing of Environment, 2024)

Selective hydroconversion of lignin-derived compounds over a Ni/hydroxyapatite - Yong-Hui Feng; Xiang Bai; Xian-Yong Wei; Yierxiati Dilixiati; Li Li; Qian-Qian Kong; Zhuang Li; Zi-Chun Fan; Ji Zhao; Zhi-Min Zong; Jun-Long Wang (Fuel, 2024)

Protein aggregation caused by pasteurization processing affects the foam performance of liquid egg white - Xiang Fan; Qi Wang; Haobo Jin; Yuanyuan Zhang; Yaqin Yang; Zhe Li; Guofeng Jin; Long Sheng (Food Chemistry, 2024)

Development of a low carbon binder system based on metakaolin: Focus on corrosion inhibitor-intercalated layered double hydroxides - Zhenjiang Gu; Jianbo Xiong; Zhihong Fan; Mengzhu Chen; Jiaqi Li; Long Jiang; Haibing Zheng; Weihua Li (Applied Clay Science, 2024)

Thioclava litoralis sp. nov., a novel species of alphaproteobacterium, isolated from surface seawater - Dakun Chen; Huimin Fan; Shaoshuai Tang; Zhen Gan; Yishan Lu; Meng Long (Archives of Microbiology, 2024)

Numerical and Experimental Analysis of Lifting Forces of Fin Stabilizers with Fin–Hull Interaction - Qidong Fan; Long Yu; Xuefeng Wang (Journal of Marine Science and Engineering, 2024)
A fin stabilizer is one of the most effective and frequently used anti-roll devices for maintaining a ship’s operational safety and passengers’ comfort. However, the discrepancy between theoretical hydrofoil-based predictions and the actual dynamic lift force of fin stabilizers due to fin–hull interactions requires more research attention. This study investigates the effect of fin stabilizers on mitigating roll motion through the performance of extensive computational fluid dynamic (CFD) simulations over a range of fin angles and ship speeds. Model tests were carried out to validate the drag and motion results obtained from numerical analyses. The results show that fin stabilizers significantly reduce the roll motion, with the lift coefficient values influenced by the Reynolds number, leading to differences between the theoretical and Reynolds-averaged Navier–Stokes (RANS) calculations. At a high Froude number (Fr), the actual fin lift is about half of the theoretical value. These findings highlight the requirement of selecting an adequate fin area at the predominant ship speeds and ensuring an effective anti-roll effect with fin–hull interaction. This study provides a significant reference for ship design, as well as stabilization system control and optimization.

Occurrence, seasonal variations, and fate of household and personal care chemicals in a wastewater treatment plant with Bacillus bioreactor process - Lin-Hui Zhang; Wen-Long Li; Zi-Feng Zhang; Xi-Ze Min; Ming-Gang Cai; Hang Xiao; Qing Diao; Zhen Qiu; Yi-Fan Li (Chemosphere, 2024)

m6A-methylated Lonp1 drives mitochondrial proteostasis stress to induce testicular pyroptosis upon environmental cadmium exposure - Kong-Wen Ouyang; Tian-Tian Wang; Hua Wang; Ye-Xin Luo; Yi-Fan Hu; Xin-Mei Zheng; Qing Ling; Kai-Wen Wang; Yong-Wei Xiong; Jin Zhang; Wei Chang; Yu-Feng Zhang; et al. (Science of The Total Environment, 2024)

Synthesis optimization and separation mechanism of ZSM-5 zeolite membranes for pervaporation dehydration of organic solvents - Qing Wang; Cheng Qian; Nong Xu; Qiao Liu; Bin Wang; Lingyun Zhang; Long Fan; Rongfei Zhou (Science of The Total Environment, 2024)

Transcriptomic mechanism revealed IbGST4 and IbGST2 genes response to low-temperature stress in sweet potatoes - Wei-Sheng Zhao; Long-Fei Yan; Kang-Di Hu; Zhi-Lin Zhou; Si-Qi Wang; Le-Ying Yan; Fan Hu; Hua Zhang; Gai-Fang Yao (Postharvest Biology and Technology, 2024)

Postharvest biocontrol ability and antagonistic mechanism of Bacillus altitudins h217 against Penicillium digitatum in citrus - Yongqing Lu; Shuqi Liu; Yuqing Wang; Fan Yang; Zhonghuan Tian; Chao-an Long (Postharvest Biology and Technology, 2024)

Two new cytotoxic diterpenoid alkaloids from Delphinium grandiflorum - Ze-dong Nan; Ying Shang; Chao-fan Deng; Yi-dong Zhu; Guo-dong Jiang; Zhen-zhen Wang; Chong-long Li; Xiao-li Ma; Zhi-Bo Jiang (Phytochemistry Letters, 2024)

Evolutionary genomics of climatic adaptation and resilience to climate change in alfalfa - Fan Zhang; Ruicai Long; Zhiyao Ma; Hua Xiao; Xiaodong Xu; Zhongjie Liu; Chunxue Wei; Yiwen Wang; Yanling Peng; Xuanwen Yang; Xiaoya Shi; Shuo Cao; et al. (Molecular Plant, 2024)

Lacustrine shale lithofacies and depositional environment in the paleocene second member of the funing formation, subei basin, China: Insights into shale oil development prospects - Xiaojie Fan; Yangbo Lu; Zhanhong Liu; Yongchao Lu; Jingyu Zhang; Kong Deng; Tao Zhou; Hao Tai; Long Li (Marine and Petroleum Geology, 2024)

Unveiling the transtensional geodynamics of Cenozoic depocenter changes in the Andaman sea: Seismic evidence for the existence of the East Sagaing Fault and the Andaman Basin Central Fault Zone in the Tanintharyi region - Thanuja D. Raveendrasinghe; Xiwu Luan; Jianghao Qiao; Long Jin; Zijie Wang; Aravinda Vikum; Yang Xue; Haozhe Ma; Renchao Yang; Guozhang Fan; Yintao Lu (Marine and Petroleum Geology, 2024)

C–C bond coupling differences between β-O-4 and 4-O-5 ether bonds over hydrophobic mesoporous Ru/MY-O catalysts: from lignin model compounds to polycyclic alkanes - Zhuang Li; Zi-Chun Fan; Xiang Bai; Xian-Yong Wei; Yierxiati. Dilixiati; Qian-Qian Kong; Ji Zhao; Yong-Hui Feng; Jun-Long Wang; Xing Fan; Xiao-Yan He; Hai-Xu Zou; et al. (Fuel, 2024)

Environmentally relevant concentrations of benzophenones exposure disrupt intestinal homeostasis, impair the intestinal barrier, and induce inflammation in mice - Yu-Jia Lin; Hong-Mei Li; Yan-Rong Gao; Ping-Fan Wu; Bin Cheng; Chen-Long Yu; Yu-Xin Sheng; Hai-Ming Xu (Environmental Pollution, 2024)

Printed bioinspired piezoelectric nano-hair for ultrahigh sensitive airflow detection - Kai Li; Fan Du; Junyang Fang; Long Sun; Mingzhen Li; Yexin Wang; Chao Wang; Xiaoying Wang; Jinbang Li; Zhijun Qiao; Dianbo Ruan (Chemical Engineering Journal, 2024)

Ta4C3TX/graphene aerogels with combined photo/electro-thermal conversion performances for multifunctional applications - Zongxing Liu; Jiarong Zhang; Ya'nan Zhao; Fan Wu; Tiantian Lv; Long Yu; Chunna Yu; Chang Zhao; Guangjian Xing (Chemical Engineering Journal, 2024)

Delayed Chronic Acidic Postconditioning Improves Poststroke Motor Functional Recovery and Brain Tissue Repair by Activating Proton-Sensing TDAG8 - Yan-Ying Fan; Yu Li; Xiao-Ying Tian; Ying-Jing Wang; Jing Huo; Bao-Lu Guo; Ru Chen; Cai-Hong Yang; Yan Li; Hui-Feng Zhang; Bao-Long Niu; Ming-Sheng Zhang (Translational Stroke Research, 2024)

Peroxydisulfate activation and versatility of defective Fe3O4@MOF-808 for enhanced carbon and phosphorus recovery from sludge anaerobic fermentation - Long Chen; Xiangyue Zhang; Jianming Zhu; Helin Fan; Zimu Qin; Jun Li; Haijiao Xie; Hongtao Zhu (Water Research, 2024)

Occurrence and fate of pharmaceuticals and personal care products in a wastewater treatment plant with Bacillus bio-reactor treatment - Xi-Ze Min; Zi-Feng Zhang; Xi-Mei Lu; Jia-Cheng Chen; Wan-Li Ma; Li-Yan Liu; Wen-Long Li; Yi-Fan Li; Roland Kallenborn (Science of The Total Environment, 2024)

Aniline antioxidants in road dust, parking lot dust, and green-belt soil in Harbin, a megacity in China: Occurrence, profile, and seasonal variation - Ye Zhang; Jin-Nong Li; Jian-Xin Wang; Jie Hu; Jia-Lin Sun; Yi-Fan Li; Wen-Long Li; Zhong-Hua Tang; Zi-Feng Zhang (Journal of Hazardous Materials, 2024)

Genesis of the Hujiazhuang apatite-rich carbonatite complex in North China and its implication for the REE fertility of the carbonatite system - Long Huang; Xiaochun Li; Jianhui Su; Xi Zeng; Hongrui Fan; Jun Lan; Tingguang Lan; Kuifeng Yang; Fangfang Hu (Journal of Asian Earth Sciences, 2024)

Micro-structure change and crystal-structure modulated of oxygen carriers for chemical looping: Controlling local chemical environment of lattice oxygen - Da Song; Tao Long; Cuiqin Li; Yang Li; Mingyang Fan; Yonghao Lu; Yuchao Zhou; Haitao Chen; Yan Lin; Zhen Huang; Fang He (Fuel, 2024)

A novel ionic-liquid-mediated covalent organic framework as a strong electrophile for high-performance iodine removal - Jie Fu; Jia-Ying Liu; Yue-Ru Zhou; Lei Zhang; Shuang-Long Wang; Song Qin; Maohong Fan; Guo-Hong Tao; Ling He (Chemical Engineering Journal, 2024)

Efficient removal of size-fractionated antibiotic resistance genes (ARGs) in WWTPs secondary effluent by vacuum ultraviolet (VUV) activated potassium peroxymonosulfate (PMS) - Xiao-Yan Fan; Shi-Long Xu; Xing Li; Zhi-Wei Zhou; Yu-Xi Gao; Jun-Ru Zhao; Zhong-Xing Zhang (Chemical Engineering Journal, 2024)

Nitazoxanide protects against experimental ulcerative colitis through improving intestinal barrier and inhibiting inflammation - Hu-Tai-Long Zhu; Jing Luo; Yi Peng; Xiao-Fan Cheng; Shang-Ze Wu; Yin-Di Zhao; Le Chang; Zhi-Jie Sun; De-Li Dong (Chemico-Biological Interactions, 2024)

Morusin inhibits breast cancer-induced osteolysis by decreasing phosphatidylinositol 3-kinase (PI3K)-mTOR signalling - Long Zhang; Weibin Li; Xiaohui Chen; Dongmin Cao; Siyuan You; Fan Shi; Zhengqiong Luo; Hongyu Li; Xiangchen Zeng; Yabin Song; Na Li; Yoshie Akimoto; et al. (Chemico-Biological Interactions, 2024)

Occurrence, distribution, and risk assessment of antibiotics in a typical aquaculture area around the Dongzhai Harbor mangrove forest on Hainan Island - Tuan-Tuan Wang; Shuai Shao; Shi-Di Fan; Wang-Qing Tang; Jiang-Wei Miao; Sai Wang; Xiao-Cong Cao; Chuan Liu; Guang-Guo Ying; Zhong-Bing Chen; Hai-Long Zhou; Xiao-Ping Diao; et al. (Science of The Total Environment, 2024)

Coupling raw material cultivation with nano-hydroxyapatite application to utilize and remediate severely Cd-containing soil - Lijie Jia; Yanli Zhou; Yunxia Su; Ping Zhao; Jingling Zhang; Wei Fan; Shengchao Yang; Guangqiang Long (Process Safety and Environmental Protection, 2024)

Seasonal patterns, fate and ecological risk assessment of pharmaceutical compounds in a wastewater treatment plant with Bacillus bio-reactor treatment - Zi-Feng Zhang; Ying-Ying Fan; Xi-Mei Lu; Xi-ze Min; Wan-Li Ma; Li-Yan Liu; Yi-Fan Li; Wen-Long Li (Journal of Environmental Management, 2024)

The initial magma–fluid evolution of the Laochang porphyry molybdenum deposit in Lancang, Yunnan, SW China: Insights from the in-situ analysis of mica and titanite - Ying-Ying Zhang; Tai-Yi Luo; Yun-Fei Fan; Han-Sheng Long; Yong Yang; Jin-Biao Yang; Fu-Qing Meng (Journal of Asian Earth Sciences, 2024)

Effective catalytic hydroconversion of benzyloxybenzene and oxydibenzene to cyclanes over nickel-supported Y-type zeolite catalyst: Lignite-related model compounds to high-density fuels - Zi-Chun Fan; Zhuang Li; Xiang Bai; Xian-Yong Wei; Yierxiati Dilixiati; Qian-Qian Kong; Ji Zhao; Yong-Hui Feng; Zhi-Min Zong; Jun-Long Wang (Fuel, 2024)

Doping Ni into CoB achieves surface reconstruction to promote efficient electrocatalytic hydrogen evolution reaction - Weijie Fang; Hairong Wang; Zhengrong Zhu; Wencan Qian; Long Qiu; Weikai Fan; Junxin Xiang; Chaojie Yin; Sheng Chen; Jiang Wu; Daolei Wang; Yongfeng Qi (Fuel, 2024)

Bioavailability transition path of phosphorus species during the sewage sludge incineration process - Qianqian Guo; Yanan Wang; Lingqin Zhao; Fan Yu; Zehuang Zhang; Nan Zhou; Long Jiao; Yanjun Hu (Environmental Research, 2024)

Sustainable adhesives for ultra-composites from biomass powder - Boxiang Zhan; Long Zhang; Yongqi Deng; Minghui Fan; Lifeng Yan (Chemical Engineering Journal, 2024)

Ventilation benefit assessment of space organization design for 'L' type inner corridor buildings - Siying Chen; Zhengyu Fan; Long He; Shichao Ma; Jiaping Liu (Building and Environment, 2024)

Contrasting moist heat across local climate zones in heat and non-heat waves: Insights from 29 Chinese metropolises - Sida Jiang; Wenfeng Zhan; Long Li; Chunli Wang; Pan Dong; Shasha Wang; Yingying Ji; Fan Huang; Zihan Liu; Yihan Gao (Building and Environment, 2024)

Corticospinal-specific Shh overexpression in combination with rehabilitation promotes CST axonal sprouting and skilled motor functional recovery after ischemic stroke - Biwu Wu; Lei Yang; Caihua Xi; Haijun Yao; Long Chen; Fengqi Fan; Gang Wu; Zhouying Du; Jin Hu; Shukun Hu (Molecular Neurobiology, 2024)

Metabolomics-based study of chemical compositions in cellulase additives derived from a tobacco-origin Bacillus subtilis and their impact on tobacco sensory attributes - Xiaofeng Chen; Teng Long; Shixin Huang; Yiqiang Chen; Hongliang Lu; Zhenkun Jiang; Cheng Cheng; Jingjing Li; Shanyi Chen; Wei He; Xu Tang; Jianqiang Fan (Archives of Microbiology, 2024)

Species distribution modeling combined with environmental DNA analysis to explore distribution of invasive alien mosquitofish (Gambusia affinis) in China - Xu Han; Jinxiao Chen; Lang Wu; Guo Zhang; Xiaoteng Fan; Tao Yan; Long Zhu; Yongjing Guan; Linjun Zhou; Tingting Hou; Xue Xue; Xiangju Li; et al. (Environmental Science and Pollution Research, 2024)

Phase separation of GRP7 facilitated by FERONIA-mediated phosphorylation inhibits mRNA translation to modulate plant temperature resilience - Fan Xu; Long Wang; Yingbin Li; Junfeng Shi; Dorothee Staiger; Feng Yu (Molecular Plant, 2024)

Recent advances on beneficial management of lithium refinery residue in China - Jihua Zhai; Pan Chen; Jianping Long; Changyi Fan; Zhiyong Chen; Wei Sun (Minerals Engineering, 2024)

Enhanced green remediation and refinement disposal of electrolytic manganese residue using air-jet milling and horizontal-shaking leaching - Fan Wang; Guangcheng Long; John L. Zhou (Journal of Hazardous Materials, 2024)

Sodium caseinate medium promotes the in vitro digestion of starch: An insight into the macromolecular crowding effect - Yu-Long Sun; Yi-Fan Tang; Lei Wang; Mi-Zhuan Li; Zhong-Xiu Chen (Food Chemistry, 2024)

The effect of microgroove pattern modification combined with MOF coating on titanium alloy for the soft tissue integration of percutaneous implants - Baobao Xue; Sheng Miao; Yue Yuan; Wenbo Geng; Donglin Li; Chao Yang; Jiahao Zeng; Kaiyong Cai; Hongbo Wei; Long Bi; Junjun Fan (Chemical Engineering Journal, 2024)

MiR-26b-3p Promotes Intestinal Motility Disorder by Targeting FZD10 to Inhibit GSK3β/β-Catenin Signaling and Induce Enteric Glial Cell Apoptosis - Yu Zhan; Yong Wen; Fan Zheng; Li-juan Du; Tai-yu Chen; Xu-long Shen; Rong Wu; Xue-gui Tang (Molecular Neurobiology, 2024)

Genetic architecture of ecological divergence between Oryza rufipogon and Oryza nivara - Qing‐Lin Meng; Cheng‐Gen Qiang; Ji‐Long Li; Mu‐Fan Geng; Ning‐Ning Ren; Zhe Cai; Mei‐Xia Wang; Zi‐Hui Jiao; Fu‐Min Zhang; Xian‐Jun Song; Song Ge (Molecular Ecology, 2024)
Ecological divergence due to habitat difference plays a prominent role in the formation of new species, but the genetic architecture during ecological speciation and the mechanism underlying phenotypic divergence remain less understood. Two wild ancestors of rice ( Oryza rufipogon and Oryza nivara ) are a progenitor‐derivative species pair with ecological divergence and provide a unique system for studying ecological adaptation/speciation. Here, we constructed a high‐resolution linkage map and conducted a quantitative trait locus (QTL) analysis of 19 phenotypic traits using an F 2 population generated from a cross between the two Oryza species. We identified 113 QTLs associated with interspecific divergence of 16 quantitative traits, with effect sizes ranging from 1.61% to 34.1% in terms of the percentage of variation explained (PVE). The distribution of effect sizes of QTLs followed a negative exponential, suggesting that a few genes of large effect and many genes of small effect were responsible for the phenotypic divergence. We observed 18 clusters of QTLs (QTL hotspots) on 11 chromosomes, significantly more than that expected by chance, demonstrating the importance of coinheritance of loci/genes in ecological adaptation/speciation. Analysis of effect direction and v ‐test statistics revealed that interspecific differentiation of most traits was driven by divergent natural selection, supporting the argument that ecological adaptation/speciation would proceed rapidly under coordinated selection on multiple traits. Our findings provide new insights into the understanding of genetic architecture of ecological adaptation and speciation in plants and help effective manipulation of specific genes or gene cluster in rice breeding.

Stereoselective cardiotoxic effects of metconazole on zebrafish (Danio rerio) based on AGE-RAGE signalling pathway - Minmin Li; Lin Yang; Rui Wang; Lin Li; Yifan Zhang; Long Li; Nuo Jin; Yatao Huang; Zhiqiang Kong; Frédéric Francis; Bei Fan; Fengzhong Wang (Science of The Total Environment, 2024)

Application of roadside air purifiers in urban street canyons: A pilot-scale study in Hong Kong - Xinwei Li; Shuwen Han; Pengge Wang; Han Mei; Zhi Ning; Fan Dong; Long Cui; Yu Huang; Tao Wang; Shao-Yuan Leu; Meng Wang; Shun-cheng Lee (Science of The Total Environment, 2024)

Diisoprenyl-cyclohexene-type meroterpenoids from a mangrove endophytic fungus Aspergillus sp. GXNU-Y65 and their anti-nonalcoholic steatohepatitis activity in AML12 cells - Feng Qin; Li Luo; Yu-Chen Liu; Xiang-Long Bo; Fu-Rong Wu; Fan-Fan Wang; Mei-Jing Tan; You-Quan Wei; Xiao-Bing Dou; Cai Yi Wang; Xi-Shan Huang; Heng-Shan Wang (Phytochemistry, 2024)

Complete genome sequence analysis of Bacillus velezensis A5, a promising biocontrol agent from the Pacific Ocean - Shunhua Ji; Yin Tian; Guangxin Xu; Yiqiang Chen; Jingjing Li; Teng Long; Wei He; Jianqiang Fan; Xixiang Tang (Marine Genomics, 2024)

Unravelling Cenozoic carbonate platform fluid expulsion: Deciphering pockmark morphologies and genesis in the Tanintharyi shelf of the Andaman Sea as promising hydrocarbon reservoirs - Jianghao Qiao; Xiwu Luan; Thanuja D. Raveendrasinghe; Yintao Lu; Guozhang Fan; Xinyuan Wei; Long Jin; Jian Yin; Haozhe Ma; Lushan Jiang (Marine and Petroleum Geology, 2024)

Intelligent quantitative recognition of sulfide using machine learning-based ratiometric fluorescence probe of metal-organic framework UiO-66-NH2/Ppix - Degui Wang; Long Yu; Xin Li; Yunfei Lu; Chaoqun Niu; Penghui Fan; Houjuan Zhu; Bing Chen; Suhua Wang (Journal of Hazardous Materials, 2024)

Antibiotic resistance genes and heavy metals in landfill: A review - Yan-Jiao Li; Ying Yuan; Wen-Bing Tan; Bei-Dou Xi; Hui Wang; Kun-Long Hui; Jia-Bao Chen; Yi-Fan Zhang; Lian-Feng Wang; Ren-Fei Li (Journal of Hazardous Materials, 2024)

Molecular and geochemical characteristics of lignite in different plant sources evaluated using unsupervised analyses - Yang-Yang Xu; Xing Fan; Feng-Yun Ma; Wen-Long Mo; Xiang Bai; Xian-Yong Wei; Peter N Kuznetsov (Fuel, 2024)

Effects of yeast screened from traditional fermented milk on commercial fermented milk as adjunct flavor culture - Hai-yan Kang; Xiao-lin Ao; Qing Tang; Hongli Li; Yang Fan; Ai-ping Liu; Li-kou Zou; Shu-liang Liu; Yong Yang; Ning Zhao; Jian-long Li (Food Bioscience, 2024)

Contribution of recycled oceanic crust to the extremely light molybdenum isotopic compositions of mid-ocean ridge basalts from the South China Sea - Yu-Xin Cai; Xiao-Long Huang; Yi-Gang Xu; Yang Yu; Jie Li; Fan Yang; Zhen-Min Ge (Chemical Geology, 2024)

Responses of carbon and microbial community structure to soil nitrogen status vary between maize and potato residue decomposition - Linkang Chen; Ping Zhao; Chunyan Ming; Wenchun Yu; Rui Xiang; Maopan Fan; Guangqiang Long (Agriculture, Ecosystems & Environment, 2024)

Petrogenesis and tectonic implications of the Silurian adakitic granitoids in the eastern segment of the Qilian Orogenic Belt, Northwest China - Jiao-Long Zhao; Xiao-Jun Huang; Pei-Qing Hu; Zhen-Xi Yang; Ying Fan; Er-Teng Wang; Fu-Bo Yang; Jing-Yu Zhang (Acta Geochimica, 2024)

A level IV fugacity-based multimedia model based on steady-state particle/gas partitioning theory and its application to study the spatio-temporal trends of PBDEs in atmosphere of northeast China - Meng Qin; Wan-Li Ma; Pu-Fei Yang; Wen-Long Li; Lei Wang; Li-Li Shi; Li Li; Yi-Fan Li (Science of The Total Environment, 2024)

Hydrological characteristics of the Bering Sea in the summer of 2019 - Hongxia Chen; Lina Lin; Long Fan; Bin Kong; Yan He; Zexun Wei; Na Liu; Yida Xu (Marine Environmental Research, 2024)

Garnet geochemistry reveals late-stage oxidation of tin-bearing fractionated granite - Jin-Xiang Li; Lin Ding; Noreen J. Evans; Fang Xu; Wei-Ming Fan; Li-Yun Zhang; Fu-Long Cai; Qiu-Yun Guan; Ya-Hui Yue; Jing Xie (Lithos, 2024)

Role of crustal radiogenic heating in ultra-high temperature metamorphism of the Greater Himalayan Crystalline complex: Phase equilibrium and numerical modelling - Yin-Long Fan; Li-Fei Zhang; Yang Wang; Zhong-Hai Li (Gondwana Research, 2024)

Fluid-rock interaction modeling to constrain Au enrichment: Implication for the giant Jiaodong Au mineralization, eastern North China Craton - Huan-Long Hu; Hong-Rui Fan; Ting-Guang Lan; Xue-Feng Yu; Da-Peng Li; Kui-Feng Yang (Gondwana Research, 2024)

Flower-like 3D MoS2 microsphere/2D C3N4 nanosheet composite for highly sensitive electrochemical sensing of nitrite - Lan Wang; Zhaoya Fan; Feng Yue; Shuo Zhang; Shuo Qin; Chenhao luo; Long Pang; Jianguo Zhao; Jingjing Du; Baodan Jin; Hongzhong Zhang (Food Chemistry, 2024)

Low temperature selective catalytic oxidation of H2S: Influencing factors, mechanisms and regeneration - Mengxue Yin; Suresh C. Pillai; Nanthi Bolan; Hailong Wang; Hongliang Yin; Zhihao Wu; Yan Zheng; Long Zhao; Feiyue Fan; Hong Hou (Chemical Engineering Journal, 2024)

Enhancing Zn2+ diffusion for dendrite-free zinc anodes via a robust zincophilic clay mineral coating - Mengjiao Liu; Anjun Hu; Zhongfu Yan; Jiahao Chen; Miao He; Bo Zhou; Yu Pan; Yining Fan; Daojiang Gao; Jianping Long (Chemical Engineering Journal, 2024)

Metasomatized mantle source of nascent oceanic crust in the Guaymas Basin, Gulf of California - Zhen-Min Ge; Xiao-Long Huang; Wei Xie; Tobias W. Höfig; Fan Yang; Yang Yu; S. Khogenkumar Singh (Chemical Geology, 2024)

Downregulation of the expression of subgenomic chromosome A7 genes promotes plant height in resynthesized allopolyploid Brassica napus - Kanglu Zhao; Jing Dong; Junxiong Xu; Yanbo Bai; Yuhe Yin; Chunshen Long; Lei Wu; Tuanrong Lin; Longqiu Fan; Yufeng Wang; Patrick P. Edger; Zhiyong Xiong (Theoretical and Applied Genetics, 2024)

Potentiation of the lateral habenula-ventral tegmental area pathway underlines the susceptibility to depression in mice with chronic pain - Chun-Kui Zhang; Pan Wang; Yuan-Yuan Ji; Jian-Shuai Zhao; Jun-Xiang Gu; Xian-Xia Yan; Hong-Wei Fan; Ming-Ming Zhang; Yu Qiao; Xiao-Die Liu; Bao-Juan Li; Ming-Hui Wang; et al. (Science China Life Sciences, 2024)

Observation of Arctic surface currents using data from a surface drifting buoy - Hongxia Chen; Lina Lin; Long Fan; Wangxiao Yang; Yinke Dou; Bingrui Li; Yan He; Bin Kong; Guangyu Zuo; Na Liu (Acta Oceanologica Sinica, 2024)

Seroprevalence and potential risk factors of brucellosis in sheep from America, Africa and Asia regions: A systematic review and meta-analysis - Lian-Min Li; Qi Wang; Jun-Feng Shi; Ting Li; Bo Zhao; Qing-Xia Ma; Hong-Ying Liu; Nuo Su; Ruo-Peng Cai; Fan-Li Zeng; Qing-Long Gong; Kun Shi; et al. (Research in Veterinary Science, 2023)

Calcium disodium edetate controls citrus green mold by chelating Mn2+ and targeting pyruvate synthesis in the pathogen - Fan Yang; Shuqi Liu; Zhonghuan Tian; Yujie Du; Deyao Zhang; Chao-an Long (Postharvest Biology and Technology, 2023)

Comparative study on characteristics of typhoon gusts in the coastal and offshore areas of the South China Sea - Qian-Jin Zhou; Lei Li; Shao-Jia Fan; Hong-Long Yang; Wei Sun; Hai-Rong Tang (Physics and Chemistry of the Earth, Parts A/B/C, 2023)

Distinctive graphdiyne coupled with phosphorylation NiFe-LDH S-scheme heterojunction for photocatalytic overall water splitting - Zhaobo Fan; Haolin Lu; Yafeng Liu; Cancan Chang; Xin Guo; Guankui Long; Zhiliang Jin (Chemical Engineering Journal, 2023)

Characteristics of heavy metal accumulation and risk assessment in understory Panax notoginseng planting system - Zhenhua Huang; Zhida Shen; Chunlan Liu; Huineng Shi; Shuran He; Guangqiang Long; Weiping Deng; Jianli Yang; Wei Fan (Environmental Geochemistry and Health, 2023)

Revisiting the Seasonal Evolution of the Indian Ocean Dipole from the Perspective of Process-Based Decomposition - Guangli Zhang; Hanjie Fan; Ke Huang; Tong Long; Wei Song; Qiang Xie (Journal of Ocean University of China, 2023)

Expressions of electron escape probability and photo-emission from metals - Yi-Fan Liu; Ai-Gen Xie; Jing Tang; Hong-Jie Dong; Yun-Long Xie (Annals of Nuclear Energy, 2023)

Experimental study on the flow characteristics of 7-pin hexagonal bundle assembly with grid spacers - Rongjie Li; Dajun Fan; Minghan He; Yang Liu; Qianwan Shi; Yanze Tang; Wangsheng Tian; Deliang Fan; Long Gu (Annals of Nuclear Energy, 2023)

Identification of Bone Metastatic and Prognostic Alternative Splicing Signatures in Prostate Adenocarcinoma - Jiwen Zhu; Jiayao Zhang; Peng Hu; Mingxiang Fan; Dianwen Song; Huabin Yin; Penghui Yan; Shuyuan Xian; Zhenyu Li; Juanru Guo; Chunling Long; Runping Xu; et al. (Biochemical Genetics, 2023)
As the most common nonepithelial malignancy, prostate adenocarcinoma (PRAD) is the fifth chief cause of cancer mortality in men. Distant metastasis often occurs in advanced PRAD and most patients are dying from it. However, the mechanism of PRAD progression and metastasis is still unclear. It’s widely reported that more than 94% of genes are selectively splicing in humans and many isoforms are particularly related with cancer progression and metastasis. Spliceosome mutations occur in a mutually exclusive manner in breast cancer, and different components of spliceosomes are targets of somatic mutations in different types of breast cancer. Existing evidence strongly supports the key role of alternative splicing in breast cancer biology, and innovative tools are being developed to use splicing events for diagnostic and therapeutic purposes. In order to identify if the PRAD metastasis is associated with alternative splicing events (ASEs), the RNA sequencing data and ASEs data of 500 PRAD patients were retrieved from The Cancer Genome Atlas (TCGA) and TCGASpliceSeq databases. By Lasso regression, five genes were screened to construct the prediction model, with a good reliability by ROC curve. Additionally, results in both univariate and multivariate Cox regression analysis confirmed the well prognosis efficacy of the prediction model (both P P P

High uncertainty of evapotranspiration products under extreme climatic conditions - Long Qian; Zhitao Zhang; Lifeng Wu; Shaoshuai Fan; Xingjiao Yu; Xiaogang Liu; Yalan Ba; Haijiao Ma; Yicheng Wang (Journal of Hydrology, 2023)

Spatiotemporal scales of precipitation in the Central Tibetan Plateau identified by in-situ soil moisture observations - Ke Zhang; Long Zhao; Kun Yang; Jun Qin; Lisheng Song; Xiang Ni; Lei Fan; Xujun Han (Journal of Hydrology, 2023)

Urban-rural gradient in vegetation phenology changes of over 1500 cities across China jointly regulated by urbanization and climate change - Yingying Ji; Wenfeng Zhan; Huilin Du; Shasha Wang; Long Li; Jingfeng Xiao; Zihan Liu; Fan Huang; Jiaxin Jin (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

The number and position of unsaturated bonds in aliphatic aldehydes affect the cysteine-glucose Maillard reaction: Formation mechanism and comparison of volatile compounds - Wenbin Du; Yutang Wang; Qinghong Yan; Shuang Bai; Yatao Huang; Long Li; Yuwen Mu; Ashbala Shakoor; Bei Fan; Fengzhong Wang (Food Research International, 2023)

Efficient production of biosurfactant surfactin by a newly isolated Bacillus subtilis (sp.) 50499 strain from oil-contaminated soil - Yulu Du; Yue Wang; Tianyou Cui; Lianpeng Ge; Fan Yu; Mengqian Zhao; Qihang Xu; Mingjie Jin; Bo Chen; Xuwei Long (Food and Bioproducts Processing, 2023)

Circularly polarized thermally activated delayed fluorescence OLEDs with nearly BT.2020 red emission - Bangjin Sun; Lei Ding; Xinzhong Wang; Zhen-Long Tu; Jian Fan (Chemical Engineering Journal, 2023)

Short-term effect of meteorological factors and extreme weather events on daily outpatient visits for dry eye disease between 2013 and 2020: a time-series study in Urumqi, China - Si-Yu Gui; Fei Wang; Jian-Chao Qiao; Xin-Chen Wang; Zhi-Hao Huang; Fan Yang; Cheng-Yang Hu; Fang-Biao Tao; Li-Ming Tao; Dong-Wei Liu; Xiang-Long Yi; Zheng-Xuan Jiang (Environmental Science and Pollution Research, 2023)

Deep insight into green remediation and hazard-free disposal of electrolytic manganese residue-based cementitious material - Fan Wang; Guangcheng Long; John L. Zhou (Science of The Total Environment, 2023)

PdGpaA controls the growth and virulence of Penicillium digitatum by regulating cell wall reorganization, energy metabolism, and CDWEs production - Yujie Du; Jinfan Zhu; Wan Zhang; Xiao Chen; Fan Yang; Zhonghuan Tian; Chao-an Long (Postharvest Biology and Technology, 2023)

Tectonic evolution of the Meso-Tethys Ocean in the Jurassic: Birth, growth, and demise of a missing intra-oceanic arc - Bo-Chuan Zhang; Jian-Jun Fan; An-Bo Luo; Xiao-Wen Zeng; Men-Long Duan; Si-Lin Sun (Gondwana Research, 2023)

Innovative co-treatment technology for effective disposal of electrolytic manganese residue - Yingying Shi; Guangcheng Long; Fan Wang; Youjun Xie; Min Bai (Environmental Pollution, 2023)

Combining HUMSC secretome and a conductive hydrogel enhances angiogenesis and electrical transmission at myocardial infarct sites to support cardiac repair - Shu-yi He; Lin-yu Long; Zhi-cun Wang; Wen-qi Liu; Wen Zhang; Cheng Hu; Xiao-feng Wu; Ruiqi Dong; Hong-song Fan; Qing-Jiang; Ying-ying Tong; Guang-hua Yang; et al. (Chemical Engineering Journal, 2023)

Different B Mo isotopic fractionation processes controlled by redox conditions in the subduction zone - Yang Yu; Xiao-Long Huang; Yu-Ming Lai; Jie Li; Yi-Gang Xu; Sun-Lin Chung; Iwan Setiawan; Fan Yang (Chemical Geology, 2023)

Intracontinental lithospheric delamination: Constraints from imaging the mantle transition zone beneath the southwestern part of the Sichuan Basin - Fan Yang; Juan Li; Sidan Chen; Yun Chen; Long Li; Yinshuang Ai (Science China Earth Sciences, 2023)

Dynamic valuation of the provisioning services of marine fisheries ecosystem based on BeiDou VMS data: A case study of TACs project for Acetes chinensis in the Yellow Sea - Guodong Li; Dongjia Li; Ying Xiong; Xiaming Zhong; Jinjin Shi; Hushun Zhang; Dade Song; Fan Yang; Zhongjie Kang; Xiaorui Wu; Shuyan Wang; Long Liang (Ocean & Coastal Management, 2023)

Divergent urbanization-induced impacts on global surface urban heat island trends since 1980s - Long Li; Wenfeng Zhan; Leiqiu Hu; TC Chakraborty; Zhihua Wang; Peng Fu; Dazhong Wang; Weilin Liao; Fan Huang; Huyan Fu; Jiufeng Li; Zihan Liu; et al. (Remote Sensing of Environment, 2023)

Pilot-scale study on an advanced Fe-Cu process for refractory wastewater pretreatment - Jin-Hong Fan; Zhen-long Yao; De-li Wu; Xia Liu; Lu-ming Ma (Journal of Hazardous Materials, 2023)

A sensitized ratiometric fluorescence probe based on N/S doped carbon dots and mercaptoacetic acid capped CdTe quantum dots for the highly selective detection of multiple tetracycline antibiotics in food - Yao Fan; Lu Shen; Yaqi Liu; Ying Hu; Wanjun Long; Haiyan Fu; Yuanbin She (Food Chemistry, 2023)

Performance and mechanism of calcium peroxide reducing H2S production from sludge anaerobic fermentation - Yunhao Xu; Qizi Fu; Wenming Wang; Fan Yang; Xuemei Li; Fengming Song; Yanguang Qing; Ziqi Lin; Weiqi Long; Dongbo Wang (Chemical Engineering Journal, 2023)

Enhanced enzyme thermostability of a family I.3 lipase LipSR1 by T118A mutation at the calcium-binding site - Shijie Jiang; Zhengfu Zhou; Jiahui Han; Qingfeng Fan; Zhijian Long; Jin Wang (Biotechnology Letters, 2023)

Regulation of soil water and nitrate by optimizing nitrogen fertilization and the addition of manure based on precipitation: An 8-year field record - Wenguang Li; Long Ma; Fan Shi; Shuting Wang; Jiarui Zhao; Wei Zheng; Zhijun Li; Ziyan Li; Bingnian Zhai (Agriculture, Ecosystems & Environment, 2023)

Description and genomic characterization of Gallaecimonas kandeliae sp. nov., isolated from the sediments of mangrove plant Kandelia obovate - Meng Long; Shaoshuai Tang; Huimin Fan; Zhen Gan; Hongli Xia; Yishan Lu (Antonie van Leeuwenhoek, 2023)

4-hydroxylonchocarpin and corylifol A: The potential hepatotoxic components of Psoralea corylifolia L - Linqi Ouyang; Zhiqiang Fan; Yang He; Long Tan; Guoyan Deng; Qin He; Yiran He; Ting Ouyang; Congjie Li; Qin Zhang; Hongyu Liu; Yajie Zuo (Toxicology Letters, 2023)

Global mapping of urban thermal anisotropy reveals substantial potential biases for remotely sensed urban climates - Huilin Du; Wenfeng Zhan; Zihan Liu; E. Scott Krayenhoff; TC Chakraborty; Lei Zhao; Lu Jiang; Pan Dong; Long Li; Fan Huang; Shasha Wang; Yuyue Xu (Science Bulletin, 2023)

First occurrence of caryocaridids (Crustacea, Phyllocarida) in the Ordovician of North China - Yi-long Liu; Ruo-ying Fan; Rui-wen Zong; Yi-ming Gong (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Enhancement of waste activated sludge hydrolysis and decomposition by combined free nitrous acid and sodium citrate pretreatment - Wu-yang Zhou; Qian Fang; Wen-xue Ding; Zi-long Xiao; Fan Luo; Peng-fei Ren; Guang-hua Wang (Journal of Water Process Engineering, 2023)

Rational design and reduction kinetics of efficient Ce-Co oxygen carriers for chemical looping reforming of methane - Weixiang Zhang; Lina Zhang; Sijia Pei; Jiarui Wang; Dawei Liu; Xiaoxun Ma; Maohong Fan; Long Xu (Fuel, 2023)

Effects of wildfire disturbance on forest soil microbes and colonization of ericoid mycorrhizal fungi in northern China - Hu Lou; Huiying Cai; Rao Fu; Chao Guo; Baozhen Fan; Haiqing Hu; Jie Zhang; Long Sun (Environmental Research, 2023)

An advanced LiCrTiO4@C cathode towards hybrid Mg-Li ion batteries with ultrastable cycling stability - Xiang Bai; Caixia Zhu; Yierxiati Dilixiati; Xing Fan; Xing-Lei Wang; Miao Du; Zhi-Xiong Huang; Xiao-Yan He; Xing-Long Wu (Chemical Engineering Journal, 2023)

Recyling manganese-rich electrolytic residues: a review - Fan Wang; Guangcheng Long; Kunlin Ma; Xiaohui Zeng; Zhuo Tang; Rongzhen Dong; Jionghuang He; Minghui Shangguan; Qingchun Hu; Rock Keey Liew; Yang Li; John Zhou (Environmental Chemistry Letters, 2023)

miRNAs contributing to the repair of tendon injury - Kexin Lyu; Xinyue Liu; Tianzhu Liu; Jingwei Lu; Li Jiang; Yixuan Chen; Longhai Long; Xiaoqiang Wang; Houyin Shi; Fan Wang; Sen Li (Cell and Tissue Research, 2023)
Tendon injury is one of the most common disorders of the musculoskeletal system, with a higher likelihood of occurrence in elderly individuals and athletes. In posthealing tendons, two undesirable consequences, tissue fibrosis and a reduction in mechanical properties, usually occur, resulting in an increased probability of rerupture or reinjury; thus, it is necessary to propose an appropriate treatment. Currently, most methods do not sufficiently modulate the tendon healing process and restore the function and structure of the injured tendon to those of a normal tendon, since there is still inadequate information about the effects of multiple cellular and other relevant signaling pathways on tendon healing and how the expression of their components is regulated. microRNAs are vital targets for promoting tendon repair and can modulate the expression of biological components in signaling pathways involved in various physiological and pathological responses. miRNAs are a type of noncoding ribonucleic acid essential for regulating processes such as cell proliferation, differentiation, migration and apoptosis; inflammatory responses; vascularization; fibrosis; and tissue repair. This article focuses on the biogenesis response of miRNAs while presenting their mechanisms in tendon healing with perspectives and suggestions.

Feasibility of low-carbon electrolytic manganese residue-based supplementary cementitious materials - Fan Wang; Guangcheng Long; Min Bai; Yingying Shi; John L. Zhou (Science of The Total Environment, 2023)

Molecular insights into the dissolved organic matter of leather wastewater in leather industrial park wastewater treatment plant - Xiao-Xu Gao; Yun-Wen Wang; Ye-Chen An; Rui-Yun Ren; Yao-Hui Lin; Ning Wang; Yi-Fan Wang; Jing-Long Han; Zhi-Neng Hao; Jing-Fu Liu; Ai-Jie Wang; Nan-Qi Ren (Science of The Total Environment, 2023)

Spatial distribution and temporal trend of organochlorine pesticides in Chinese surface soil - Shuai Hao; Wen-Long Li; Li-Yan Liu; Zi-Feng Zhang; Wan-Li Ma; Yi-Fan Li (Environmental Science and Pollution Research, 2023)

Attapulgite amendment favors the utilization of high cadmium-contaminated soil for Erigeron breviscapus cultivation - Lijie Jia; Wei Fan; Peili Wang; Yu Chen; Ping Zhao; Shengchao Yang; Guangqiang Long (Chemosphere, 2023)

Cloning and rational modification of a cold-adapted esterase for phthalate esters and parabens degradation - Yan-Yan Liu; Yi-Xin Zhang; Hua-Mei Wen; Xiao-Long Liu; Xin-Jiong Fan (Chemosphere, 2023)

Influence on the levels of PAHs and methylated PAHs in surface soil from pollution control in China: Evidence in 2019 data compared with 2005 and 2012 data - Fu-Jie Zhu; Zi-Feng Zhang; Li-Yan Liu; Hong Yao; Hong-Liang Jia; Zhi Zhang; Song Cui; Bo Meng; Gang Cao; Peng-Hao Su; Xiao-Xuan Mao; Bao-Long Li; et al. (Science of The Total Environment, 2023)

Ca. 830 Ma alkaline mafic dykes in the southeastern Guizhou Province, South China: New constraints on the Neoproterozoic evolution of the Yangtze Block - Hong-Peng Fan; Jia-Xi Zhou; Zhi-Long Huang; Tao Wu; Hao Zhang (Precambrian Research, 2023)

GAR-transferase contributes to purine synthesis and mitochondrion function to maintain fungal development and full virulence of Penicillium digitatum - Fan Yang; Yongqing Lu; Yulin Du; Shuqi Liu; Xiuying Zhong; Yujie Du; Zhonghuan Tian; Chao-an Long (International Journal of Food Microbiology, 2023)

Gold endowment and unloading along pathway for giant gold mineralization: Insights from spatiotemporal variations of in-situ pyrite geochemistry and gold fineness from the Jiaodong gold deposits, north China Craton - Ting-Guang Lan; Hong Wang; Hong-Rui Fan; Thomas Ulrich; Huan-Long Hu; You-Wei Chen; Lei Shu (Gondwana Research, 2023)

A comparative study of different iron minerals on phosphorus capture from municipal wastewater and subsequent recovery as vivianite through acidogenic fermentation - Shi-Xu Wang; Yun-Xin Huang; Hao Wang; Yao-Yao Lu; Wen-Long He; Jing Li; Nian-Si Fan; Bao-Cheng Huang; Ren-Cun Jin (Chemical Engineering Journal, 2023)

Metformin Alleviates Delayed Hydrocephalus after Intraventricular Hemorrhage by Inhibiting Inflammation and Fibrosis - Yi Cao; Chang Liu; Gaowei Li; Weina Gao; Hui Tang; Shuanmin Fan; Xin Tang; Long Zhao; Haoxiang Wang; Aijun Peng; Chao You; Aiping Tong; et al. (Translational Stroke Research, 2023)

A reversible CHEF-based NIR fluorescent probe for sensing Hg2+ and its multiple application in environmental media and biological systems - Meiqing Zhu; Long Sun; Xina Liu; Xiaohui Pang; Fugang Fan; Xiaofan Yang; Rimao Hua; Yi Wang (Science of The Total Environment, 2023)

Role of reaction adsorption on the production of 5-hydroxymethylfurfural from fructose under microwave hydrothermal process - Yanhong Wang; Lijiao Fan; Liqun Xiao; Lulu Wang; Dongsheng Shen; Yuyang Long (Fuel, 2023)

Reduced and deep application of controlled-release urea maintained yield and improved nitrogen-use efficiency - Kaibo Hu; Ping Zhao; Kaixian Wu; Hongli Yang; Qingxia Yang; Maopan Fan; Guangqiang Long (Field Crops Research, 2023)

A safe anode-free lithium metal pouch cell enabled by integrating stable quasi-solid electrolytes with oxygen-free cathodes - Chuan Zhao; Yu Pan; Runjing Li; Anjun Hu; Bo Zhou; Miao He; Jiahao Chen; Zhongfu Yan; Yining Fan; Nian Chen; Mengjiao Liu; Jianping Long (Chemical Engineering Journal, 2023)

Comparative genomic analysis provides insights into taxonomy and temperature adaption of Aeromonas salmonicida - Meng Long; Huimin Fan; Zhen Gan; Zenghai Jiang; Shaoshuai Tang; Hongli Xia; Yishan Lu (Journal of Fish Diseases, 2023)
Aeromonas salmonicida has long been known as psychrophiles since it is mainly isolated from cold water fish, and recent reports have revealed the existence of mesophilic strains isolated from warm sources. However, the genetic differences between mesophilic and psychrophilic strains remain unclear due to few complete genomes of mesophilic strain are available. In this study, six A. salmonicida (2 mesophilic and 4 psychrophilic) were genome‐sequenced, and comparative analyses of 25 A. salmonicida complete genomes were conducted. The ANI values and phylogenetic analysis revealed that 25 strains formed three independent clades, which were referred as typical psychrophilic, atypical psychrophilic and mesophilic groups. Comparative genomic analysis showed that two chromosomal gene clusters, related to lateral flagella and outer membrane proteins (A‐layer and T2SS proteins), and insertion sequences (ISAs4, ISAs7 and ISAs29) were unique to the psychrophilic groups, while the complete MSH type IV pili were unique to the mesophilic group, all of which may be considered as lifestyle‐related factors. The results of this study not only provide new insights into the classification, lifestyle adaption and pathogenic mechanism of different strains of A. salmonicida , but also contributes to the prevention and control of disease caused by psychrophilic and mesophilic A. salmonicida.

Effects of cadmium on transcription, physiology, and ultrastructure of two tobacco cultivars - Zhiguo Liu; Xiuzhe Wu; Lei Hou; Shengzhe Ji; Yao Zhang; Weiru Fan; Tong Li; Li Zhang; Peng Liu; Long Yang (Science of The Total Environment, 2023)

Diversity of sesquiterpenoids from Stellera chamaejasme with neuroprotective effects - Fang-Yu Yuan; Zhuo-Ya Tang; Xue-Long Yan; Dong Huang; Han-Zhuang Weng; Jia-Luo Huang; Run-Zhu Fan; Ye Chen; Sheng Yin; Gui-Hua Tang (Phytochemistry, 2023)

Fabrication of an alginate-based ZhiNengCong gel showed an enhanced antiviral and plant growth promoting functions - Long Jiang; Qin Wang; Shuai Zhang; Changyun Liu; Ke Wang; Fengwei Li; Xiaoyan Wang; Weina Liu; Xiaozhou Ma; Guangjin Fan; Tiancai Chen; Yabo Jin; et al. (Pesticide Biochemistry and Physiology, 2023)

A novel evaluation method for rolling energy losses of tacked vehicle road wheels using experimental modal analysis - Chengwei Zhu; Ye Zhuang; Weiguang Fan; Zhenxin Long; Shuyu Zhang (Journal of Terramechanics, 2023)

Manganese and copper additions differently reduced cadmium uptake and accumulation in dwarf Polish wheat (Triticum polonicum L.) - Xing Chen; Shan Yang; Jian Ma; Yiwen Huang; Yi Wang; Jian Zeng; Jun Li; Siyu Li; Dan Long; Xue Xiao; Lina Sha; Dandan Wu; et al. (Journal of Hazardous Materials, 2023)

Effect of different vegetation restoration on soil organic carbon dynamics and fractions in the Rainy Zone of Western China - Fan Yang; Yujian Zhong; Guangzhong Han; Xiuzhi Li; Li Luo; Xiaomin Cai; Xinyu Long; Tangli Li; Laiming Huang (Journal of Environmental Management, 2023)

Different reoxygenation rates induce different metabolic, apoptotic and immune responses in Golden Pompano (Trachinotus blochii) after hypoxic stress - Tian Jiang; Ye Song Liang; Yue Gu; Fu Cheng Yao; Yi Fan Liu; Kai Xi Zhang; Fei Biao Song; Jun Long Sun; Jian Luo (Fish & Shellfish Immunology, 2023)

Association between maternal exposure to per- and polyfluoroalkyl substances and serum markers of liver function during pregnancy in China: A mixture-based approach - Qian Liao; Peng Tang; Haoran Fan; Yanye Song; Jun Liang; Huishen Huang; Dongxiang Pan; Meile Mo; LeiLei; Mengrui Lin; Jiehua Chen; Huanni Wei; et al. (Environmental Pollution, 2023)

Biomass types of nitrate-reducing denitrifiers to differentiate the hybrid community allocation of partial denitrification (PD) and anammox: IFAS vs MBBR - Lifang Yu; Yiting Wang; Xin Tian; Ye Fan; Yexing Liu; Jiayi Yang; Long Li (Chemical Engineering Journal, 2023)

Fluid evolution and ore genesis of the Tiantangshan granite-related vein-type Rb-Sn-W deposit, south China: constraints from LA-ICP-MS analyses of fluid inclusions - Hong-Wei Peng; Hong-Rui Fan; Pilar Lecumberri-Sanchez; Jian-Qing Lai; Huan-Long Hu; Ting-Guang Lan; Xing-Hui Li (Mineralium Deposita, 2023)

Long-term effects of meteorological factors and extreme weather on daily outpatient visits for conjunctivitis from 2013 to 2020: a time-series study in Urumqi, China - Si-Yu Gui; Jian-Chao Qiao; Xin-Chen Wang; Fan Yang; Cheng-Yang Hu; Fang-Biao Tao; Xiang-Long Yi; Zheng-Xuan Jiang (Environmental Science and Pollution Research, 2023)

Effects of farmland use transition on soil organic carbon in dry farming areas - Ligang Lyu; Junjun Zhu; Hualou Long; Kaihua Liao; Yeting Fan; Junxiao Wang (Environment, Development and Sustainability, 2023)

Seasonal variations of airborne phthalates and novel non-phthalate plasticizers in a test residence in cold regions: Effects of temperature, humidity, total suspended particulate matter, and sources - Chun-Yan Huo; Wen-Long Li; Li-Yan Liu; Yu Sun; Jia-Qi Guo; Liang Wang; Hayley Hung; Yi-Fan Li (Science of The Total Environment, 2023)

Competition between biogeochemical drivers and land-cover changes determines urban greening or browning - Long Li; Wenfeng Zhan; Weimin Ju; Josep Peñuelas; Zaichun Zhu; Shushi Peng; Xiaolin Zhu; Zihan Liu; Yuyu Zhou; Jiufeng Li; Jiameng Lai; Fan Huang; et al. (Remote Sensing of Environment, 2023)

Catalytic activation of formic acid using Pd nanocluster decorated graphitic carbon nitride for diclofenac reductive hydrodechlorination - Feng Shao; Yixuan Gao; Wenhui Xu; Fengbin Sun; Long Chen; Fan Li; Wen Liu (Journal of Hazardous Materials, 2023)

Superhydrophobic aerogel blanket with magnetic and solar heating effect enables efficient continuous cleanup of highly viscous crude oil - Xueyan Wang; Xianfeng Liu; Zhong Liu; Wenying Cui; Shilong Gao; Jun Zhang; Tingting Fan; Seeram Ramakrishna; Yun-Ze Long (Journal of Hazardous Materials, 2023)

Room-temperature synthesis of nitrogen-rich conjugated microporous polymers for solid-phase extraction of trace synthetic musks - Ye-Fei Fan; Hai-Long Jiang; Xiang-Feng Chen; Na Li; Xiao-Li Wang; Jin-Ming Lin; Ru-Song Zhao (Food Chemistry, 2023)

Stronger effects of environmental factors than denitrifying genes on soil denitrification under a subtropical land use change - Qiong Chen; Fan Yang; Jingwen Chen; Chunyan Long; Xiaoli Cheng (CATENA, 2023)

Response of Soil Bacteria of Dicranopteris dichotoma Populations to Vegetation Restoration in Red Soil Region of China - Qi-yan Li; Chen-lu Zhu; Jun-bao Yu; Xin-yi Wu; Si-qi Huang; Fan Yang; Mulualem Tigabu; Xiao-long Hou (Journal of Soil Science and Plant Nutrition, 2023)

Leaf and rhizome transcriptome assembly and expression analysis of genes involved in terpene biosynthesis in Dioscorea opposita - Dianyun Hou; Yaoyao Wang; Ruiying Zhang; Xingli Zhao; Zhanqiang Ma; Zhenjie Fan; Long Wang; Xiaoran Liu; Jiaqi Zhang (Journal of Plant Biochemistry and Biotechnology, 2023)

Effects of shared governance and cost redistribution on air pollution control: a study of game theory–based cooperation - Chen-xi Yin; Yi-fan Gu; Guo-long Zhao (Environmental Science and Pollution Research, 2023)

Airflow characteristics of rotorcraft plant protection UAV operating in rice fields - Gangao Fan; Zhijie Liu; Yijuan Qin; Bo Long; Huifen Li; Jiyu Li (Biosystems Engineering, 2023)

Different reaction mechanisms of SO4•− and •OH with organic compound interpreted at molecular orbital level in Co(II)/peroxymonosulfate catalytic activation system - Huixuan Zhang; Chenghan Xie; Long Chen; Jun Duan; Fan Li; Wen Liu (Water Research, 2023)

Full-scale experimental and numerical study of smoke spread characteristics in a long-closed channel with one lateral opening - Weixin Tong; Fanliang Ge; Long Ding; Jie Ji; Yuanlong Zhou; Yang Zhou; Fan Zhou (Tunnelling and Underground Space Technology, 2023)

Seismic behavior of prefabricated steel multi-ribbed composite walls connected with cast steel joints - Gang Liu; Wei Huang; Chen-Long Zhang; Wei Wang; Zhen-Hui Fan (Soil Dynamics and Earthquake Engineering, 2023)

Contaminant characterization at pesticide production sites in the Yangtze River Delta: Residue, distribution, and environmental risk - Mei Li; Qiang Chen; Lu Yang; Ya Zhang; Jinlin Jiang; Shaopo Deng; Jinzhong Wan; Tingting Fan; Tao Long; Shengtian Zhang; Yusuo Lin (Science of The Total Environment, 2023)

Multiple-objective optimization of Jet Controlled Compression Ignition (JCCI) mode with dual-direct injection in a high-speed light-duty engine - Bo Li; Jian Wang; Heng Zhang; Liyun Fan; Xianyin Leng; Wuqiang Long; Ge Xiao (Fuel, 2023)

Resistance vs. surrender: Different responses of functional traits of soybean and peanut to intercropping with maize - Wei-Ping Zhang; Zhao-Xin Li; Sai-Nan Gao; Hao Yang; Hua-Sen Xu; Xin Yang; Hong-Xia Fan; Ye Su; Surigaoge; Jacob Weiner; Dario Fornara; Long Li (Field Crops Research, 2023)

Prediction and optimization of medium-chain carboxylic acids production from food waste using machine learning models - Fei Long; Joshua Fan; Hong Liu (Bioresource Technology, 2023)

Bioactive components and beneficial bioactivities of flowers, stems, leaves of Lonicera japonica Thunberg: A review - Yuke Li; Long Xie; Kai Liu; Xiaofang Li; Fan Xie (Biochemical Systematics and Ecology, 2023)

Default mode network mechanisms of repeated transcranial magnetic stimulation in heroin addiction - Long Jin; Menghui Yuan; Wei Zhang; Lei Wang; Jiajie Chen; Fan Wang; Jia Zhu; Tao Liu; Yixin Wei; Yunbo Li; Wei Wang; Qiang Li; et al. (Brain Imaging and Behavior, 2023)

Investigation on swelling characteristics of GMZ bentonite with different initial water contents - Bo Chen; Fan Peng; Long Zhang; De'an Sun (Annals of Nuclear Energy, 2023)

Hypoxia alters glucose and lipid metabolisms in golden pompano (Trachinotus blochii) - Tian Jiang; Jun Long Sun; Yue Gu; Fu Cheng Yao; Ye Song Liang; Yi Fan Liu; Kai Xi Zhang; Fei Biao Song; Li Zhou; Zhong Wei Wang; Jian Fang Gui; Jian Luo (Aquaculture, 2023)

Quantification of the asynchronous gas diffusivity in macro-/micropores using a Nelder-Mead simplex algorithm and its application on predicting desorption-based indexes - Wei Zhao; Kai Wang; Yang Ju; Long Fan; Heng Cao; Yun Yang; Longyong Shu; Zhongkai Feng; Ran Cui; Xiaofang Guo; Liuyi Wang (Fuel, 2023)

Effect of solvent swelling with different enhancement methods on the microstructure and pyrolysis performance of Hefeng subbituminous coal - Hui Kan; Yue Wang; Wen-Long Mo; Xian-Yong Wei; Hong-Yu Mi; Kong-Jun Ma; Mei-Xia Zhu; Wen-Cang Guo; Jia Guo; Jun-Min Niu; Xing Fan (Fuel, 2023)

Effect of sequential thermal dissolution on the structure and pyrolysis characteristics of Naomaohu lignite - Xiao-Bo Hu; Hao Xu; Wen-Long Mo; Xing Fan; Wen-Cang Guo; Jia Guo; Jun-Min Niu; Hong-Yu Mi; Ya-Ya Ma; Xian-Yong Wei (Fuel, 2023)

Characterisation of a laccase isolated from Trametes hirsuta and its application in the oligomerisation of phenolic compounds - Long-Bin Zhang; Zhi-Qiang Deng; Ting-Ting Qiu; Wu-Wei-Jie Yang; Fan Zhu; Xiu-Yun Ye (Fungal Biology, 2023)

FeCl3 and Fe2(SO4)3 differentially reduce Cd uptake and accumulation in Polish wheat (Triticum polonicum L.) seedlings by exporting Cd from roots and limiting Cd binding in the root cell walls - Qin Yao; Weiping Li; Ying Liu; Yiran Cheng; Xue Xiao; Dan Long; Jian Zeng; Dandan Wu; Lina Sha; Xing Fan; Houyang Kang; Haiqin Zhang; et al. (Environmental Pollution, 2023)

A facile graphene oxide modified approach towards membrane with prominent improved permeability and antifouling performance - Shougang Fan; Zhihao Yu; Xi Wang; Yiyi Tao; Huaiqi Shao; Mingce Long; Xiaoyan Guo (Desalination, 2023)

Direct cytosolic delivery of DNA by creating fast closable holes in the cell membrane - Haili Wang; Wei You; Fan Gao; Lei Zhang; Aizong Shen; Fei Wang; Guang Chen; Xuan Nie; Lei Xia; Wei-Qiang Huang; Wen-Jian Zhang; Long-Hai Wang; et al. (Chemical Engineering Journal, 2023)

Tailoring mixed geometrical configurations in amorphous catalysts to activate oxygen electrode reactions of lithium-oxygen batteries - Runjing Li; Anjun Hu; Chuan Zhao; Bo Zhou; Miao He; Yining Fan; Jiahao Chen; Zhongfu Yan; Yu Pan; Jianping Long (Chemical Engineering Journal, 2023)

Cationic molecular probes based on aggregation-induced emission for fluorescent sensing and super-resolution imaging of insulin fibrosis - Li-Jun Mei; Cheng Fan; Chu-Ran Xu; Qi Yu; Chong Li; Ya-Long Wang; Ming-Qiang Zhu (Chemical Engineering Journal, 2023)

The reaction mechanism of highly dispersed Cu atoms and ultrafine MnOx nanoclusters co-modified ZSM-5 based on in-situ heteronuclear substitution for catalytic oxidation C6H14 - Jian Li; Jingnan Hu; Yingjie Shi; Jiajia Zhao; Hongchang Wang; Shuang Deng; Yutao Cui; Fan Wang; Hongyan Long; Yuling Tan (Chemical Engineering Journal, 2023)

Groundwater Quality Evaluation and Analysis Technology Based on AHP-EWM-GRA and Its Application - Menghua Li; Bo Li; Jingyan Chu; Huang Wu; Zhicheng Yang; Juan Fan; Lei Yang; Pu Liu; Jie Long (Water, Air, & Soil Pollution, 2023)

Water consumption prediction and influencing factor analysis based on PCA-BP neural network in karst regions: a case study of Guizhou Province - Zhicheng Yang; Bo Li; Huang Wu; MengHua Li; Juan Fan; Mengyu Chen; Jie Long (Environmental Science and Pollution Research, 2022)

Associations of bisphenol exposure with thyroid hormones in pregnant women: a prospective birth cohort study in China - Huishen Huang; Jun Liang; Peng Tang; Chuanxiang Yu; Haoran Fan; Qian Liao; Jinghua Long; Dongxiang Pan; Xiaoyun Zeng; Shun Liu; Dongping Huang; Xiaoqiang Qiu (Environmental Science and Pollution Research, 2022)

The central role of GmGLP20.4 in root architecture modifications of soybean under low-nitrogen stress - Wei Wang; Jiajia Li; Muhammad Nadeem; Jianxin Wang; Ru Huang; Qian Liu; Wenqiao Fan; Haowei Zheng; Long Yan; Xiaobo Wang (Theoretical and Applied Genetics, 2022)

The analysis of spatial–temporal effects of relevant factors on carbon intensity in China - Yu Zheng; Yonghong Long; Honggang Fan (Stochastic Environmental Research and Risk Assessment, 2022)

Two new monoterpenoid indole alkaloids from Mappianthus iodoides stems - Lan Zhou; Pian-Chou Gongpan; Qing-Fei Fan; Zhi Na; Feng-Mei Huang; Kai-Long Ji; Qi-Shi Song (Natural Product Research, 2022)

Fine mapping of the reduced height gene Rht22 in tetraploid wheat landrace Jianyangailanmai (Triticum turgidum L.) - Chao Wang; Yunjing Bao; Qin Yao; Dan Long; Xue Xiao; Xing Fan; Houyang Kang; Jian Zeng; Lina Sha; Haiqin Zhang; Dandan Wu; Yonghong Zhou; et al. (Theoretical and Applied Genetics, 2022)

Potential antibacterial and anti-biofilm effects of Anoectochilus roxburghii rhizome cultures - Ming-Zhi Fan; Xiao-Long Jiang; Xuan-Chun Piao; Xue-Feng Li; Mei-Yu Jin; Mei-Lan Lian (Journal of Plant Biochemistry and Biotechnology, 2022)

Genome-wide association study of SARS-CoV-2 infection in Chinese population - Jie Fan; Quan-Xin Long; Ji-Hua Ren; Hao Chen; Meng-Meng Li; Zheng Cheng; Juan Chen; Li Zhou; Ai-Long Huang (European Journal of Clinical Microbiology & Infectious Diseases, 2022)

Experimental and Numerical Resistance Analysis for a Cruise Ship W/O Fin Stabilizers - Rulin Yao; Long Yu; Qidong Fan; Xuefeng Wang (Journal of Marine Science and Engineering, 2022)
Applying fin stabilizers is an effective solution for ship rolls on waves in a seaway. They generally consist of one or two pairs of retractable fins that are symmetrically mounted to both sides of the ship, effectively reducing the roll motion at low or moderate speeds. Fin stabilizers are commonly used by cruise ships for the comfort and safety of passengers. However, there is still little experimental and numerical analysis of the fins’ effect on hydrodynamic performance. In this study, the resistance performance of a cruise ship was investigated with/without fin stabilizers at different fin angles and ship velocities by model tests and numerical analysis. The CFD analysis provides a flow-detailed interpretation of the physical phenomenon, especially at an asymmetric maximum fin angle. The significant fin-induced resistance is newly discovered and averages up to 19% in calm water conditions, while the added resistance in waves is evaluated with a smaller increment up to 1.31%. By comparing the numerical and experimental results, this study provides insight into the resistance induced by overhanging fins, which provides an accurate prediction reference for cruise ship performance and benefits the fin stabilizers’ design and selection.

Characterization of Fine-Scale Turbulence Generated in a Laboratory Orbital Shaker and Its Influence on Skeletonema costatum - Lin Yu; Yifan Li; Zhongzhi Yao; Long You; Zong-Pei Jiang; Wei Fan; Yiwen Pan (Journal of Marine Science and Engineering, 2022)
Turbulence is one of the ubiquitous aspects of aquatic systems and affects many physical and biological processes. Based on direct velocity measurements and a computational fluid dynamics (CFD) simulation, we characterized the distribution of the turbulent kinetic dissipations rates (ε) in an orbital shaker system within a range of rotation frequencies. CFD was able to estimate the ε distribution in containers accurately, which was confirmed by other two methods and was independent of velocity measurement. The results showed that ε was linearly correlated with the rotational frequencies. Despite the existence of gradients of ε and the fact that a mean circular horizontal flow was formed within the tank, the energy levels of the whole tank varied spatially within an order of magnitude and the ε distributions at different rotational frequencies were similar, suggesting that the ε distribution in the whole tank could be seen as quasi-homogeneous. To investigate the influence of turbulence on algae growth, culture experiments of a typical diatom—Skeletonema costatum were carried out under different turbulence conditions. Our results suggested turbulence mixing promoted nutrient uptake and growth of Skeletonema costatum, which could be attributed to the break of the diffusion-limited resource concentration boundary layer surrounding phytoplankton.

High-normal blood pressure (prehypertension) is associated with PM2.5 exposure in young adults - Huaze Ye; Jie Tang; Leiqin Luo; Tianjian Yang; Kedi Fan; Long Xu (Environmental Science and Pollution Research, 2022)

Biological characterization and genomic analysis of Acinetobacter baumannii phage BUCT628 - Yinuo Zhu; Ke Han; Long Chen; Shizhong Luo; Huahao Fan; Yigang Tong (Archives of Virology, 2022)

Identification and characterization of stress responsive homeodomain leucine zipper transcription factors in Medicago truncatula - Xiao Li; Yiyao Hou; Fan Zhang; Mingna Li; Fengyan Yi; Junmei Kang; Qingchuan Yang; Ruicai Long (Molecular Biology Reports, 2022)

Noninvasive oral cancer screening based on local residual adaptation network using optical coherence tomography - Wei Yuan; Long Cheng; Jinsuo Yang; Boya Yin; Xingyu Fan; Jing Yang; Sen Li; Jianjun Zhong; Xin Huang (Medical & Biological Engineering & Computing, 2022)

Investigation on oxygen-controlled sewage sludge carbonization with low temperature: from thermal behavior to three-phase product properties - Fan Yu; Yanjun Hu; Lianming Li; Qianqian Guo; Yonghao Zhu; Long Jiao; Yihong Wang; Xiaoqiang Cui (Environmental Science and Pollution Research, 2022)

Ligulaveitnoid A, a new phenylpropanoid from rhizomes and roots of Ligularia veitchiana - Dong Xu; Hong-Zhi Song; Jian-Long Xu; Wei-Min Hu; Xiao-Yong Fan; Hui Wang; Kun Zou (Natural Product Research, 2022)

Sampling Designs for Monitoring Ichthyoplankton in the Estuary Area: A Case Study on Coilia mystus in the Yangtze Estuary - Xiangyu Long; Rong Wan; Zengguang Li; Dong Wang; Pengbo Song; Fan Zhang (Frontiers in Marine Science, 2022)
A fishery-independent survey can provide detailed information for fishery assessment and management. However, the sampling design for the survey on ichthyoplankton in the estuary area is still poorly understood. In this study, we developed six stratified schemes with various sample sizes, attempting to find cost-efficient sampling designs for monitoring Coilia mystus ichthyoplankton in the Yangtze Estuary. The generalized additive model (GAM) with the Tweedie distribution was used to quantify the “true” distribution of C. mystus eggs and larvae, based on the data from the fishery-independent survey in 2019–2020. The performances of different sampling designs were evaluated by relative estimation error (REE), relative bias (RB), and coefficient of variation (CV). The results indicated that appropriate stratifications with intra-stratum homogeneity and inter-stratum heterogeneity could improve precision. The stratified schemes should be divided not only between the North Branch and South Branch but between river and sea. No less than two stratifications in the South Branch could also get better performance. The sample sizes of 45–55 were considered as the cost-efficient range. Compared to other monitoring programs, monitoring ichthyoplankton in the estuary area required a more complex stratification and a higher resolution sampling. The design ideology and optimization methodology in our study would provide references to sampling designs for ichthyoplankton in the estuary area.

Nakamurella leprariae sp. nov., isolated from a lichen sample - De-Feng An; Shao-Juan Yang; Long-Qian Jiang; Xin-Yu Wang; Xiao-Yu Huang; Lei Lang; Xue-Mei Chen; Ming-Qun Fan; Gui-Ding Li; Ming-Guo Jiang; Li-Song Wang; Cheng-Lin Jiang; et al. (Archives of Microbiology, 2022)

The role of earthquake-induced landslides in erosion and weathering from active mountain ranges: Progress and perspectives - Zhangdong Jin; Robert G. Hilton; A. Joshua West; Gen K. Li; Fei Zhang; Jin Wang; Gaojun Li; Xuanmei Fan; Meng-Long Hsieh (Science China Earth Sciences, 2021)

Investigation on the statistical characteristics of geoelectric field seismic anomalies in the North–South seismic belt of Chinese mainland - Hou Ze-Yu; An Zhang-Hui; Fan Ying-Ying; Tan Da-Cheng; Fu A-Long; Wei Lei (Acta Geophysica, 2021)

Improvement of farmland drainage calculation method under environmental change in Huaibei plain * - Jun‐feng Wang; Mei Zhu; Zhen‐long Wang; Tian‐tong Zhang; Yin‐fan Qi; Ling‐ling Zhu (Irrigation and Drainage, 2021)
Changes and new thoughts are vital if the farmland drainage method in the Huabei Plain is to be improved. In this article, drainage flow was chosen as the research object. Based on long‐series precipitation data, the spatial distribution of precipitation was analysed. The peak value relation index ( m ) was either adjusted or unadjusted in contrast calculations with the empirical formula and the average draining formula. The adjustment rationality and adjustment range of m were researched. Results of calculations were analysed and used to improve the applicability of the empirical formula. The spatial distribution of precipitation showed a decreasing trend from south‐west to north‐east. Before adjustment, the result of the empirical formula was equivalent to the flow of 1 day of draining water. After adjusting m to 0.84–0.87, the result was equivalent to the flow of 1.5 days of draining water. With the decrease of rainfall frequency, the drainage flow of the average draining formula was greater than that of the empirical formula and the ratio was 1.13 times when the runoff depth was 50 mm. m can be selected from 0.84 to 0.87 for calculating drainage flow in the Huabei Plain by using the empirical formula and has a direct ratio with precipitation.

Euphanoids A and B, two new lathyrane diterpenoids with nitric oxide (NO) inhibitory activity from Euphorbia kansuensis - Xue-Long Yan; Run-Zhu Fan; Jun Sang; Xing-Lin Xie; Gui-Hua Tang; Sheng Yin (Natural Product Research, 2021)

Risk factors for recurrent positive results of the nucleic acid amplification test for COVID-19 patients: a retrospective study - Wanwan Yi; Xuan Long; Jin Liu; LiShuai Shi; Zichen Chen; Jing Yang; Ziyu Yang; Zhongwei Lv; Hengwei Fan (Human Cell, 2021)
Positive retests of COVID-19 represent a public health concern because of the increased risk of transmission. This study explored whether factors other than the nucleic acid amplification test (NAAT) contribute to positive retest results. Patients with COVID-19 admitted to the Guanggu district of the Hubei Maternal and Child Health Hospital between February 17 and March 28, 2020, were retrospectively included. The patients were grouped into the negative ( n = 133) and positive ( n = 51) retest groups. The results showed that the proportion of patients presenting with cough was higher ( P < 0.001) and the proportion of patients with dyspnea was lower ( P = 0.018) in the positive than in the negative retest group. The positive retest group showed shorter durations between symptom onset and hospitalization ( P < 0.001) and symptom onset and the first positive NAAT ( P = 0.033). The positive retest group had higher basophil counts ( P = 0.023) and direct bilirubin ( P = 0.032) and chlorine concentrations ( P = 0.023) but lower potassium concentrations ( P = 0.001) than the negative retest group. Multivariable regression analysis showed that coughing (OR = 7.59, 95% CI 2.28–25.32, P = 0.001) and serum chloride concentrations (OR = 1.38, 95% CI 1.08–1.77, P = 0.010) were independently associated with a positive retest result. Coughing and serum chloride concentrations were independent risk factors for positive NAAT retest results. Patients with a hospital stay of < 2 weeks or a short incubation period should stay in isolation and be monitored to reduce transmission. These results could help identify patients who require closer surveillance.

Osteogenic and Angiogenic Potency of VEGF165-Transfected Canine Bone Marrow Mesenchymal Cells Combined with Coral Hydroxyapatite in Vitro - Quanyin Zhang; Jie Zhang; Lin Chen; Yunjian Fan; Jiazhen Long; Shuguang Liu (Tissue Engineering and Regenerative Medicine, 2021)

Vagus nerve stimulation in pediatric patients with failed epilepsy surgery - Jeng-Dau Tsai; Pi-Chuan Fan; Wang-Tso Lee; Pi-Lien Hung; Kun-Long Hung; Huei-Shyong Wang; Kuang-Lin Lin (Acta Neurologica Belgica, 2021)

Magnetic Resonance Imaging-Guided and Navigated Individualized Repetitive Transcranial Magnetic Stimulation for Cognitive Impairment in Schizophrenia - Xu-Sha Wu; Tian-Cai Yan; Xian-Yang Wang; Yang Cao; Xiao-Fan Liu; Yu-Fei Fu; Lin Wu; Yin-Chuan Jin; Hong Yin; Long-Biao Cui (Neuroscience Bulletin, 2021)

Fate processes of Parabens, Triclocarban and Triclosan during wastewater treatment: assessment via field measurements and model simulations - Zi-Feng Zhang; Lu Wang; Xianming Zhang; Xue Zhang; Yi-Fan Li; Anatoly Nikolaev; Wen-Long Li (Environmental Science and Pollution Research, 2021)

First report of leaf spot on sorghum caused by Pestalotiopsis trachycarpicola in China - Juan Fan; Hong Bo Qiu; Hai Jiang Long; Wei Zhao; Xiao Long Xiang; An Long Hu (Journal of Plant Pathology, 2021)

First report of leaf spot on Prunus salicina caused by Alternaria alternata in China - Haijiang Long; Sen Yang; Xianhui Yin; Zhibo Zhao; Youhua Long; Juan Fan; Ran Shu; Guifei Gu (Journal of Plant Pathology, 2021)

Deep Learning Convolutional Neural Network Applying for the Arctic Acoustic Tomography Current Inversion Accuracy Improvement - Kangkang Jin; Jian Xu; Zichen Wang; Can Lu; Long Fan; Zhongzheng Li; Jiaxin Zhou (Journal of Marine Science and Engineering, 2021)
Warm current has a strong impact on the melting of sea ice, so clarifying the current features plays a very important role in the Arctic sea ice coverage forecasting study field. Currently, Arctic acoustic tomography is the only feasible method for the large-range current measurement under the Arctic sea ice. Furthermore, affected by the high latitudes Coriolis force, small-scale variability greatly affects the accuracy of Arctic acoustic tomography. However, small-scale variability could not be measured by empirical parameters and resolved by Regularized Least Squares (RLS) in the inverse problem of Arctic acoustic tomography. In this paper, the convolutional neural network (CNN) is proposed to enhance the prediction accuracy in the Arctic, and especially, Gaussian noise is added to reflect the disturbance of the Arctic environment. First, we use the finite element method to build the background ocean model. Then, the deep learning CNN method constructs the non-linear mapping relationship between the acoustic data and the corresponding flow velocity. Finally, the simulation result shows that the deep learning convolutional neural network method being applied to Arctic acoustic tomography could achieve 45.87% accurate improvement than the common RLS method in the current inversion.

Microwave irradiation coupled with zero-valent iron that enhances the composite geopolymerization of chromite ore processing residue and its mechanisms - Tao Huang; Zhen-Xing Cao; Xin-Chuan Fan; Jun-Xun Jin; Chun-Hai Yang; Long-Fei Liu; Shu-Wen Zhang (Environmental Science and Pollution Research, 2021)

Divergent responses in morphology and life history to an Asplanchna kairomone between attached and free-swimming Brachionus dorcas (Rotifera) - Shan Jiang; Yan Bai; Fan Sun; Le-Le Ge; Yi-Long Xi (Hydrobiologia, 2021)

Study on the oxidation and acidification characteristics of the sulfur-containing tailings material - Wenzhao Chen; Gang Wang; Xiqi Liu; Jiaqing Fan; Mingnan Xu; Botao Fei; Hui Long (Arabian Journal of Geosciences, 2021)

High-density mapping for gray leaf spot resistance using two related tropical maize recombinant inbred line populations - Long Chen; Li Liu; Ziwei Li; Yudong Zhang; Manjit S. Kang; Yunyue Wang; Xingming Fan (Molecular Biology Reports, 2021)

Spatial Analysis of the Fishing Behaviour of Tuna Purse Seiners in the Western and Central Pacific Based on Vessel Trajectory Data - Han Zhang; Sheng-Long Yang; Wei Fan; Hui-Min Shi; San-Ling Yuan (Journal of Marine Science and Engineering, 2021)
The Western and Central Pacific Oceans are the primary operational areas of tuna purse seiners worldwide. Describing and analysing the fishing behaviour of vessels is highly significant for the protection of sustainable tuna resources. This study uses Automatic Identification System (AIS) data of 130 tuna purse seiners from July 2017 to May 2018 and uses data mining methods to identify the operating status of tuna purse seiners; describes the spatial characteristics of fishing intensity and the distribution of hot spots; and analyses vessel spatial characteristics to describe their fishing behaviour. The results show that the tuna purse seiner speed has a marked bimodal distribution, which corresponds to high-speed transiting and low-speed seine operation. Additionally, from July to September 2017, the amount of fishing effort invested by tuna purse seiners was lower than that in other months. The tuna purse seiner activity range includes 120° E–60° W, 30° S–30° N, and the activities for fish and seine operations are primarily concentrated at 140° E–150° W, 15° S–15° N. There are differences between the space for fishing search operations and space where fishing events took place in each month. Spatial analysis shows that the high-speed transiting fishing effort map covers a large area, while seine fishing covers a small area. The global spatial autocorrelation analysis shows that the fishing effort devoted to searching for fish stocks has a spatial distribution pattern of aggregation and close aggregation. The results of a hot-spot analysis show that the hot spots on a heat map for finding fish, which are closely spatially clustered, correspond to vessels searching for fish concentration areas and seine operation areas. Correlation testing shows that under a 5° × 5° grid, there is a high positive correlation between the fishing effort invested in finding fish stocks and the yield data, nets (r > 0.8), and a moderate correlation with catch per unit of effort(CPUE) (r > 0.3). Based on vessel behaviour, the location of the fish school can be directly determined, and the distribution of fish clusters and fishing grounds can be predicted. This study can aid in managing tuna purse seiners in the Western and Central Pacific Oceans and analysing changes in fishery resources.

Correlation of exosomal microRNA clusters with bone metastasis in non-small cell lung cancer - Xiao-Rong Yang; Can Pi; Ruoying Yu; Xiao-Jun Fan; Xiao-Xiao Peng; Xu-Chao Zhang; Zhi-Hong Chen; Xue Wu; Yang Shao; Yi-Long Wu; Qing Zhou (Clinical & Experimental Metastasis, 2021)
20–40% of lung cancer patients develop bone metastasis (BM) with significantly decreased overall survival. Currently, BM is mainly diagnosed by computerized tomography (CT) scan or magnetic resonance imaging (MRI) when symptom develops. Novel biomarkers with higher prediction value of BM are needed. Plasma-derived exosomal microRNAs had been isolated and sequenced of total 30 non-small cell lung cancer (NSCLC) patients including 16 with bone metastasis and 14 without bone metastasis. Hierarchical clustering based on the total miRNA profile can clearly separate cancer patients and healthy individuals (H), but not patients with (BM +) or without (BM−) BM. Weight Co-expression network of miRNAs (WGCNA) analyses identified three consensus clusters (A, B, C) of highly correlated miRNAs, among which cluster B (144 miRNAs) showed significantly differential expression in lung cancer patients, especially in BM + group. Pathway analysis of cluster B miRNAs revealed enrichment in metabolic pathways that may involve in preconditioning of the metastatic niche. Three differentially expressed miRNAs between BM + and BM− patients within cluster B were identified as miR-574-5p, a suppressor of Wnt/β-catenin pathway, was down-regulated, while miR-328-3p and miR-423-3p, two activators of the same pathway, were up-regulated in BM + patients. Cluster A miRNAs (n = 49) also showed trend of upregulation in BM + patients. Interestingly, pathway analysis indicated that 43 of them are associated with chromosome14, which has been suggested to promote epithelial-mesenchymal transition (EMT) and bone metastasis.

Size distribution of PM20 observed to the north of the Tibetan Plateau - Cheng-long Zhou; Fan Yang; Wen Huo; Ali Mamtimin; Xing-hua Yang (Journal of Mountain Science, 2021)

Distribution characteristics and main influencing factors of selenium in surface soil of natural selenium-rich area: a case study in Langao County, China - Litao Hao; Jiandong Zhang; Shixi Zhang; Sumin Ma; Bo Li; Jie Long; Jingsen Fan; Kunli Luo (Environmental Geochemistry and Health, 2021)

CD40 induces an antimicrobial response against the intracellular pathogen Streptococcus agalactiae in Nile tilapia, Oreochromis niloticus - Hongli Xia; Huimin Fan; Meng Long; Jun Cheng; Wenjie Chen; Dapeng Yu; Liqun Xia; Yishan Lu (Journal of Fish Diseases, 2021)
Streptococcus agalactiae is a Gram‐positive facultative intracellular bacterium that leads to severe economic loss of tilapia worldwide. Previous studies demonstrated that CD40 contributes to host protection against intracellular injection. In this study, CD40 was characterized from Nile tilapia ( Oreochromis niloticus ), named OnCD40. Sequence analysis showed that open reading frame of OnCD40 was 933 bp, containing a single peptide, a transmembrane domain and four cysteine‐rich domains. The qRT‐PCR revealed that OnCD40 was expressed in all examined tissues with the most abundant ones in spleen and thymus. After S. agalactiae stimulation, the expression of OnCD40 was significantly induced in most of the detected organs. Moreover, OnCD40‐overexpressing fish elicited significant protection against subsequent S. agalactiae challenge; approximately 10000‐fold fewer bacteria were detected in spleen of OnCD40‐overexpressing fish in comparison with control fish. Thus, CD40 had protecting function in Nile tilapia against intracellular pathogens.

Adakitic rocks at convergent plate boundaries: Compositions and petrogenesis - Qiang Wang; Lulu Hao; Xiuzheng Zhang; Jinsheng Zhou; Jun Wang; Qiwei Li; Lin Ma; Long Zhang; Yue Qi; Gongjian Tang; Wei Dan; Jingjing Fan (Science China Earth Sciences, 2020)

Fine-Grained Topography and Modularity of the Macaque Frontal Pole Cortex Revealed by Anatomical Connectivity Profiles - Bin He; Long Cao; Xiaoluan Xia; Baogui Zhang; Dan Zhang; Bo You; Lingzhong Fan; Tianzi Jiang (Neuroscience Bulletin, 2020)
The frontal pole cortex (FPC) plays key roles in various higher-order functions and is highly developed in non-human primates. An essential missing piece of information is the detailed anatomical connections for finer parcellation of the macaque FPC than provided by the previous tracer results. This is important for understanding the functional architecture of the cerebral cortex. Here, combining cross-validation and principal component analysis, we formed a tractography-based parcellation scheme that applied a machine learning algorithm to divide the macaque FPC (2 males and 6 females) into eight subareas using high-resolution diffusion magnetic resonance imaging with the 9.4T Bruker system, and then revealed their subregional connections. Furthermore, we applied improved hierarchical clustering to the obtained parcels to probe the modular structure of the subregions, and found that the dorsolateral FPC, which contains an extension to the medial FPC, was mainly connected to regions of the default-mode network. The ventral FPC was mainly involved in the social-interaction network and the dorsal FPC in the metacognitive network. These results enhance our understanding of the anatomy and circuitry of the macaque brain, and contribute to FPC-related clinical research.

Responses of phytoplankton functional groups to environmental factors in the Pearl River, South China - Shengxing Long; Ting Zhang; Jingjing Fan; Can Li; Kangning Xiong (Environmental Science and Pollution Research, 2020)

High-precision downward continuation of potential fields algorithm utilizing adaptive damping coefficient of generalized minimal residuals - Zhi-Hou Zhang; Xiao-Long Liao; Ze-Yu Shi; Anthony R. Lowry; Yu Yao; Run-Qi Lu; Xiang-Tai Fan; Peng-Fei Liu; Si-Wei Zhao (Applied Geophysics, 2020)

Shortening the sgRNA-DNA interface enables SpCas9 and eSpCas9(1.1) to nick the target DNA strand - Rong Fan; Zhuangzhuang Chai; Sinian Xing; Kunling Chen; Fengti Qiu; Tuanyao Chai; Jin-Long Qiu; Zhengbin Zhang; Huawei Zhang; Caixia Gao (Science China Life Sciences, 2020)

Permeability of loess from the South Jingyang Plateau under different consolidation pressures in terms of the three-dimensional microstructure - Ya-ni Wei; Wen Fan; Ningyu Yu; Long-sheng Deng; Tingting Wei (Bulletin of Engineering Geology and the Environment, 2020)

Two new secondary metabolites from the mangrove endophytic fungus Pleosporales sp. SK7 - Shitong Wen; Weilong Fan; Huixian Guo; Cuiying Huang; Zhangyuan Yan; Yuhua Long (Natural Product Research, 2020)

Cortical morphometry alterations in brain regions involved in emotional, motor-control and self-referential processing in patients with functional constipation - Chunxin Hu; Li Liu; Lei Liu; Junwang Zhang; Yang Hu; Wenchao Zhang; Yueyan Ding; Yuanyuan Wang; Zhida Zhang; Karen M. von Deneen; Long Qian; Huaning Wang; et al. (Brain Imaging and Behavior, 2020)

Identification and functional characterization of glycerol dehydrogenase reveal the role in kojic acid synthesis in Aspergillus oryzae - Junxia Fan; Zhe Zhang; Chuannan Long; Bin He; Zhihong Hu; Chunmiao Jiang; Bin Zeng (World Journal of Microbiology and Biotechnology, 2020)

First record of field dodder (Cuscuta campestris) parasitizing invasive buffalobur (Solanum rostratum) - Wei-Bin Wang; Fan-Fan Gao; Mei-Ni Shao; Ming-Chao Liu; Hong-Feng Zhai; Bo Qu; Yu-Long Feng (Journal of Plant Pathology, 2020)

Molecular cloning and expression analysis of the transcription factor CobHLH40 from Cornus officinalis on the basis of de novo transcriptome sequencing - Dianyun Hou; Wenbin Wang; Mengmeng Yang; Zhihong Li; Jingya Xu; Long Wang; Zhenjie Fan; Yaoyao Wang (Plant Biotechnology Reports, 2020)

Comparative transcriptome analysis reveals a gene expression profile that contributes to rhizome swelling in Panax japonicus var. major - Jun Rong Tang; Ying Chun Lu; Zheng Jie Gao; Wan Ling Song; Kun Hua Wei; Yan Zhao; Qing Yan Tang; Xue Jiao Li; Jun Wen Chen; Guang Hui Zhang; Guang Qiang Long; Wei Fan; et al. (Plant Biosystems, 2020)

Efficacy of amisulpride on postoperative nausea and vomiting: a systematic review and meta-analysis - Lu-Feng Zhang; Chao-Fan Zhang; Wen-Xin Tang; Long He; Yang Liu; Dan-Dan Tian; Yan-Qiu Ai (European Journal of Clinical Pharmacology, 2020)

A novel putative betapartitivirus isolated from the plant-pathogenic fungus Rhizoctonia solani - Yi Chen; Jia En Su; Xi Yun Qin; Zhi Yong Fan; Xiao Hai Zhang; Qing Yu; Zhen Yuan Xia; Cong Ming Zou; Gao Kun Zhao; Zhong Long Lin (Archives of Virology, 2020)

First report of cucumber mosaic virus infecting bahizi (Angelica dahurica) in China - Ruo-Fan Wei; Wan-Long Ding; Yong Li; Rong Wang (Journal of Plant Pathology, 2020)

Correction to: The Effects of 50 nm Unmodified Nano-ZnO on Lipid Metabolism and Semen Quality in Male Mice - Tao Kong; Shu-Hui Zhang; Cai Zhang; Ji-Liang Zhang; Fan Yang; Guo-Yong Wang; Zi-Jun Yang; Dong-Ying Bai; Yun-Yun Shi; Tian-Qi Liu; Hai-Long Li (Biological Trace Element Research, 2020)

The Effects of 50 nm Unmodified Nano-ZnO on Lipid Metabolism and Semen Quality in Male Mice - Tao Kong; Shu-Hui Zhang; Cai Zhang; Ji-Liang Zhang; Fan Yang; Guo-Yong Wang; Zi-Jun Yang; Dong-Ying Bai; Yun-Yun Shi; Tian-Qi Liu; Hai-Long Li (Biological Trace Element Research, 2020)

Prolonged Neo-Tethyan magmatic arc in Myanmar: evidence from geochemistry and Sr–Nd–Hf isotopes of Cretaceous mafic–felsic intrusions in the Banmauk–Kawlin area - Jin-Xiang Li; Wei-Ming Fan; Li-Yun Zhang; Tou-Ping Peng; Ya-Li Sun; Lin Ding; Fu-Long Cai; Kyaing Sein (International Journal of Earth Sciences, 2020)

Seismic design and behavior of self-centering energy dissipation braced steel frame - Long-He Xu; Yu-Sheng Sun; Xiao-Wei Fan; Zhong-Xian Li (Bulletin of Earthquake Engineering, 2020)

MiR-125a-5p Regulates Vitamin D Receptor Expression in a Mouse Model of Experimental Autoimmune Encephalomyelitis - Han-Chun Long; Rui Wu; Chun-Feng Liu; Fei-Long Xiong; Zu Xu; Dian He; Yi-Fan Zhang; Bing Shao; Ping-An Zhang; Guang-Yin Xu; Lan Chu (Neuroscience Bulletin, 2020)

The false smut pathogen Ustilaginoidea virens requires rice stamens for false smut ball formation - Jing Fan; Jie Liu; Zhi‐You Gong; Pei‐Zhou Xu; Xiao‐Hong Hu; Jin‐Long Wu; Guo‐Bang Li; Juan Yang; Yu‐Qiu Wang; Yu‐Feng Zhou; Shuang‐Cheng Li; Li Wang; et al. (Environmental Microbiology, 2020)
Summary Rice false smut has emerged as a serious grain disease in rice production worldwide. The disease is characterized by the transformation of individual rice florets into false smut balls, which is caused by the fungal pathogen Ustilaginoidea virens . To date, little is known about the host factors required for false smut ball formation by U . virens . In this study, we identified histological determinants for the formation of false smut balls by inoculating U . virens into rice floral mutants defective with respect to individual floral parts. The results showed that U . virens could form mature false smut balls in rice floral mutants with defective pistils, but failed to develop false smut balls in the superwoman mutant lacking stamens, identifying that U . virens requires rice stamens to complete its infection cycle. Comparative transcriptome analysis indicated a list of candidate host genes that may facilitate nutrient acquisition by U . virens from the rice stamens, such as SWEET11 , SWEET14 and SUT5 , and genes involved in the biosynthesis of trehalose and raffinose family sugars. These data pinpoint rice stamens as the key target organ of U . virens infection and provide a valuable starting point for dissecting the molecular mechanism of false smut ball formation.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Molecular Cloning and Expression Analysis of Ethylene-Insensitive3-Like 1 (ScEIL1) Gene in Sugarcane - Fan-Wei Wang; Jian-Bin Yu; Dong Xiao; Yang-Rui Li; Long-Fei He; Ai-Qin Wang (Sugar Tech, 2019)

Liangyi Gao extends lifespan and exerts an antiaging effect in Caenorhabditis elegans by modulating DAF-16/FOXO - Liling Zeng; Chen Sun; Zhong Pei; Tianchan Yun; Shaoyi Fan; Simei Long; Tengteng Wu; Ziwen Chen; Zhimin Yang; Fuping Xu (Biogerontology, 2019)

Proteomic Analysis of Shoot Tips from Two Alfalfa Cultivars with Different Florescence - Hao Sun; Ruicai Long; Fan Zhang; Tiejun Zhang; Junmei Kang; Zhen Wang; Chunyu Cao; Jie Yu; Qingchuan Yang (Plant Molecular Biology Reporter, 2019)

Effects of metaxenia on the carbohydrate and mogroside content and related enzyme activities in Siraitia grosvenorii fruit - Zhi-gang Yan; Dong Xiao; Yong-li Xu; Jing Ma; Fan Liu; Long-hua Bai; Xiao-jun Ma (Acta Physiologiae Plantarum, 2019)

Quantitative Evaluation Methods of Brittle Failure Characteristics of Coal: A Case Study of Hard Coal in China - Bo Ren; Shao-hua Wang; Jun-hua Xue; Kai-long Qiu; Guo-feng Yu; Ying-jie Fan; Shi-qi Zhao; Zhen-yu Du; Dong-sheng Deng; Xian-jie Hao (Geotechnical and Geological Engineering, 2019)

Effects of intercropping with Bidens species plants on the growth and cadmium accumulation of Ziziphus acidojujuba seedlings - Qian Deng; Qunxian Deng; Yang Wang; Lei Li; Xingyu Long; Si Ren; Yue Fan; Lijin Lin; Hui Xia; Dong Liang; Jin Wang; Huifen Zhang; et al. (Environmental Monitoring and Assessment, 2019)

Characteristics of runoff processes and nitrogen loss via surface flow and interflow from weathered granite slopes of Southeast China - Long-zhou Deng; Kai Fei; Tian-yu Sun; Li-ping Zhang; Xiao-juan Fan; Liang Ni (Journal of Mountain Science, 2019)

Calpain-2 promotes MKP-1 expression protecting cardiomyocytes in both in vitro and in vivo mouse models of doxorubicin-induced cardiotoxicity - Dong Zheng; Zhaoliang Su; Yi Zhang; Rui Ni; Guo-Chang Fan; Jeffrey Robbins; Long-Sheng Song; Jianmin Li; Tianqing Peng (Archives of Toxicology, 2019)

Effect of Chronic Exposure to Methomyl on Tissue Damage and Apoptosis in Testis of Tilapia (Oreochromis niloticus) and Recovery Pattern - Shun Long Meng; Tao Liu; Xi Chen; Li Ping Qiu; Geng Dong Hu; Chao Song; LiMin Fan; Yao Zheng; Jia Zhang Chen; Pao Xu (Bulletin of Environmental Contamination and Toxicology, 2019)

Toxicity of exogenous antimony to the soil-dwelling springtail Folsomia candida - Xianglong Lin; Zaijin Sun; Long Zhao; Feiyue Fan; Jin Ma; Shutingi Zhao; Hong Hou (Environmental Science and Pollution Research, 2019)

Effect of Rotary Evaporator Water Bath Temperature on Recovery Rate of Phthalate Esters - Long Wang; Ying Liu; Fan Pu; Wen Zhang; Zhongmu Zhou (Bulletin of Environmental Contamination and Toxicology, 2018)

Morphological Change in the Northern Red River Delta, Vietnam - Vuong Van Bui; Daidu Fan; Dac Ve Nguyen; Dinh Lan Tran; Duc Thanh Tran; Van Long Hoang; Thi Hong Hanh Nguyen (Journal of Ocean University of China, 2018)

The primate extinction crisis in China: immediate challenges and a way forward - Baoguo Li; Ming Li; Jinhua Li; Pengfei Fan; Qingyong Ni; Jiqi Lu; Xuming Zhou; Yongcheng Long; Zhigang Jiang; Peng Zhang; Zhipang Huang; Chenming Huang; et al. (Biodiversity and Conservation, 2018)

Flavonoids of Rosa roxburghii Tratt offers protection against radiation induced apoptosis and inflammation in mouse thymus - Sai-Juan Xu; Fan Zhang; Li-Juan Wang; Ming-Hua Hao; Xian-jun Yang; Na-na Li; Hong-long Ji; Ping Xu (Apoptosis, 2018)

Recombinant rabies virus expressing interleukin-6 enhances the immune response in mouse brain - Jun Luo; Boyue Zhang; Yuting Wu; Qin Tian; Meijun Mo; Teng Long; Mingzhu Mei; Ruqi Fan; Ziyu Lyu; He Jiang; Fan Wu; Yingyi Lin; et al. (Archives of Virology, 2018)

Magnetic nanoparticles based cancer therapy: current status and applications - Huan Zhang; Xiao Li Liu; Yi Fan Zhang; Fei Gao; Ga Long Li; Yuan He; Ming Li Peng; Hai Ming Fan (Science China Life Sciences, 2018)

Anomalous gray matter structural networks in recent onset post-traumatic stress disorder - Shun Qi; Yun-Feng Mu; Long-Biao Cui; Jian Zhang; Fan Guo; Qing-Rong Tan; Mei Shi; Kang Liu; Yi-Bin Xi; Nan-Yin Zhang; Xiao-Liang Zhang; Yong He; et al. (Brain Imaging and Behavior, 2018)

One pot simultaneous preparation of both enantiomer of β-amino alcohol and vicinal diol via cascade biocatalysis - Jian-Wei Zhao; Hua-Lei Wu; Jian-Dong Zhang; Wen-Chao Gao; Xiao-Jun Fan; Hong-Hong Chang; Wen-Long Wei; Jian-He Xu (Biotechnology Letters, 2018)

Soybean and cottonseed meals are good candidates for fishmeal replacement in the diet of juvenile Macrobrachium nipponense - Yu-Juan Huang; Nan-Nan Zhang; Wu-Jiang Fan; Yan-Yan Cui; Samwel Mchele Limbu; Fang Qiao; Yun-Long Zhao; Li-Qiao Chen; Zhen-Yu Du; Dong-Liang Li (Aquaculture International, 2018)

Multiple correlation analyses revealed complex relationship between DNA methylation and mRNA expression in human peripheral blood mononuclear cells - Fang-Fei Xie; Fei-Yan Deng; Long-Fei Wu; Xing-Bo Mo; Hong Zhu; Jian Wu; Yu-Fan Guo; Ke-Qin Zeng; Ming-Jun Wang; Xiao-Wei Zhu; Wei Xia; Lan Wang; et al. (Functional & Integrative Genomics, 2018)

Convex model-based calculation of robust seismic fragility curves of isolated continuous girder bridge - X. H. Long; Z. Y. Xie; J. Fan; Y. Miao (Bulletin of Earthquake Engineering, 2018)

Erratum to: The Extent of Heavy Metal Pollution and Their Potential Health Risk in Topsoils of the Massively Urbanized District of Shanghai - Syed Taseer Abbas Jaffar; Fan Luo; Rong Ye; Hassan Younas; Xue-feng Hu; Long-zhu Chen (Archives of Environmental Contamination and Toxicology, 2017)

The Extent of Heavy Metal Pollution and Their Potential Health Risk in Topsoils of the Massively Urbanized District of Shanghai - Syed Taseer Abbas Jaffar; Fan Luo; Rong Ye; Hassan Younas; Xue-feng Hu; Long-zhu Chen (Archives of Environmental Contamination and Toxicology, 2017)

Rock strata movement and subsidence based on MDDA, an improved discontinuous deformation analysis method in mining engineering - Jian-ping Zuo; Yun-jiang Sun; Yue-chun Li; Jin-tao Wang; Xu Wei; Long Fan (Arabian Journal of Geosciences, 2017)

C-Reactive Protein Gene Contributes to the Genetic Susceptibility of Hemorrhagic Stroke in Men: a Case-Control Study in Chinese Han Population - Yong Xue; Long Zhang; Yao Fan; Qianhui Li; Yuzhang Jiang; Chong Shen (Journal of Molecular Neuroscience, 2017)

N-Myc Downstream-Regulated Gene 2 (Ndrg2) Is Involved in Ischemia–Hypoxia-Induced Astrocyte Apoptosis: a Novel Target for Stroke Therapy - Yu-Long Ma; Li-xia Zhang; Guang-lin Liu; Yanhong Fan; Ye Peng; Wu-Gang Hou (Molecular Neurobiology, 2017)

Synthesis of Two Coumarin-Derived Schiff Bases and Investigation of theirs Selectivity for Zn2+ - Long Fan (Journal of Fluorescence, 2017)

Abnormal Effective Connectivity in the Brain is Involved in Auditory Verbal Hallucinations in Schizophrenia - Baojuan Li; Long-Biao Cui; Yi-Bin Xi; Karl J. Friston; Fan Guo; Hua-Ning Wang; Lin-Chuan Zhang; Yuan-Han Bai; Qing-Rong Tan; Hong Yin; Hongbing Lu (Neuroscience Bulletin, 2017)

Integrative multi-omics analysis revealed SNP-lncRNA-mRNA (SLM) networks in human peripheral blood mononuclear cells - Wei Xia; Xiao-Wei Zhu; Xin-Bo Mo; Long-Fei Wu; Jian Wu; Yu-Fan Guo; Ke-Qin Zeng; Ming-Jun Wang; Xiang Lin; Ying-Hua Qiu; Lan Wang; Pei He; et al. (Human Genetics, 2017)

Changes of ammonia, urea contents and transaminase activity in the body during aerial exposure and ammonia loading in Chinese loach Paramisgurnus dabryanus - Yun-Long Zhang; Hai-Long Zhang; Ling-Yu Wang; Bei-Yi Gu; Qi-Xue Fan (Fish Physiology and Biochemistry, 2017)

Persistent mitoKATP Activation Is Involved in the Isoflurane-induced Cytotoxicity - Yan Yang; Xiufang Chen; Haiyan Min; Shiyu Song; Juan Zhang; Shanshan Fan; Long Yi; Hongwei Wang; Xiaoping Gu; Zhengliang Ma; Qian Gao (Molecular Neurobiology, 2017)

Molecular cloning and functional analysis of the drought tolerance gene MsHSP70 from alfalfa (Medicago sativa L.) - Zhenyi Li; Ruicai Long; Tiejun Zhang; Zhen Wang; Fan Zhang; Qingchuan Yang; Junmei Kang; Yan Sun (Journal of Plant Research, 2017)

Integrative analysis for identification of shared markers from various functional cells/tissues for rheumatoid arthritis - Wei Xia; Jian Wu; Fei-Yan Deng; Long-Fei Wu; Yong-Hong Zhang; Yu-Fan Guo; Shu-Feng Lei (Immunogenetics, 2017)

New isocoumarin and stilbenoid derivatives from the tubers of Sparganium stoloniferum (Buch.-Ham.) - Da-Wei Wu; Qiao-Li Liang; Xiao-Long Zhang; Zheng Jiang; Xiu-He Fan; Wei Yue; Qi-Nan Wu (Natural Product Research, 2017)

MicroRNA-146a Promotes Oligodendrogenesis in Stroke - Xian Shuang Liu; Michael Chopp; Wan Long Pan; Xin Li Wang; Bao Yan Fan; Yi Zhang; Haifa Kassis; Rui Lan Zhang; Xiao Ming Zhang; Zheng Gang Zhang (Molecular Neurobiology, 2017)

Genome-wide profiling of genetic variation in Agrobacterium-transformed rice plants - Wen-xu Li; San-ling Wu; Yan-hua Liu; Gu-lei Jin; Hai-jun Zhao; Long-jiang Fan; Qing-yao Shu (Journal of Zhejiang University-SCIENCE B, 2016)

Responses and recovery pattern of sex steroid hormones in testis of Nile tilapia (Oreochromis niloticus) exposed to sublethal concentration of methomyl - Shun Long Meng; Li Ping Qiu; Geng Dong Hu; Li Min Fan; Chao Song; Yao Zheng; Wei Wu; Jian Hong Qu; Dan Dan Li; Jia Zhang Chen; Pao Xu (Ecotoxicology, 2016)

Transcriptome profiling indicating canine parvovirus type 2a as a potential immune activator - Xu-Xu Fan; Yuan Gao; Long Shu; Yan-Quan Wei; Xue-Ping Yao; Sui-Zhong Cao; Guang-Neng Peng; Xiang-Tao Liu; Shi-Qi Sun (Virus Genes, 2016)

A strategy for introducing an endangered plant Mosla hangchowensis to urban area based on nitrogen preference - Mei-Ying Fan; Kai-Xuan Pan; Wen-Juan Han; Yi-Jun Lu; Qi Shen; Meng Wang; Yuan Ren; Ze-Long Qu; Jie Chang; Ying Ge (Acta Physiologiae Plantarum, 2016)

Identification and transcript profiles of citrus growth-regulating factor genes involved in the regulation of leaf and fruit development - Xiao Liu; Ling-Xia Guo; Long-Fei Jin; Yong-Zhong Liu; Tao Liu; Yu-Hua Fan; Shu-Ang Peng (Molecular Biology Reports, 2016)

Downregulation of KDM4A Suppresses the Survival of Glioma Cells by Promoting Autophagy - Bo Wang; Xinxin Fan; Chong Ma; Hui Lei; Qianfa Long; Yuan Chai (Journal of Molecular Neuroscience, 2016)

Occurrence and fate of PBDEs and novel brominated flame retardants in a wastewater treatment plant in Harbin, China - Bo Li; Shao-Jing Sun; Chun-Yan Huo; Wen-Long Li; Ning-Zheng Zhu; Hong Qi; Ling-Jun Kong; Yi-Fan Li; Wan-Li Ma (Environmental Science and Pollution Research, 2016)

Targeting of water-using networks involving regeneration with a graphical approach - Xiao-Yan Fan; Da-Long Xu; Jian-Feng Zhu; Zhi-Yong Liu (Clean Technologies and Environmental Policy, 2016)

Levels, congener profile and inventory of polychlorinated biphenyls in sediment from the Songhua River in the vicinity of cement plant, China: a case study - Song Cui; Qiang Fu; Yi-Fan Li; Wen-long Li; Tian-xiao Li; Min Wang; Zhen-xiang Xing; Lu-ji Zhang (Environmental Science and Pollution Research, 2016)

Learning curves of percutaneous endoscopic lumbar discectomy in transforaminal approach at the L4/5 and L5/S1 levels: a comparative study - Xin-bo Wu; Guo-xin Fan; Xin Gu; Tu-gang Shen; Xiao-fei Guan; An-nan Hu; Hai-long Zhang; Shi-sheng He (Journal of Zhejiang University-SCIENCE B, 2016)

The occurrence and fate of siloxanes in wastewater treatment plant in Harbin, China - Bo Li; Wen-Long Li; Shao-Jing Sun; Hong Qi; Wan-Li Ma; Li-Yan Liu; Zi-Feng Zhang; Ning-Zheng Zhu; Yi-Fan Li (Environmental Science and Pollution Research, 2016)

Manufacturer identification and storage time determination of “Dong’e Ejiao” using near infrared spectroscopy and chemometrics - Wen-long Li; Hai-fan Han; Lu Zhang; Yan Zhang; Hai-bin Qu (Journal of Zhejiang University-SCIENCE B, 2016)

Sustainability of in situ remediation of Cu- and Cd-contaminated soils with one-time application of amendments in Guixi, China - Hongbiao Cui; Yuchao Fan; Lei Xu; Jing Zhou; Dongmei Zhou; Jingdong Mao; Guodong Fang; Long Cang; Zhenqiu Zhu (Journal of Soils and Sediments, 2016)

A Novel Chromone Schiff-Base Fluorescent Chemosensor for Cd(II) Based on C=N Isomerization - Jun Yan; Long Fan; Jing-can Qin; Chao-rui Li; Zheng-yin Yang (Journal of Fluorescence, 2016)

NPAS4 Facilitates the Autophagic Clearance of Endogenous Tau in Rat Cortical Neurons - Wenhui Fan; Yan Long; Yujie Lai; Xuefeng Wang; Guojun Chen; Binglin Zhu (Journal of Molecular Neuroscience, 2016)

High pH-induced flocculation of marine Chlorella sp. for biofuel production - Fangfang Yang; Wenzhou Xiang; Jiewei Fan; Hualian Wu; Tao Li; Lijuan Long (Journal of Applied Phycology, 2016)

Bacterioplankton community analysis in tilapia ponds by Illumina high-throughput sequencing - Li Min Fan; Kamira Barry; Geng Dong Hu; Shun long Meng; Chao Song; Wei Wu; Jia Zhang Chen; Pao Xu (World Journal of Microbiology and Biotechnology, 2016)

DNA barcoding reveals commercial fraud related to yak jerky sold in China - Yunyu Wang; Kai He; Long Fan; Yushui Wang; Shifang Wu; Robert W. Murphy; Wenzhi Wang; Yaping Zhang (Science China Life Sciences, 2016)

A Chromone-Derived Schiff-Base Ligand as Al3+ “Turn on” Fluorescent Sensor: Synthesis and Spectroscopic Properties - Chao-rui Li; Jing-can Qin; Bao-dui Wang; Long Fan; Jun Yan; Zheng-yin Yang (Journal of Fluorescence, 2016)

Physiological characterization of maize tolerance to low dose of aluminum, highlighted by promoted leaf growth - Liang Wang; Xian-Wei Fan; Jian-Long Pan; Zhang-Bao Huang; You-Zhi Li (Planta, 2015)

Changes in digestive enzyme activities during larval development of Chinese loach Paramisgurnus dabryanus (Dabry de Thiersant, 1872) - Yun-Long Zhang; Qiao-Wan Wu; Wei-Hua Hu; Fan Wang; Zhong-Bo Zhao; Hui He; Wei-Han Shao; Qi-Xue Fan (Fish Physiology and Biochemistry, 2015)

A long-term volume transport time series estimated by combining in situ observation and satellite altimeter data in the northern South China Sea - Xiao-Hua Zhu; Ruixiang Zhao; Xinyu Guo; Yu Long; Yun-Long Ma; Xiaopeng Fan (Journal of Oceanography, 2015)

A Potent Multi-functional Neuroprotective Derivative of Tetramethylpyrazine - Hai-Yun Chen; Da-Ping Xu; Guo-Lian Tan; Wei Cai; Gao-Xiao Zhang; Wei Cui; Jin-Zhao Wang; Cheng Long; Ye-Wei Sun; Pei Yu; Karl Wahkeung Tsim; Zai-Jun Zhang; et al. (Journal of Molecular Neuroscience, 2015)

Isolation and functional characterization of salt-stress induced RCI2-like genes from Medicago sativa and Medicago truncatula - Ruicai Long; Fan Zhang; Zhenyi Li; Mingna Li; Lili Cong; Junmei Kang; Tiejun Zhang; Zhongxiang Zhao; Yan Sun; Qingchuan Yang (Journal of Plant Research, 2015)

Combining Bone Marrow Stromal Cells with Green Tea Polyphenols Attenuates the Blood-Spinal Cord Barrier Permeability in Rats with Compression Spinal Cord Injury - De-shui Yu; Li-bo Liu; Yang Cao; Yan-song Wang; Yun-long Bi; Zi-jian Wei; Song-ming Tong; Gang Lv; Xi-fan Mei (Journal of Molecular Neuroscience, 2015)

Polymorphic microsatellite loci in the Chinese skink, Plestiodon chinensis (squamata: scincidae) - Tian-qi Fan; Tian-long Fu; Yan-xia Zhang; Hong-liang Lu; Chao-nan Zhu; Shan Sun; Hong Li (Conservation Genetics Resources, 2015)

Ordovician radiolarians from the Yinisala ophiolitic mélange and their significance in western Junggar, Xinjiang, NW China - RuiWen Zong; ZiZhang Wang; YiMing Gong; GuoCan Wang; Long Xiao; ZhiHong Wang; RuoYing Fan (Science China Earth Sciences, 2015)

Integration of metal chemical forms and subcellular partitioning to understand metal toxicity in two lettuce (Lactuca sativa L.) cultivars - Cheng-Cheng Li; Fei Dang; Long Cang; Chui-Fan Zhou; Dong-Mei Zhou (Plant and Soil, 2014)

Mitochondrial genomes of domestic animals need scrutiny - Ni‐Ni Shi; Long Fan; Yong‐Gang Yao; Min‐Sheng Peng; Ya‐Ping Zhang (Molecular Ecology, 2014)
More than 1000 complete or near‐complete mitochondrial DNA (mt DNA ) sequences have been deposited in GenBank for eight common domestic animals (cattle, dog, goat, horse, pig, sheep, yak and chicken) and their close wild ancestors or relatives, as well. Nevertheless, few efforts have been performed to evaluate the sequence data quality. Herein, we conducted a phylogenetic survey of these complete or near‐complete mt DNA sequences based on mt DNA haplogroup trees for the eight animals. We show that errors due to artificial recombination, surplus of mutations and phantom mutations do exist in 14.5% (194/1342) of mt DNA sequences and all of them should be treated with wide caution. We propose some caveats for future mt DNA studies of domestic animals.

Hepatic Antioxidant Enzymes SOD and CAT of Nile Tilapia (Oreochromis niloticus) in Response to Pesticide Methomyl and Recovery Pattern - Shun Long Meng; Jia Zhang Chen; Pao Xu; Jian Hong Qu; Li Min Fan; Chao Song; Li Ping Qiu (Bulletin of Environmental Contamination and Toxicology, 2014)

Combined effect of five single nucleotide polymorphisms related to IL23/Th17 pathway in the risk of psoriasis - Xianyong Yin; Hui Cheng; Ran Zhang; Xing Fan; Fusheng Zhou; Long Jiang; Xianfa Tang; Gang Chen; Xianbo Zuo; Xiaodong Zheng; Sen Yang; Xuejun Zhang (Immunogenetics, 2014)

Identification of critical amino acid residues for chloride binding of Bacillus licheniformis trehalose-6-phosphate hydrolase - Ping-Lin Ong; Tzu-Ting Chuang; Tzu-Fan Wang; Long-Liu Lin (Biologia, 2014)

Microbiota Regulates the TLR7 Signaling Pathway Against Respiratory Tract Influenza A Virus Infection - Sha Wu; Zhen-You Jiang; Yi-Fan Sun; Bin Yu; Jia Chen; Cong-Qi Dai; Xian-Lin Wu; Xiao-Long Tang; Xiao-Yin Chen (Current Microbiology, 2013)

Transjugular intrahepatic portosystemic shunt induced short- and long-term cerebral blood flow variations in cirrhotic patients: an arterial spin labeling MRI study - Gang Zheng; Long Jiang Zhang; Yue Cao; Zhiying Pan; Rong Feng Qi; Ling Ni; Donghong Shi; Xinxin Fan; Guang Ming Lu (Metabolic Brain Disease, 2013)

Phylogeography of Sophora davidii (Leguminosae) across the ‘Tanaka‐Kaiyong Line’, an important phytogeographic boundary in Southwest China - Deng Mei Fan; Ji Pei Yue; Ze Long Nie; Zhi Min Li; Hans Peter Comes; Hang Sun (Molecular Ecology, 2013)
The ‘Tanaka‐Kaiyong Line’ ( TKL ) is a major phytogeographic boundary in Southwest China, separating East Asia's Sino‐Himalayan and Sino‐Japanese Floras. However, little is known about the importance of this boundary in promoting intraspecific phylogeographic subdivision and divergence. Using chloroplast (cp DNA ) and nuclear‐intron ( nDNA ) sequence data, we reconstructed the population history of Sophora davidii , a drought‐tolerant riparian shrub widely distributed on either side of the TKL . Specifically, we aimed at testing two long‐standing explanations for possible vicariant events across the TKL: (i) Late Pliocene ( c . 3 Ma) geological uplift of the eastern Qinghai‐Tibetan Plateau (QTP) or (ii) a sharp environmental gradient associated with the establishment of different monsoon regimes on either side of the TKL during the (Late) Pleistocene. Our genealogical analyses detected a major west–east split in cpDNA, geographically largely consistent with the TKL, and dated to c . 1.28 Ma (95% HPD: 0.21–2.96 Ma), hence postdating the latest phase of eastern QTP uplift. Furthermore, integrating cpDNA phylogeographic patterns with mismatch analyses, we found multiple refugial isolation and long‐term demographic stability of populations in the west (Hengduan Mountain Range) compared with extensive range expansions in the east, possibly during the last glacial period(s) and followed by differentiation into regional sublineages (southeast: Yunnan‐Guizhou Plateau vs. northeast: Qinling Mts./Loess Plateau). Although nuclear differentiation was less marked, the geographical pattern of nDNA haplotypes provided some further indication of the species' eastward expansion, possibly from source populations located just east of the TKL (lower Jinshajiang region). Overall, the present data reject the geological (tectonic) explanation for the TKL and, instead, provide supportive evidence for its role as a climatically driven barrier to present‐day plant dispersal. In addition, our study highlights changing temperatures and vegetation types during the last glacial period(s), along with aspects of regional topography, to be important determinants of the glacial eastward expansion of S. davidii . In consequence, our study lends support to a ‘glacial out‐of‐Hengduan Mts’. hypothesis for the xerophytic‐riparian flora of Southwest China, which in turn is inconsistent with the traditional view of the TKL as a ‘classical’ vicariant‐biogeographic boundary.

Diversity arrays technology (DArT) for studying the genetic polymorphism of flue-cured tobacco (Nicotiana tabacum) - Xiu-ping Lu; Bing-guang Xiao; Yong-ping Li; Yi-jie Gui; Yu Wang; Long-jiang Fan (Journal of Zhejiang University-SCIENCE B, 2013)

Application of a web-based remote agro-ecological monitoring system for observing spatial distribution and dynamics of Bactrocera dorsalis in fruit orchards - Joe-Air Jiang; Tzu-Shiang Lin; En-Cheng Yang; Chwan-Lu Tseng; Chia-Pang Chen; Chung-Wei Yen; Xiang-Yao Zheng; Chun-Yi Liu; Ren-Hau Liu; Yu-Fan Chen; Wan-Yi Chang; Cheng-Long Chuang (Precision Agriculture, 2013)

Three genetic systems controlling growth, development and productivity of rice (Oryza sativa L.): a reevaluation of the ‘Green Revolution’ - Fan Zhang; Yun-Zhu Jiang; Si-Bin Yu; J. Ali; A. H. Paterson; G. S. Khush; Jian-Long Xu; Yong-Ming Gao; Bin-Ying Fu; R. Lafitte; Zhi-Kang Li (Theoretical and Applied Genetics, 2013)

Ventral medial prefrontal functional connectivity and emotion regulation in chronic schizophrenia: A pilot study - Feng-Mei Fan; Shu-Ping Tan; Fu-De Yang; Yun-Long Tan; Yan-Li Zhao; Nan Chen; Bin-Bin Li; Chong-Sheng Song; Yun-Hui Wang; Zhen Jin; Dong-Feng Zhou; Michael P. Milham; et al. (Neuroscience Bulletin, 2013)

Compressibility and structural properties of jadeite, NaAlSi2O6 at high pressure - Xiuling Wu; Xiaoyu Fan; Fei Qin; Dawei Meng; Xiaoling Zhang; Long Chen; Weiping Liu; Jianping Zheng (Journal of Earth Science, 2013)

Novel and ancient HMW glutenin genes from Aegilops tauschii and their phylogenetic positions - Wen-Jie Chen; Xing Fan; Bo Zhang; Bao-Long Liu; Ze-Hong Yan; Lian-Quan Zhang; Zhong-Wei Yuan; You-Liang Zheng; Huai-Gang Zhang; Deng-Cai Liu (Genetic Resources and Crop Evolution, 2012)

Possible Correlation between Selenoprotein W and Myogenic Regulatory Factors in Chicken Embryonic Myoblasts - Qiong Wu; Hai-Dong Yao; Zi-Wei Zhang; Bo Zhang; Fan-Yu Meng; Shi-Wen Xu; Xiao-Long Wang (Biological Trace Element Research, 2012)

Remediation of polychlorinated biphenyl-contaminated soil by soil washing and subsequent TiO2 photocatalytic degradation - Xiangdong Zhu; Dongmei Zhou; Yujun Wang; Long Cang; Guodong Fang; Jianxin Fan (Journal of Soils and Sediments, 2012)

Ginsenoside Rg1 inhibits autophagy in H9c2 cardiomyocytes exposed to hypoxia/reoxygenation - Zi-Long Zhang; Yan Fan; Mei-Lin Liu (Molecular and Cellular Biochemistry, 2012)

Association between TaqIB polymorphism of cholesteryl ester transfer protein and coronary artery disease in the Chinese population - Qi Yu; En-qi Liu; Si-hai Zhao; Ya-feng Li; Yan-li Wang; Yu-long Chen; Ke-na Wei; Bing-qiao Huang; Jian-lin Fan; Peng-hui Yang (Journal of Zhejiang University-SCIENCE B, 2012)

Temperature reconstruction from tree-ring maximum latewood density of Qinghai spruce in middle Hexi Corridor, China - Feng Chen; Yu-jiang Yuan; Wen-shou Wei; Shu-long Yu; Zi-ang Fan; Rui-bo Zhang; Tong-wen Zhang; Qin Li; Hua-ming Shang (Theoretical and Applied Climatology, 2012)

Protection against Escherichia coli O157:H7 challenge by immunization of mice with purified Tir proteins - Hong-ying Fan; Ling Wang; Jun Luo; Bei-guo Long (Molecular Biology Reports, 2012)

DNA methylation polymorphism in flue-cured tobacco and candidate markers for tobacco mosaic virus resistance - Jie-hong Zhao; Ji-shun Zhang; Yi Wang; Ren-gang Wang; Chun Wu; Long-jiang Fan; Xue-liang Ren (Journal of Zhejiang University-SCIENCE B, 2011)

Development and application of a set of breeder-friendly SNP markers for genetic analyses and molecular breeding of rice (Oryza sativa L.) - Haodong Chen; Hang He; Yanjiao Zou; Wei Chen; Renbo Yu; Xia Liu; Yang Yang; Yong-Ming Gao; Jian-Long Xu; Liu-Min Fan; Yi Li; Zhi-Kang Li; et al. (Theoretical and Applied Genetics, 2011)

Tectonic dynamics and correlation of major earthquake sequences of the Xiaojiang and Qujiang-Shiping fault systems, Yunnan, China - XueZe Wen; Fang Du; Feng Long; Jun Fan; Hang Zhu (Science China Earth Sciences, 2011)

Cooperation of deregulated Notch signaling and Ras pathway in human hepatocarcinogenesis - Renhua Fan; Pingsheng Chen; Di Zhao; Jing long Tong; Jing Li; Feng Liu (Journal of Molecular Histology, 2011)

Fluid Dynamics Analysis of a Novel Micropatterned Cell Bioreactor - Yuhong Cui; Bo Huo; Shujin Sun; Fan Yang; Yuxin Gao; Jun Pan; Mian Long (Annals of Biomedical Engineering, 2011)

Nicotinic acetylcholine receptor alpha7 subunit is time-dependently expressed in distinct cell types during skin wound healing in mice - Yan-Yan Fan; Tian-Shui Yu; Tao Wang; Wei-Wei Liu; Rui Zhao; Shu-Tao Zhang; Wen-Xiang Ma; Ji-Long Zheng; Da-Wei Guan (Histochemistry and Cell Biology, 2011)

Maintenance of Multifemale Social Organization in a Group of Nomascus concolor at Wuliang Mountain, Yunnan, China - Peng-Fei Fan; Xue-Long Jiang (International Journal of Primatology, 2010)

Short hairpin RNA targeting NP mRNA inhibiting Newcastle disease virus production and other viral structural mRNA transcription - Hua Yue; Shu Deng; Fa-long Yang; Ding-fei Li; An-jing Fu; Fan Yang; Cheng Tang (Virus Genes, 2009)

Predation on giant flying squirrels (Petaurista philippensis) by black crested gibbons (Nomascus concolor jingdongensis) at Mt. Wuliang, Yunnan, China - Peng-fei Fan; Xue-long Jiang (Primates, 2009)

Analysis of synonymous codon usage and evolution of begomoviruses - Xiao-zhong Xu; Qing-po Liu; Long-jiang Fan; Xiao-feng Cui; Xue-ping Zhou (Journal of Zhejiang University-SCIENCE B, 2008)

Seasonal Variations in the Activity Budget of Nomascus concolor jingdongensis at Mt. Wuliang, Central Yunnan, China: Effects of Diet and Temperature - Peng-Fei Fan; Qing-Yong Ni; Guo-Zheng Sun; Bei Huang; Xue-Long Jiang (International Journal of Primatology, 2008)

Molecular cloning and tissue specific expression of an elongation factor 1A gene in sugarcane stalks - Ai-Qin Wang; Ying-Zhi Qin; Xing-Zhi Ye; Ye-Geng Fan; Long-Fei He; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2008)

Virulence of H5N1 avian influenza virus enhanced by a 15-nucleotide deletion in the viral nonstructural gene - Jin-Xue Long; Da-Xin Peng; Yu-Liang Liu; Yan-Tao Wu; Xiu-Fan Liu (Virus Genes, 2008)

Microsatellite Analysis of Genetic Variation and Population Genetic Differentiation in Autotetraploid and Diploid Rice - Li Luan; Xing Wang; Wen-Bo Long; Yu-Hua Liu; Sheng-Bin Tu; Zhan-Peng Zhao; Fan-Lun Kong; Mao-Qun Yu (Biochemical Genetics, 2008)

Analysis of metabolic flux in Escherichia coli expressing human-like collagen in fed-batch culture - Yan E. Luo; Dai D. Fan; Long A. Shang; Hui J. Shi; Xiao X. Ma; Yu Mi; Gui F. Zhao (Biotechnology Letters, 2008)

Genes expression analyses of sea-island cotton (Gossypium barbadense L.) during fiber development - Li-Li Tu; Xian-Long Zhang; Shao-Guang Liang; Di-Qiu Liu; Long-Fu Zhu; Fan-Chang Zeng; Yi-Chun Nie; Xiao-Ping Guo; Feng-Lin Deng; Jia-Fu Tan; Li Xu (Plant Cell Reports, 2007)

A rice gene activation/knockout mutant resource for high throughput functional genomics - Yue-Ie Hsing; Chyr-Guan Chern; Ming-Jen Fan; Po-Chang Lu; Ku-Ting Chen; Shuen-Fang Lo; Peng-Kai Sun; Shin-Lon Ho; Kuo-Wei Lee; Yi-Chieh Wang; Wen-Lii Huang; Swee-Suak Ko; et al. (Plant Molecular Biology, 2007)

A New Retroposed Gene in Drosophila Heterochromatin Detected by Microarray-Based Comparative Genomic Hybridization - Chuanzhu Fan; Manyuan Long (Journal of Molecular Evolution, 2007)

Nitrogen Fixation of Faba Bean (Vicia faba L.) Interacting with a Non-legume in Two Contrasting Intercropping Systems - Fenliang Fan; Fusuo Zhang; Yana Song; Jianhao Sun; Xingguo Bao; Tianwen Guo; Long Li (Plant and Soil, 2006)

Sustainable rural livelihood and ecological shelter construction in upper reaches of changjiang river - Ke-rong Sheng; Jie Fan; Hai-long Ma (Chinese Geographical Science, 2006)

New Fluorescent Labels: 4- and 7-Chlorofluorescein - Feng-Yan Ge; Xi-Long Yan; Fan-Yong Yan; Hui-Ying Pan; Li-Gong Chen (Journal of Fluorescence, 2005)

Maximal sequence length of exact match between members from a gene family during early evolution - Xiao Wen; Xing-yi Guo; Long-jiang Fan (Journal of Zhejiang University-SCIENCE B, 2005)

Two ancient rounds of polyploidy in rice genome - Yang Zhang; Guo-hua Xu; Xing-yi Guo; Long-jiang Fan (Journal of Zhejiang University-SCIENCE B, 2005)

Note: Identification of Three Novel Insertion/Deletion Mutations in Wilson Disease's Gene - Yuxin Fan; Long Yu; Yongzhu Han; Mingshan Ren; Renmin Yang; Shouyuan Zhao (Biochemical Genetics, 2004)

Biooxidation of ferrous iron by immobilized Acidithiobacillus ferrooxidans in poly(vinyl alcohol) cryogel carriers - Zhong-er Long; Yunhong Huang; Zhaoling Cai; Wei Cong; Fan Ouyang (Biotechnology Letters, 2003)

Mutation analysis of hereditary multiple exostoses in the Chinese - L. Xu; J. Xia; H. Jiang; J. Zhou; H. Li; D. Wang; Q. Pan; Z. Long; C. Fan; H.-X. Deng (Human Genetics, 1999)

Cloning and Tissue Expressional Characterization of a Full-Length cDNA Encoding Human Neuronal Protein P17.3 - Yingyu Cui; Long Yu; Ruomu Gong; Min Zhang; Yuxin Fan; Peng Yue; Shouyuan Zhao (Biochemical Genetics, 1999)